Self-propelled AzBA-algae microrobots enable rapid and stable dynamic remediation of sulfamethoxazole in aqueous environments - Jinxin Liu; Lin Cheng; Han Fu; Zhili Gao; Junjie Li; Jiawei He; Cheng Tian; Shusheng Zhang (Bioresource Technology, 2026)

Biochar enhances anaerobic oxidation of methane coupled with Cr(VI) reduction: Pyrolysis temperature-dependent electron transfer pathways and regulatory mechanisms - Lianfu Liang; Yepu Li; Xiaofeng Fu; Rui Lin; Keying Liu; Zhiqiang Zhao (Bioresource Technology, 2026)

Projected climate change impacts on crop yields in China's drylands by statistical models and emulators - Shuangshuang Zi; Yiqing Liu; Yan Li; Shuai Wang; Shan Sang; Huiqing Lin; Chengcheng Hou; Fengyu Fu; Bojie Fu (Agricultural Systems, 2026)

Salidroside alleviates sepsis-associated acute lung injury through modulation of the ERK/FoxO3a signaling axis and improvement of impaired autophagic flux - Xiangli Ma; Yurong Zhang; Zhenzhen Huang; Ling Zhang; Yujie Lin; Xu Fu; Peiwu Li (Molecular Biology Reports, 2026)

Monsoon and Westerlies drive particle size sorting of microplastics in the riparian zone of the Tibetan Plateau interior - Qinghui Zeng; He Gao; Yang Zhou; Suxing Fu; Huixin Zeng; Chaowei Zhou; Zhaofang Han; Jian Su; Kexin Ma; Junting Li; Lin Zhou; Haiping Liu (Water Research, 2026)

High spatial variations of potential nitrification and N2O production across the Yangtze River and associated major tributaries - Caixia Lan; Qiuxun Lin; Mengting Qi; Yuxuan Fu; Guosen Zhang; Ye Li; Min Liu; Lijun Hou; Xiaofei Li (Water Research, 2026)

Erratum to “Spatial metabolomics reveals tissue-specific oxidative imbalance and sulfur amino acid metabolism during postharvest deterioration of goji berry (Lycium barbarum L.)” [Postharv. Biol. Technol. 240 (2026) 114463] - Hanxi Li; Long Xiang; Xintong Wang; Yukun Xi; Fu Wang; Lin Chen; Hongping Chen (Postharvest Biology and Technology, 2026)

TBBPA facilitates splenic inflammation and pyroptosis by targeting HMGB1 - Fu-Wei Jiang; Jing-Han Lin; Jia-Xin Wang; Ming-Shan Chen; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Ming Lou; Zi-Yan Hu; Yi Zhao; Jin-Long Li (Journal of Environmental Sciences, 2026)

Infectious spleen and kidney necrosis virus promotes replication organelle formation and sphingolipid biosynthesis to facilitate viral replication - Wenwen Xiao; Xiaozhe Fu; Yilin Zhu; Qiquan Liu; Qiang Lin; Hongru Liang; Xia Luo; Yinjie Niu; Baofu Ma; Ningqiu Li (Fish & Shellfish Immunology, 2026)

Intermittent organophosphate pesticide exposure induces hepatic injury in goats with subclinical fatty liver via immune activation and energy metabolism reprogramming - Dechun Chen; Tianjun Yang; Ting Zhao; Anzhu Li; Qingjia Lin; Xinying Zhou; Huanrong Zhang; Jian Fu; Falong Yang; Haifeng Liu (Environmental Pollution, 2026)

Exciton regulation and directional electron transfer in artemisia-derived carbon dots/g-C3N4 heterojunction for enhanced visible-light photocatalytic antibacterial activity - Mingzhu Yuan; Weile Xie; Ran Qiu; Mingxin Zhou; Yangyang Li; Yuanxu Liu; Zibing Liu; Yupeng Yuan; Da Fu; Xiangang Lin (Chemical Engineering Journal, 2026)

Mechanism of Kushen Tongguan Pill on benign prostatic hyperplasia: roles of TLR4/NF-κB pathway and macrophage M1 polarization - Shaofeng Chen; Jie Wang; Yuhong Feng; Chunxu Li; Fu Wang; Lin Miao; Yaojun Li; Yangyang Lei; Qiang Geng; Zhong Li; Feng Zhao; Yuan Sun; et al. (Journal of Molecular Histology, 2026)

Persistent carbon composition converges across vegetated and unvegetated coastal soils despite contrasting stabilization pathways - Yuan Li; Joeri Kaal; Chuancheng Fu; Dongdong Zhang; Peter I. Macreadie; Ting Wang; Lin Zeng; Feilong Hu; Guangxuan Han; Yongming Luo (Water Research, 2026)

Spatial metabolomics reveals tissue-specific oxidative imbalance and sulfur amino acid metabolism during postharvest deterioration of goji berry (Lycium barbarum L.) - Hanxi Li; Long Xiang; Xintong Wang; Yukun Xi; Fu Wang; Lin Chen; Hongping Chen (Postharvest Biology and Technology, 2026)

Physicochemical pretreatment for enhancing anammox and related coupled processes in the treatment of high-strength ammonium industrial wastewater: Research advances and prospects - Long Jiao; Xue-chao Wang; Jia-lin Xue; Zhuo-yuan You; Jie Li; Jia-jun Fu; Hong Yu (Journal of Environmental Chemical Engineering, 2026)

Transformation of antibiotics mediated by iron-bearing minerals: A review - Yu Fu; Tao Wang; Jiamin Cai; Jieyun Lin; Shi Chen; Jiang Li; Bin Wang; Shaoqi Zhou; Yuanyuan Liu (Journal of Environmental Sciences, 2026)

Diversity of Diaporthe species associated with post-harvest decay on kiwifruit in China - Lu Feng; Yang Lin; Chao Li; Jiatao Xie; Jiasen Cheng; Bo Li; Tao Chen; Daohong Jiang; Yanping Fu (Fungal Biology, 2026)

A non-complex-algorithmic and manually calculable fragment-resolved isotope framework ratios for geographic authentication of refined sugar - ShuoCong Li; ZhenPeng Zhen; XiaoFeng Xie; RongWei Fu; DeJin Kong; Zhu Lin; ZhaoHua Ping; GuiHua Wang; YuFeng Gao (Food Chemistry, 2026)

Multi-level biomarker responses in Eisenia fetida co-exposed to PE-MPs and DiBP: An ecological risk assessment based on physiological, biochemical, and molecular indicators - Yanan Zhang; Yumu Luo; Zhensi Meng; Jun Luo; Ke Li; Yuhang Lin; Minle Li; Rongren Bin; Mingming Fu; Ming Hung Wong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Synergistic alkaline etching and nitrogen lattice occupation strategy enables gradient defluorinated cathode for high-performance Li/CFx batteries - Hongwei Cai; Xiaoxiao Pan; Cong Li; Hao Luo; Menghan Lin; Mingyi Shang; Jiqiong Lian; Yanan Fu; Hongjun Yue; Huixin Chen; Xiaolong Li; Yujin Tong; et al. (Chemical Engineering Journal, 2026)

An objective detection method for tinnitus using memristors - Hui Ma; Xiaoyan Ma; Yingying Xuan; Zelin Cao; Lin Li; Kaikai Gao; Mengna Wang; Ruifeng Qiao; Qin Hu; Wentao Yan; Kun Wang; Haoyuan Wang; et al. (Chemical Engineering Journal, 2026)

Tailoring Cu-doped SmMn2O5 with rich Mn4+ active sites for highly efficient and selective ultra-low temperature photothermal NOx catalytic reduction - Mingxia Wu; Jiale Cheng; Yu Wang; Siying Zhang; Yi Li; Ruixue Bai; Chunming Yang; Lin Liu; Feng Fu; Jun Wan (Chemical Engineering Journal, 2026)

Micro-bipolar interface in catalyst layers for polymer electrolyte membrane fuel cell - Yunqi Li; Xinkai Zhang; Hanfei Xie; Qi Zhang; Xiaofang Shen; Yuheng Zhou; Haining Wang; Yiyang Liu; Jin Zhang; Wen Li; Jiashuo Fu; Lin Zhuang; et al. (Chemical Engineering Journal, 2026)

A dual-mode self-verification strategy based on the bimetallic ion amplification effect: Enabling highly sensitive detection of the chemotherapy-induced cardiac toxicity biomarkers IL-6 and MPO - Haiying He; Bolu Sun; Jiali Kang; Mian Chen; Chenyu Qin; Xiangdong Wang; Yuxin Dong; Jiaru Fu; Yaru Zhang; Yuqiong Wu; Huajie Li; Lin Yang; et al. (Analytica Chimica Acta, 2026)

Inside-out conversion of open pores into closed nanopores enables high-plateau hard carbon anodes for sodium-ion batteries - Zhuo Xiong; Rui Li; Ping Liu; Shuang Lin; Chaoshu Zhao; Wenyuan Fu; Jiale Shen; Lili Xiao; Xuedan Chen; Jianping Long; Xianguang Zeng; Anjun Hu; et al. (Chemical Engineering Journal, 2026)

A fully human antibody A140 neutralizes abrin toxin via lysosomal intracellular mechanisms, confers potent protection in vitro and in vivo, and reverses transcriptomic dysregulation with a Favorable safety profile - Feng Qin; Shi-You Chen; Peng Lin; Bin Wang; Xin Fu; Jian-Li Jiang; Hong-Yong Cui; Shi-Jie Wang (Toxicology and Applied Pharmacology, 2026)

Multiomics analysis of the tolerance thresholds and decline mechanisms under sequential cumulative PE-MPs exposure in a novel HN-AD bacteria-Chlorella system treating synthetic wastewater - Qian Zhang; Lin Deng; Bixiang Nie; Fu Wei; Zheng Chen; Siyu Hua; Xiaozhuo Li; Chenhui Zhang; Yuyang Zhang; Quanli Chen (Process Safety and Environmental Protection, 2026)

Urinary biomarkers of emerging contaminants in relation to prevalent Parkinson's disease: An exploratory mixture and network toxicology study - Chiqun Shan; Yiming Ge; Junye Bian; Yuli Lin; Bo Fu; Qinru Xiao; Aihua Guo; Mengyan Li; Pan Xu; Yi Chen; Haobo Chen; Shaoyou Lu (Journal of Hazardous Materials, 2026)

Occurrence and leaching of per- and polyfluoroalkyl substances in waste incineration residues: Insights into thermodynamic mechanisms and implications for environmental release - Lanlan Fu; Xingyao Huang; Xuemei Liu; Nan Zhang; Rui Ma; Xinyue Wang; Yue Zhi; Lin Li; Xiaoming Wang (Journal of Hazardous Materials, 2026)

The content, bio-accessibility and in vitro bioavailability of lead species in various seafood samples collected from Fujian, China - Siyi liu; Ying Peng; Yuting Yang; Wenchao Lv; Jingguang Li; FengFu Fu; Yue Lin (Journal of Hazardous Materials, 2026)

Impact origin of pink spinel in the Chang’e-6 lunar soils - Linxi Li; Guangyuan Yu; Sen Hu; Hejiu Hui; Yi Chen; Qiu-Li Li; Wei Yang; Lihui Jia; Di Zhang; Shitou Wu; Guoqiang Tang; Hao Wang; et al. (Geochimica et Cosmochimica Acta, 2026)

Ultra-high pressure-assisted enzymatic extraction enhances phenolic release and functional potency in fermented dark tea extracts - Xiaoying Lin; Jun Li; Yuanshan Yu; Dengwen Lei; Tenggen Hu; Manqin Fu; Qiang Xiao; Junying Zou; Ya Gao; Chao Huang; Jing Wen (Food Research International, 2026)

Prenatal exposure to residential greenness and artificial light at night and neurodevelopmental outcomes in children aged 4–12 years: A retrospective cohort study in China - Jian Chen; Daosen Wang; Jiaxuan Fu; Ranran Gong; Qifei Chen; Jie Tang; Ziyu Feng; Han Li; Xinyun Lin; Xiuhong Li (Environmental Research, 2026)

A spider-silk-inspired suture with heterogeneous core-shell structure for integrated wound strain monitoring and on-demand antibacterial therapies - Junxuan Li; Xiaohe Wang; Jingjing Wang; Yue Sun; Yanmin Zhou; Biao Dong; Lin Wang; Li Fu; Lin Xu (Chemical Engineering Journal, 2026)

Highly charged nanocellulose enables triple-function hydrogels for bionic electronic skins - Danning Fu; Jiawen Wu; Huiming Xiao; Yonghao Ni; Zhixin Jia; Wanqing Wang; Lin Li (Chemical Engineering Journal, 2026)

Nanozyme-enabled antibacterial sponge hydrogel-based electronic skin for underwater tactile sensing and slip-direction recognition - Jinli Fu; Lingling Zhang; Jiahao Yuan; Zhenyu Li; Chang Yang; Chunhua Luo; Hechun Lin; Xiaodong Tang; Hui Peng (Chemical Engineering Journal, 2026)

Autophagy-augmenting peptide nanoplatform for synergistic chemo-immunotherapy against breast cancer - Chen Wei; Wei Gao; Xingyue Li; Ming Fu; Fantao Lin; Xiaoyu Zhao; Huiying Jia; Kang Zhang; Changgang Sun; Rui Wang; Jingkun Bai (Chemical Engineering Journal, 2026)

Thrombin-triggered in situ anchoring of a biomimetic bilayer scaffold synergizes with PRP to promote osteochondral regeneration - Zijian Yan; Yongan Lin; Jiayi Chen; Ruibin Lin; Zhuhao Tan; Yunqi Fu; Feifan Luan; Chenxiao Zheng; Li Ren (Chemical Engineering Journal, 2026)

Magneto-photothermal elastomer microactuators for point-of-care Salmonella detection - Kaiyuan Jia; Xunyang He; Jianhan Lin; Zeyu Wen; Fengzhen Yang; Jing Yuan; Qijie Lin; Meixuan Li; Taige Fu; Jianmin Zhang; Yuhe Wang; Lei Wang (Chemical Engineering Journal, 2026)

Ultrahigh-resolution flexible quantum-dot light-emitting diodes via dual assembly and transfer printing - Xin Hu; Yangbin Zhu; Runzhen Sun; Zhen Wang; Jiayu Sun; Qinghong Lin; Yi Jiang; Hongyang Fu; Kejia You; Xuan Guo; Yue Wang; Deli Li; et al. (Chemical Engineering Journal, 2026)

From Geoheritage to Rural Revitalization: A Case Study of the Ru’an Geo-Cultural Village in Hainan Province, China - Jianweng Gao; Zhenliang Wang; Jingjing Gong; Jianzhou Yang; Yan’gang Fu; Lujun Lin; Zhuang Duan; Keqiang Zhao; Yong Li (Geoheritage, 2026)

Acupoint hot compress for labor-pain management: a randomized, parallel-group, controlled trial - Fangfang Wang; Leyi Fu; Xinyue Li; Yuqun Pu; Lianqing Gong; Lin Zhou; Lanxiang Fu; Yaping Chen; Mali Chen; Yue Qin; Xiaoying Lyu; Ye Zhang; et al. (Journal of Zhejiang University-SCIENCE B, 2026)

Nanomaterials as plant delivery carriers: transport mechanisms and design principles - Ye Li; Yezhuo Zhang; Zhun Zhang; Xi Zhang; Hongyang Wu; Man Zhang; Zhuo Li; Yinglang Wan; Yujie Fu; Wei Dong; Ruili Li; Jinxing Lin (Science China Life Sciences, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Dimeric 2-(2-phenethyl)chromones from agarwood of Aquilaria malaccensis - Wei Li; Xian-Yun Yan; Hao Wang; Li Yang; Sheng-Zhuo Huang; Jun Zeng; Fei Wu; Guang-Ying Chen; Wen-Li Mei; Lin-Fu Liang; Hao-Fu Dai; Yong-Min Zhang (Phytochemistry, 2026)

Joule-thermal desert-beetle-inspired mesh for efficient purification of viscous emulsified kitchen oil - Jiawei Sun; Runtang Cai; Xiangyu Huang; Jialuo Dai; Huan Fu; Xinjuan Zeng; Limiao Lin; Penghui Li; Min Zhang (Journal of Water Process Engineering, 2026)

Microbial insights into a high water-quality dependent freshwater snail: Geographical origin and rearing mode shape the gut antibiotic resistance gene profile of Sulcospira hainanensis - Lingtong Ye; Chen Chen; Shengli Fu; Jie Lu; Tuo Yao; Huajian Lin; Zhifu Liang; Huan Li; Jinxia Peng; Zhenhua Ma (Environmental Pollution, 2026)

Phosphorus–boron synergistic carbonization/dormancy strategy enables polyurethane foams with aging enhanced fire safety - Shuang Li; Hai-Bo Zhao; Ming-Jun Chen; Lei He; Lin Zhang; Fu-Rong Zeng; Yu-Zhong Wang (Chemical Engineering Journal, 2026)

Co-pyrolyzed biochar enhances soil fertility and crop quality by modulating rhizosphere microbial functional modules - Zhouyang Lin; Jiaqi Li; Yaquan Zhang; Yi Lu; Qingyun Chen; Shengdao Shan; Haifeng Zhuang; Jianzhou Fu (Journal of Soils and Sediments, 2026)

Population Decline, Inbreeding and Hybridization Shape the Genetic Vulnerability of a Critically Endangered Seabird - Guoling Chen; Chenqing Zheng; Lanhui Peng; Hongzhou Lin; Feng Dong; Shou‐Hsien Li; Yiwei Lu; Siyu Wang; Zhongyong Fan; Yinan Fu; Peng Ding; Jian Zhang; et al. (Molecular Ecology, 2026)
Many endangered species have been rescued from the brink of extinction, yet their long‐term viability remains uncertain due to the prolonged genetic consequences of severe bottlenecks. In particular, the combined effects of inbreeding and hybridization with closely related species remain poorly understood. Using a comparative conservation genomic framework, we investigated these issues in the Chinese crested tern ( Thalasseus bernsteini ), a critically endangered seabird once presumed extinct but which has increased to approximately 100 individuals over the past two decades and its close relative, the great crested tern ( T. bergii ). We demonstrate that the Chinese crested tern has experienced ongoing genetic erosion. Its prolonged population decline has intensified genetic drift and reduced the efficiency of purifying selection, resulting in genome‐wide accumulation of highly deleterious mutations. Highly inbred individuals also carry significantly more homozygous deleterious mutations than less inbred individuals. In both species, runs of homozygosity (ROH) show a relative enrichment of moderately and weakly deleterious mutations. Even more concerning, we found an enrichment of moderately and weakly deleterious mutations in putatively introgressed regions in both species, suggesting that occasional hybridization may have facilitated the spread of deleterious variants and could potentially compromise long‐term fitness. These findings highlight that severe bottlenecks have lasting genomic consequences and that both inbreeding and hybridization can increase the genetic vulnerability of small populations—underscoring the importance of management strategies that promote population growth and sustained genetic monitoring.

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

Management regimes underpin soil carbon accrual following forest conversion to tea plantations across China - Lin Chen; Li Ruan; Yu Duan; Biao Feng; Yixuan Bai; Scott X. Chang; Teng Yang; Yowhan Son; Yuwei Yuan; Shangwen Fu; Chuan Yue; Zhongyi Li; et al. (Science Bulletin, 2026)

Ethylene signaling, pathogenesis-related proteins (PRs) and SlCBF1 collectively regulate Botrytis cinerea resistance in postharvest tomato fruit under low temperature conditions - Pan Shu; Zhiyuan Wang; Bingqing Qian; Zhiyin Yu; Qinlu Zheng; Xin Yao; Hongye Fu; Yuan Qing; Xiaojuan Yin; Pan Zou; Jing Li; Lin Shen (Postharvest Biology and Technology, 2026)

Microbially induced mineralization for mine tailings treatment: Progress, challenges, and future prospects - Zhimin Li; Xiaoqing Yuan; Huicheng Fu; Sen Lin; Xin Xu (Journal of Environmental Management, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

An integrated γ-aminobutyric acid–phytic acid strategy mitigates oxidative stress and quality deterioration in spinach during ambient-temperature storage - Shiai Zeng; Lan Gao; Kai Wang; Xuwei Liu; Peihong Fu; Lin Li; Lei Zhao (Food Bioscience, 2026)

Global lactylation is downregulated despite lactate accumulation: lactylome data and functional insights during ISKNV infection - Zhourui Sun; Yinjie Niu; Xiaozhe Fu; Qiang Lin; Xianglin Cao; Hongru Liang; Xia Luo; Baofu Ma; Wenwen Xiao; Ningqiu Li; Jianjun Chen (Fish & Shellfish Immunology, 2026)

Daily mortality prediction under compound environmental stressors: Comparing epidemiological time series models and machine learning models - Wanjie Wang; Xiaoyan Zhou; Na Li; Feng Chen; Jingqiao Fu; Zhiyang Su; Yuqing Yao; Xiaoyan Yuan; Sirui Lin; Mengfan Chen; Maji Gan; Jieming Zhong; et al. (Environmental Research, 2026)

Molecular attribute-driven hybrid SEI engineering for durable silicon anodes - Yijie Lin; Yingkang Deng; Yuling Fu; Mingjun Ma; Haolei Chen; Xinqi Chen; Shuhan Chen; Jiarong He; Lidan Xing; Weishan Li (Chemical Engineering Journal, 2026)

Experimental Investigation into the Influence of Water Saturation on the Tensile Failure Behavior of Diaspore-Type Bauxite: Implications for Underground Mining of Bauxite - Defu Zhu; Wenshuo Hu; Yalin Li; Qingsheng Bai; Yongjie Jia; TengFei Fu; Gan Feng; Yujiang Zhang; Xiaosong Sun; Yongqing Lin; Dingwei Sun (Rock Mechanics and Rock Engineering, 2026)

Context-dependent links between microbial co-occurrence topology and nitrogen mineralization in two adjacent subalpine Picea asperata stands - Lixia Wang; Haoying Gao; Shuangjia Fu; Lin Xu; Li Zhang; Han Li; Chengming You; Sining Liu; Hongwei Xu; Jiao Li; Bo Tan; Zhenfeng Xu (Plant and Soil, 2026)

Effects of PE microplastics on root morphology and soil nutrients with mechanisms of rhizosphere enrichment in Brassica rapa var. chinensis - Yifei Lin; Chenrui Zhao; Chengliang Li; Lei Hou; Na Liu; Yicheng Fu; Qian Zhang (Journal of Soils and Sediments, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

Promoting green mobility for urban park visits through explainable machine learning and policy simulation - Yinghui Huang; Saixin Cao; Lingli Peng; Yilin Chen; Bowen Zeng; Dongpu Lin; Erkang Fu; Xi Li (Sustainable Cities and Society, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Microwave-induced phase transformation and ultrasound-driven interface reaction for Cu/Te separation - Renkun Luo; Zhonghua Li; Zhuoyu Yin; Shixing Wang; Hongliang Liu; Jiangcheng Wang; Pengcheng Zhang; Yonggang Zuo; Gengwei Zhang; Guo Lin; Libo Zhang; Likang Fu (Journal of Environmental Chemical Engineering, 2026)

Clay minerals reduced antibiotic resistance gene dissemination in the plant rhizosphere through inhibiting horizontal gene transfer and reshaping microbial community structure - Yuxin Qin; Yuqiu Luo; Haihui Fu; Haopeng Pang; Xiaoyu Long; Qian Zhang; Hai Lin; Bing Li (Journal of Environmental Chemical Engineering, 2026)

Functional characterization of chemosensory proteins in Pharsalia antennata with special emphasis on the roles of CSP2 orthologs in pheromone detection - Fu-Peng Li; Xiao-Rong Xiong; Zi-Hui Liu; Zi-Hao Long; Lin-Mei Pu; Nai-Yong Liu (Insect Biochemistry and Molecular Biology, 2026)

Catalytic co-pyrolysis of sewage sludge and corn stover over self-sourced activated biochar: Product distribution, nitrogen migration, and heavy metal immobilization - Xiaojie Zhuansun; Binbin Tang; Zhen Sun; Hongtao Li; Peng Fu; Xiaona Lin (Fuel, 2026)

Multifunctional Cu2O@Ag probe for ultra-sensitive SERS detection and inhibition of Escherichia coli O157: H7 - Hao Jiang; Yu-Qing Wang; Huan Cheng; Shi-Ying Fu; Hongmei Li; Jia-Sheng Lin; Yue-Jiao Zhang; Jian-Feng Li (Food Chemistry, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Amorphous/crystalline heterophase induced S2− migration and oxidation for enhanced oxygen evolution reaction - Yue Huang; Jiejie Li; Yu Liu; Ying-Jie Ma; Lin Zhu; Fu-Rui Teng; Ziqi Tian; Ai-Dong Li (Chemical Engineering Journal, 2026)

Mutual activation of g-C3N4 and persulfate synchronizes rapid visible-light-triggered fabrication of multifunctional hydrogels - Mingming Deng; Dagang Zhou; Lin Luo; Boyi Fu; Ping Li; Qi Liu; Chi Huang (Chemical Engineering Journal, 2026)

Strong and liquid-free ion-conductive elastomer reinforced by chemically cross-linked cellulose network for strain sensors and triboelectric nanogenerators - Meilin Zhang; Zhongshen Cai; Yufan Lan; Zongming Lv; Rui Qian; Zhongsheng Shi; Lihua Fu; Baofeng Lin; Chuanhui Xu; Qunyang Li; Bai Huang (Chemical Engineering Journal, 2026)

The synergy of active and passive satellite sensors for robust sea-fog detection: A two-stage machine-learning model with constraints from ICOADS - Luyu Yan; Xuehua Fan; Disong Fu; Hongrong Shi; Lin Chen; Bo Li; Zhuhui Jiang; Xiaoqiong Zhen; Xiaoguang Sun; Xiangao Xia (Atmospheric Research, 2026)

Ejecta from Chaffee S Crater in Chang’E-6 Landing Site Constrained by Seifertite-Bearing Norite - Zhan Zhou; Sen Hu; Yubing Gao; Linxi Li; Huicun He; Liang Gao; Mengfan Qiu; Lixin Gu; Xu Tang; Xiaoguang Li; Wei Yang; Yangting Lin; et al. (Journal of Earth Science, 2026)

Contrasting responses of bacterial-mediated soil organic phosphorus transformations to varying rates of nitrogen addition in a Cunninghamia lanceolata plantation - Xiang Zhang; Qiong Zhao; Li-Man Wei; Lin-Hui Wu; Xiang-Min Fang; Yong-Hong Ma; Fu-Sheng Chen (Applied Soil Ecology, 2026)

Structurally diverse monoterpenoid indole alkaloids from Damnacanthus hainanensis as well as their potential anti-inflammatory and anti-HIV effects - Gui-Qiong Wu; Long-Cheng Cui; Ye-Ping Liu; Chen-Xu Yue; Lin-Xuan Li; Tian-Yu Wang; Yu-Shan Wang; Shu-Ri Li; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2026)

Toxicological effects of polypropylene nanoparticles similar in size to nanoplastics in plastic-bottled injections on mice and zebrafish - Hui-Min Sun; Jie Wang; Xian-Fu Wu; Zhong-Lan Chen; Hui-Ying Yang; Zhi Lin; Shuang-Xing Li; Zhe Qu; Hua Chen; Shang-Chen Yao (Science of The Total Environment, 2026)

Identification of novel genes involved in pediatric congenital heart disease using trio-based whole genome sequencing - Bo Wang; Mo Li; Wei Zhou; Huiwen Chen; Ying Xiang; Guocheng Shi; Guoling You; Luan Chen; Yesheng Zhang; Xiaoqing Zhang; Yunqian Gao; Lulu Li; et al. (Science Bulletin, 2026)

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

Ensemble learning: a study on the border inspection prediction model for high-risk products adulterated with Sudan Red in Taiwan - Li-Ya Wu; Wei-Chih Cheng; King-Fu Lin; Jia-Jhen Lee; Wen-Chou Lin; Hsu-Yang Lin; Chia-Yen Lu; Chih-Kang Chiang (Food Control, 2026)

Leaf functional traits and wood density of evergreen and deciduous tree species in a tropical karst forest - Yu-Meng Gao; Shi-Jian Yang; Jiao-Lin Zhang; Yan-Juan Jiang; Shu-Bin Zhang; Amy Ny Aina Aritsara; Guo-Hao Hu; Pei-Li Fu; Ze-Xin Fan; Kun-Fang Cao (Flora, 2026)

Iron and calcium interaction for soil As remediation in As waste mine site: Risk assessment and In-situ stabilization - Yuliang Zhang; Sheng Li; Pingfeng Fu; Fangxiang Tu; Tao Zhang; Huiqun Yu; Huifen Yang; Tianli Xue; Xi Qin; Chonggao Wei; Lin Liang (Environmental Pollution, 2026)

Bridging accelerated cell-level degradation to module-relevant failure mechanisms in TOPCon solar cells and modules - Xinyuan Wu; Wei Wu; Weiguang Yang; Yan Zhang; Jiexi Fu; Xutao Wang; Jing Yuan; Jianjun Nie; Zhencong Qiao; Chao An; Feng Li; Lin Lv; et al. (Chemical Engineering Journal, 2026)

Hydroxylamine enhances the iron double-cycle system to improve the removal efficiency of norfloxacin via Fe3O4@N-rGO/PMS system - Lingzi Fu; Chao Wang; Aiguo Lin; Zhangbin Pan; Bin Wang; Li'’an Hou (Chemical Engineering Journal, 2026)

A high-performance bimodal sub-nanoporous polyelectrolyte complex membrane for organic solvent nanofiltration constructed by MOF-reinforced nano-unit - Hui-Qian Huo; Bing-Xin Gu; Jin-Lin Wang; Jia-Chen Zhang; Kai Zhang; Ming-Jie Yin; Yan-Li Ji; Quan-Fu An (Chemical Engineering Journal, 2026)

Gene-Environment Interaction of Rims1 and Adolescent Social Isolation on Schizophrenia-Like Behaviors in Mice - Lian-Hong Lin; Wei-Min Li; Qian-Yun Wu; Shuang-Yan Li; Xu-Xuan Ma; Yuan Xu; Si-Fu Deng; Bin Zhang; Ji-Hong Liu (Neuroscience Bulletin, 2026)

RCTUnet: a deep learning model for crop-residue-soil image segmentation and crop residue cover extraction - Ting Li; Yang Liu; Haikuan Feng; Meiyan Shu; Hao Yang; Yuanyuan Fu; Xin Xu; Yinghao Lin; Hongbo Qiao; Wei Guo; Xinming Ma; Lei Shi; et al. (Journal of Zhejiang University-SCIENCE B, 2026)

Preparation of cancer cell membrane-coated Gambogic acid-loaded pH-sensitive liposomes to enhance targeted anti-hepatocellular carcinoma effect - Yi-Feng Zhang; Kun Chen; Yu-Qing Zhu; Lin Liu; Xiang-Tao Kong; Yan Dai; Xiu-Juan Fu; Ya-Ling Li; Ming-Hua Liu; Dan Zhang (Drug Delivery and Translational Research, 2026)

A review for bioactive peptides from oyster: functional properties, structure-function relationships and challenges - Zihan Zheng; Jiongqi Lin; Dongmei Li; Zhanming Li; Caili Fu; Zhongyang Ren (Trends in Food Science & Technology, 2026)

Eocene topography differentiation between the western and eastern North China Craton: Insights from multi-method chronometry in the northern Taihangshan Mountains - Li-Xia Feng; Ping-Ping Li; Zeng-Zhen Wang; Rong Ren; Lin Wu; Bo Zheng; Bo Liu; Jian-Qing Ji; Bao-Fu Han (Tectonophysics, 2026)

Integrated metabolomic and transcriptomic analyses unravel the function of quercetin in enhancing grape resistance to anthracnose - Meng-Fei Li; Ming-Yi Wang; Fu-Lai Han; Zhe Zhang; Ya-Lin Liu; Meng-Ran Li; Yu-Fei Li; Jie Yang; Xin Liu; Guang-Chao Liu (Postharvest Biology and Technology, 2026)

Excitation mechanisms and vibration response of a horizontal elbow in gas-liquid two-phase flow - Yitong Fu; Xiang Li; Bolun Ding; Yiran Duan; Lin Ding (Ocean Engineering, 2026)

Opisoma menchikoffi Dubar, 1948: New occurrences from the Lower Jurassic of the High Atlas, Morocco and Tethyan Himalaya, southern Xizang (Tibet), China - Fu-Lin Li; Kai Ye; Xin Rao; Zhong Han; Cheng-Gang Wang; Xiong-Wei Zeng; Long Wang; Hao Liu; Zong-Xin Wang; Fa-Fu Wu; Kun Liang; Wen-Kun Qie (Palaeoworld, 2026)

Geochemistry of tourmaline in granitic rocks from the Zharigana and Caolong areas, Northern Tibet: Implications for the identification of lithium-mineralizing plutons - Ling Ma; Jin-Sheng Zhou; Qiang Wang; Lin Ma; Jin-Heng Liu; Wu-Fu Li; Bing-Zhang Wang; Chun-Tao Wang; Jian-Dong Liu; Xin-Yuan Zhang; Mao-Rui Liu; Zhi-Wei Yu; et al. (Lithos, 2026)

Synergistic enhancement of electrochemical performances via PDA/Fe3O4 modified anodes and amino acid-mediated bioelectrocatalysis of biomineralization in marine sediment microbial fuel cells - Lin-Meng Wang; Li-Ze Huangfu; Yi Yang; Yan Chen; Yu-Bin Fu (Journal of Environmental Chemical Engineering, 2026)

High spatiotemporal resolution acoustic tomography based on virtual microphone array and hybrid deep learning - Qi Liu; Minglu Dai; Tao Zhang; Bin Shi; Hui Zhang; Tianren Fu; Lin Li; Lunbo Duan (Fuel, 2026)

Interfacial structure and adsorption at hydrogen–brine interfaces regulated by cushion gases (N2, CO2): A molecular dynamics simulation - Pengyu Chen; Riyi Lin; Shengxiang Ma; Huanan Li; Yujie Fu; Qiwei Donga; Ruiqi Liu; Zhizhuang Wang; Chengxing Huang; Yan Qiao (Fuel, 2026)

Structural vibration analysis and safety assessment of centrifuges under hypergravity environments - Chengpeng Hong; Guanwen Liang; Li Bi; Haoran Fu; Zizhuang Yan; Kuigen Lin; Yunmin Chen (Engineering Structures, 2026)

Effect of perovskite A-site disorder on its activity in solid-state CO2 electrolysis - Shuo Liu; Lin-Bo Liu; Biao Ouyang; Yan Li; Qinglin Pan; Yifei Sun; Xian-Zhu Fu; Jing-Li Luo; Subiao Liu (Chemical Engineering Journal, 2026)

Design and synthesis of novel fucosylated chondroitin sulfate derivatives as intrinsic FXase inhibitors and evaluation of their antithrombotic activities - Dongliang Xu; Xi Gong; Lisha Lin; Hang Dong; Yijian Wen; Yingnian Li; Gang Fu; Yuanhang Ma; Weicheng Xiong; Tianyu Guan; Ao Sun; Xiangbao Meng; et al. (Carbohydrate Polymers, 2026)

Effects of Lactobacillus Acidophilus Mediated Improvement of Intestinal Barrier in Mice with Autism - Yong Song; Jia Shi; XiaoYi Fu; Dan Fu; Li Xu; WeiMei Liu; JingJing Cao; YaoCheng Ding; ShuPeng Huang; Lin Zhou; Kai Qian (Probiotics and Antimicrobial Proteins, 2026)

Rapid selection of early-maturing and low-ear position maize hybrids suitable for China using genomic prediction - Ping Luo; Wenzhe Li; Lin Zhang; Jie Yang; Houwen Wang; Fei Wang; Ruisi Yang; Xinlong Xu; Ke Yang; Hongjun Yong; Mingshun Li; Jianfeng Weng; et al. (Plant Molecular Biology, 2026)

From SPP to RTK: promoting the satellite navigation potential of acoustically excited antenna - Shangyang Wang; Yifan Fu; Rui Hu; Du Li; Bing Xu; Ruofan Liu; Yinuo Song; Junru Li; Bin Fang; Wenkui Lin; Zhongming Zeng; Xiangwei Zhu (GPS Solutions, 2026)

Contrasting behaviour in geogenic degassing along an active segment of the East Anatolian fault zone (Türkiye) - G. Yüce; W. D'Alessandro; C.C. Fu; F. Italiano; M. İçhedef; H. Elmacı; B. Kürkcüoğlu; B. Kahraman; A. Demirtaş; L.H. Lin; D. Yasin; Ş. Gürboğa; et al. (Applied Geochemistry, 2026)

A national-scale early detection and rapid response (EDRR) to invasive cane toads (Rhinella marina) in Taiwan - Yung-Chih Lai; Chun-Fu Lin; Li-Mien Tseng; Cheng-En Li; Jia-Han Lee; Jou-Yun Chen; Ming-Chih Wang; Chun-Hung Lai; Yueh-Feng Chen; Chun-Lin Ho; Wei-Chun Cheng; Yi-Ju Yang (Biological Invasions, 2026)

Global Patterns and Drivers of Recent Decoupling Between Extratropical Spring Phenology and Temperature - Ziyu Lu; Ming Shao; Jiayan Li; Jingyuan Lin; Peiyuan Tao; Mengyu Li; Siqi Zhang; Peng Yao; Yang Fu (Global Change Biology, 2026)
While spring phenology has been widely studied, the magnitude and drivers of its decoupling from thermal cues across extratropical biomes remain poorly understood. Using satellite data from 1982 to 2021, we show that the onset of vegetation green‐up (GSOS) generally lags the onset of the thermal growing season (TSOS). This mismatch (ΔSOS) has increased by 1.51 days per decade ( p 15 days), warming‐driven advances in TSOS are increasingly decoupled from GSOS, as declining precipitation and enhanced evaporative demand intensify moisture limitation and delay green‐up; in temperate forests (both coniferous and broadleaf), warming together with enhanced shortwave radiation promotes faster GSOS advancement relative to TSOS, thereby dampening the mismatch. These contrasting pathways reveal an accelerating yet heterogeneous phenology–temperature decoupling, with far‐reaching consequences for ecosystem synchrony, seasonal carbon uptake, and land–climate feedbacks. Our results underscore the need to incorporate non‐thermal drivers and biome‐specific controls into phenological and Earth system models to better constrain future climate–biosphere interactions.

How does recreation involvement in urban parks promote restorative effects? - Erkang Fu; Lin Li; Jiawen Zhou; Li Deng; Mingxuan Pu; Peilin Qu; Yijun Xu; Xi Li (Urban Forestry & Urban Greening, 2026)

A dynamic Bayesian network-based probabilistic analysis method for urban gas pipelines from the perspective of “Accident-Barrier-Resilience” - Fu-qiang Yang; Hai-feng Liu; Shi-yi Li; Xing-lin Chen; Zong-hou Huang (Process Safety and Environmental Protection, 2026)

Fine mapping and preliminary mechanism analysis of tobacco Fusarium root rot resistance genes - Yang Shen; Junqi Cheng; Chao Fu; Chenglin Wu; Yapei Li; Zhongxu Lin; Jinglin Cao (Physiological and Molecular Plant Pathology, 2026)

Body size- and water homeostasis-dependent temperature stress tolerance and transcriptional changes in red fire ant workers - Wei Gao; Rui Peng; Jian-min Yang; Jian-lin Lu; Hong-yun Cao; Ying-huan Li; Chun Li; Wen Fu; Jin Xu (Journal of Asia-Pacific Entomology, 2026)

Space weathering on the lunar nearside and farside revealed by iron and potassium isotopes - Heng-Ci Tian; Wei Yang; Xinmiao Zhao; Jun Du; Liyu Shan; Wen-Jun Li; Jing Wang; Xuhang Zhang; Yangting Lin; Xian-Hua Li; Fu-Yuan Wu (Geochimica et Cosmochimica Acta, 2026)

Preferential N2-transport thin-film composite membrane for energy-efficient CO2 capture - Jin-Lin Wang; Cheng-Gang Jin; Hui-Qian Huo; Bing-Xin Gu; Yue Li; Wen-Hai Zhang; Ming-Jie Yin; Quan-Fu An (Chemical Engineering Journal, 2026)

Multi-model machine learning framework for prediction of greenhouse gas emissions during composting of organic solid waste - Jing He; Jing Tang; Zhonghao He; Qiqi Fu; Yi Li; Ci Song; Wei Huang; Jiajia Wang; Jiangfang Yu; Lin Tang (Bioresource Technology, 2026)

Strategy for doubling the yield of phenolics in hydrothermal liquefaction of Arundo donax: mechanistic study on weak alkaline catalyst suppressing hydrochar formation and enriching phenolics in aqueous and biocrude phases - Lei-ming Bi; De-lin Fu; Xian-shuai Fu; Li-hui Zhang; Feng Duan (Biomass and Bioenergy, 2026)

Dietary 4-hydroxy-2,5-dimethyl-3(2 H)-furanone supplementation enhances serum antioxidant capacity and nutrient digestibility in Hu sheep by promoting biofilm formation - Qinghua Qiu; Chuanpei Fu; Lin Li; Kehui Ouyang; Mingren Qu (Animal Feed Science and Technology, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Zedoarondiol inhibits monocyte adhesion and expression of VCAM and ICAM in endothelial cells induced by oxidative stress - Bei-li Xie; Yu-long Bie; Bo-ce Song; Ming-wang Liu; Lin Yang; Jiangang Liu; Da-Zhuo Shi; Fu-Hai Zhao (Natural Product Research, 2026)

Arsenic species in crayfish from the Yangtze River basin, China: Levels composition and health risk assessment - Xinjie Li; Bo Fu; Kai Lin; Jiayin Huang; Sisi Yu; Wenchao Zhu; Yuli Lin; Chiqun Shan; Mingqin Zhong; Shaoyou Lu (Aquaculture, 2026)

Integrated indicator assessment of coastal sustainable development capacity: Informing policy and prioritizing management actions in developing countries - Yiqiu Fu; Zengkai Zhang; Chao Liu; Zheng Li; Yixuan Chen; Xiaoxiang Liu; Jiaju Lin; Caiyun Zhang; Tao Lin; Jinliang Huang; Xiongzhi Xue (Ocean & Coastal Management, 2026)

Enhancing urban bird corridor identification by integrating three-dimensional factors: A validation with citizen science data - Yaling Huang; Ziru Chen; Yankai Huang; Tongyan Li; Chengyu Ran; Ying Lin; Yinghong Ding; Deng Pan; Yuxiang Lan; Jiali Jin; Zhipeng Zhu; Weicong Fu (Urban Forestry & Urban Greening, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Anthropogenic disturbances drive stepwise geomorphic changes of shoal-channel systems in a tide-dominated estuary - Ping Zhang; Linxi Fu; Xiangyuan Li; Jianliang Lin; Huayang Cai; Zhijun Dai; Qingshu Yang (Marine Geology, 2026)

Microplastics found in Weddell seal placenta in Antarctica, potential threatening marine ecosystem health - Xing Miao; Conghui Peng; Renxin Zhang; Baohong Chen; Zongzheng Chen; Hui Lin; Tingting Fu; Yuan Li; Longshan Lin (Journal of Hazardous Materials, 2026)

An enhanced sorting method for second-life lithium-ion batteries based on two-step clustering - Fu Wan; Yupeng Lin; Da Yang; Shufan Li; Ruiqi Liu; Lei Zhu; Wenwei Yin; Weigen Chen (Journal of Cleaner Production, 2026)

Mercury isotope perspectives on vegetation-enhanced nickel mobilization and migration during laterite formation - Ruo-Lin Liu; Martin Yan Hei Li; Run-Sheng Yin; Mei-Fu Zhou; Jun-Hong Zhao (Geochimica et Cosmochimica Acta, 2026)

Wave flow field design optimization for enhanced performance of high-temperature PEM fuel cells - Mingwei Li; Lirong Fu; Huadong Lin; Jinyi Liu; Xiaosong Zhang (Fuel, 2026)

Scalable production of antioxidant ‘sandwich’ films from all-natural composites for inhibiting fruit browning - Jie Deng; Hao Fu; Xinhong Li; Jieping Liu; Yuancheng Zhang; Wenxin Zhao; Baofeng Lin (Food Chemistry, 2026)

Development and application of fluorescent immunoassay lateral flow Technology for the Detection of Prolamins in food - Xinyi Zhao; Qi Fu; Wenye Zhu; Hong Lin; Zhiyu Liu; Hao Wang; Phon Reno; Ziye Zhang; Yuhao Huang; Zhenxing Li (Food Chemistry, 2026)

Energy-saving and fire/water-resistant recyclable aerogel coatings for thermal-insulating polyurethane foam - Cong-Mei Lin; Xue-Lian Chen; Fu-Rong Zeng; Li-Xiao Hao; Yu-Shi Wen; Bing-Ru Zhang; Bo-Wen Liu; Lin Zhang; Hai-Bo Zhao (Chemical Engineering Journal, 2026)

Water vapor-mediated cellulose skeleton enhances liquid-free ion-conductive elastomers for flexible electronics - Zongming Lv; Hongping Li; Meilin Zhang; Yuanyuan Lao; Lihua Fu; Baofeng Lin; Chuanhui Xu; Bai Huang (Chemical Engineering Journal, 2026)

Defect passivation with Pb for high-performance Sb2S3 solar cells via vapor transport deposition - Gan Huang; Xin-Yi Cai; Hu Li; Jin-Rui Cai; Ying-Sen Xia; Zhi-Ping Huang; Li-Mei Lin; Fu-Bao Gong; Shui-Yuan Chen; Gui-Lin Chen (Chemical Engineering Journal, 2026)

Manganese cycle-mediated synchronous bacteria-algae/anammox coupled denitrification system under low-temperature conditions: Performance and mechanisms - Peng-fei Yu; Dian-lin Jiang; Ding Wang; Xing-guan Ma; Jun-Li; Li-yao Han; Ao Wang; Yu-bo Fu; Xing Jin (Bioresource Technology, 2026)

An effective gauge-satellite fusion approach for daily precipitation bias correction based on multi-dimensional precipitation feature space (BCFS) - Gaoyun Shen; Li Zeng; Lin Fu; Lei Wang; Junann Xiong; Wei Wang (Atmospheric Research, 2026)

FGF2 Enhances MSCs Secretome Therapy for Skin Photoaging by Delaying Senescence via iNAMPT/AMPK Signaling and Facilitating eNAMPT-Mediated Regenerative Crosstalk - Yixin Zhang; Manping Lu; Jieqing Ouyang; Lin Liang; Fan Li; Zhihan Pei; Lihao Chen; Miaoman Ye; Jiajie Tan; Liwei Xiang; Lijing Kong; Long Huang; et al. (Stem Cell Reviews and Reports, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

A synthetic biocontrol consortium of Streptomyces salinarius and Bacillus halotolerans exhibits superior protection against Fusarium oxysporum infection in Pinus via synergistic interactions - Haixia Wang; Lin Fu; Chunli Li; Xuanyi Meng; Siyang Wang; Xinlu Zhang; Xinyu Zhou; Xiangna Wang; Fangliang Zheng; Chunyu Zhu (Plant and Soil, 2026)

Caffeoylquinic acid derivatives (CQAs) from Daphne gemmata and their antimicrobial activities - Lin Li; Fu-Qiang Song; Ping-Jing Yu; Li-Ping Tang; Xian Li (Natural Product Research, 2026)

Enhancing oil-water separation via droplet coalescence regulated by particle self-rotation in swirling fields - Wei Zhao; Ao-song Wei; Shu Zhu; Tong Zhang; Peng-bo Fu; Jian-ping Li; Xue-jing Yang; Hua-lin Wang (Water Research, 2026)

Dual-anode electrochemical strategy enables simultaneous carbon and nitrogen removal from biologically treated landfill leachate - Zichao Lin; Hengyi Fu; Jianyi Zhou; Lele Tu; Qiaoxin Li; Rundong Chen; Li Tian; Wenxiao Zheng; Chaohai Wei; Chunhua Feng (Water Research, 2026)

mTOR mediates airway epithelial E-cadherin disruption in toluene diisocyanate-induced asthma - Lin Fu; Lichang Chen; Xianru Peng; Changyun Yang; Jiamin Sun; Zemin Chen; Sudan Gan; Shiyue Li; Haixiong Tang; Yidan Lin; Lihong Yao (Toxicology and Applied Pharmacology, 2026)

The glutamyl-prolyl-tRNA synthetase 1 inhibitor halofuginone exerts synergistic antitumor effects with bortezomib in colon cancer cells - Han Lin; Ying Yan; Chenyu Qiu; Junqi Wang; Wenying Fu; Chongchong Shu; Yinghua Chen; Chenxin Xu; Shaotang Li; Yiqun Xia; Jundixia Chen; Yunzhi Chen; et al. (Toxicology and Applied Pharmacology, 2026)

Do biodegradable plastic residues pose lower ecological risks to crops than conventional plastic residues? A meta-analytic comparison - Feng Yuan; Teng Wang; Hongyu Chen; Yongcheng Ding; Jianguo Tao; Yue Xue; Linjie Zhang; Haiyan Lin; Baojie Li; Yifei Qiu; Guanghe Fu; Xinqing Zou (Journal of Hazardous Materials, 2026)

Formation mechanism of high arsenic geothermal water in Gonghe basin, Northwest China - Zhen Wang; Yongge Li; Chuanxia Ruan; Fu Wang; Wenjing Lin; Yu Yang; Narsimha Adimalla (Journal of Geochemical Exploration, 2026)

Delivery of carbonaceous materials to the Moon - Linxi Li; Mengfan Qiu; Sen Hu; Hejiu Hui; Yi Chen; Qiu-Li Li; Wei Yang; Yuyang He; Shitou Wu; Hao Wang; Guoqiang Tang; Di Zhang; et al. (Icarus, 2026)

The low R = d/d high-entropy strategy enables high-performance sodium layered oxide cathode materials - Jun-Jie Liao; Min Wen; Wei-Wei Yuan; Qi-Lin Zheng; Kang Chen; Fu-Sheng Zhou; Zhen-Xin Qiu; Su-Yun Wang; Li-Li Wang; Lituo Zheng; Yiyin Huang; Jia-Xin Li; et al. (Chemical Engineering Journal, 2026)

Enhancing pearl luster by targeted delivery of astaxanthin using submicron hollow ordered mesoporous silica to the mantle of pearl oysters - Yuan-shuai Fu; Xi-ke Li; Yue Lin; Yun-ao Li; Yong Zhao; Wei-hao Wu; He Wang; Xue-feng Lv; Yuan Zhang; Yong-heng Zhu; Zhi-yi Bai (Chemical Engineering Journal, 2026)

Promotion of nitric oxide to ammonia via nickel species enhanced active hydrogen generation - Hui Liu; Lin Wu; Yingxue Fu; Zhujiang Wang; Jiaqi Long; Jing Yuan; Xinlei Wang; Jieyu Li; Jun Wu; Kaisong Xiang (Chemical Engineering Journal, 2026)

Development and validation of a multiplex high-risk HPV detection method using lyophilized microsphere technology and multicolor melting curve analysis - Miao Fu; Huabin Wang; Yingchao Wu; Chaoyong He; Wei Chen; Na Zhang; Xin Chen; Jinhua Wang; Xiaohuan Zhao; Meili Lin; SiSi Mao; Xi Xiang; et al. (Chemical Engineering Journal, 2026)

Soil moisture dynamics and rainfall infiltration across vegetation types in subtropical ecosystems in Southwest China - Qiao-Shun Yan; Yu-Xi Peng; Xiao-Jin Jiang; Pei-Li Fu; Zhi-Yun Lu; Xiao-Wen Hu; Yong-Jiang Zhang; Jiao-Lin Zhang; Ze-Xin Fan (CATENA, 2026)

Effect of CPAP treatment on subjective cognitive decline in patients with mild obstructive sleep apnea syndrome - Liang Tan; Xin Zhang; Zhijian Fu; Chunyao Dong; Chang Zhou; Caiyun Hou; Yuanyuan Lin; Xiaolei Wang; Li Li; Jin Zhou (Sleep and Biological Rhythms, 2026)
There is no consensus on whether to use continuous positive airway pressure (CPAP) treatment for mild obstructive sleep apnea syndrome (OSAS). Our study aims to observe the efficacy and necessity of using CPAP treatment in mild OSAS patients complicated with subjective cognitive decline (SCD). From August 2021 to July 2022, patients with mild OSAS and SCD were randomized to the control group or the CPAP group, and followed up for 3 months. The primary results were evaluated using subjective cognitive decline questionnaire (SCD-Q), the Huashan version of the Auditory Verbal Learning Test (AVLT-H), and animal fluency test (AFT), which were tested at admission and three months after treatment, respectively. And plasma Aβ1–40 and Aβ1–42 levels were also measured at admission and 3 months after treatment. A total of 110 patients completed the final study, with 55 in the control group and 55 in the CPAP group. No significant differences in demographic data, Laboratory tests, AHI index, SCD-Q, AVLT-H, and AFT scores between the two groups before treatment. The SCD-Q score of patients in CPAP group significantly decreased after 3 months of treatment and was significantly lower than that of control group ( P <0.05). And the immediate memory score of AVLT-H in the treatment group was significantly increased after 3 months of treatment ( P < 0.05). The Aβ1–42/Aβ1–40 ratio in the treatment group significantly decreased after 3 months of treatment, and was significantly lower than that of control group ( P <0.05). Furthermore, there was linear correlation between SCD-Q score and Aβ1–42/Aβ1–40 ratio in all patients after 3 months of treatment ( P <0.001, r =0.584). Our findings suggested that CPAP treatment can significantly decrease the Aβ1–42/Aβ1–40 ratio, and improve SCD, which may play an important role in the prevention of dementia, but further research are warranted.

How do moss-dominated biocrusts drive carbon sequestration under lithological constraints in karst soils? - Fang Wang; Yuanfeng Yang; Ze Li; Zhe Lin; Zhiyong Fu; Hongsong Chen; Yusong Deng (Plant and Soil, 2026)

Ectomycorrhizal exploration types shape soil enzyme activity, decomposition, and nitrogen dynamics in subalpine forests - Lixia Wang; Haoying Gao; Shuangjia Fu; Huichao Li; Lin Xu; Li Zhang; Han Li; Chengming You; Sining Liu; Hongwei Xu; Jiao Li; Bo Tan; et al. (Plant and Soil, 2026)

Modulating NLRP3 Inflammasome Activity and Enhancing Cortical Synaptic Plasticity: Nanoparticulate Hydrogen’s Role in Relief of Post-traumatic Anxiety-like Behaviors in Rats - Lanxia Wu; Congwen Yang; Yiqin Ding; Xinru Liu; Hao Sun; Xue Li; Yining Lu; Lifen Liu; Qingyang Fu; Min Li; Yingshuai Wang; Yuehan Zhao; et al. (Molecular Neurobiology, 2026)

Large-scale analysis of SARS-CoV-2 genomic data from sewage using eVarEPS reveals that amino acid mutations detected in sewage provide an early warning on population prevalence - Ziquan Lv; Chang Shu; Yulin Fu; Yinghui Li; Shisong Fang; Xiangjie Yao; Qinglan Sun; Kesheng Peng; Jian Lu; Guomei Fan; Dongmei Liu; Jinzhen Tang; et al. (Water Research, 2025)

Corrigendum to “Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk” [Toxicology and Applied Pharmacology Volume 503, October 2025, 117465]. - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

10-Hydroxy-2-decenoic acid ameliorates LPS-induced acute lung injury through targeting MD2-mediated inflammatory signaling pathways - Cong Shu; Chen Li; Huamin Liu; Zengxian Zhou; Chenghao Qian; Zhuohui Xie; Fenfen Lin; Yuxiao Jiang; Ruping Chen; Yue Liu; Xin Liu; Gaozhi Chen; et al. (Toxicology and Applied Pharmacology, 2025)

Two new 2-(2-phenylethyl)chromone dimers from agarwood of Aquilaria malaccensis - Lin Zhang; Wei Li; Hao Wang; Jun Zeng; Wen-Hua Dong; Bei Jiang; Jing-Zhe Yuan; Fei Wu; Wen-Li Mei; Hao-Fu Dai (Phytochemistry Letters, 2025)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

The attribution of subseasonal extreme precipitation in arid and semi-arid regions based on extended convergent cross mapping - Tingxing Chen; Attilio Castellarin; Yonghua Zhu; Haishen Lü; Andrea Magnini; Yinghao Fu; Yuan Li; Yu Lin; Zhenzhou Ding; Jiaying Liu (Journal of Hydrology, 2025)

Optimal matrix identification of parabens, triclosan and triclocarban for biomonitoring: Comparative analysis in urine, whole blood, serum, and plasma - Weizhong Chen; Yuli Lin; Kai Lin; Xiaoru Wu; Chiqun Shan; Bo Fu; Yiran Chen; Junye Bian; Xinjie Li; Xulong Chen; Tao Chen; Guangyu Sun; et al. (Journal of Hazardous Materials, 2025)

A framework for ecological restoration baseline delineation integrating geology-landscape-ecology and carbon sinks based on geographical similarity - Shu Wang; Quanli Xu; Shengfeng Li; Zhaoxin Fu; Yijing Lin (Journal of Environmental Management, 2025)

Functional characterization of two CCL20 chemokines in black rockfish (Sebastes schlegelii): dual roles in immune cell recruitment and direct antimicrobial defense - Fengjun Lin; Yiying Liu; Chonghui Chen; Xiaoxu Zhang; Pei Zhang; Huijun Huo; Chao Li; Qiang Fu (Fish & Shellfish Immunology, 2025)

Self-powered water quality optical inspection as mechanically triggered by time-controlled instantaneous discharging - Zixian Lai; Minyan Zhang; Guoliang Fu; Jiale Chen; Zhijian Li; Jiaqi Wang; Zhong Lin Wang (Chemical Engineering Journal, 2025)

Homogeneous MgF2-engineered Na surface architecture enabling uniform ion deposition in ultra-stable sodium metal batteries - Xueming Su; Junjie Fu; Lin Luo; Xiaoquan Yang; Yue Li; Weijiang Hu; Qing Li; Qingye Li; Chencheng Sun; Jun Yang; Hongwei Gu (Chemical Engineering Journal, 2025)

Evaluation of Feeding Effect of a New Artificial Diet on Chilo sacchariphagus and Chilo infuscatellus (Lepidoptera: Crambidae), Two Major Stalk Borers on Sugarcane in China - Ji-li Wei; Yong-lin Ma; Cheng-hua Huang; Feng-ying Wang; Qiao-xian Wei; Liu-feng Li; Ren-zhao Liao; Fu Lv; Xue-hong Pan; Xian-kun Shang (Sugar Tech, 2025)

Pluvial flood warnings in a tidally influenced basin enhanced by rainfall–tide compound indicators: Taipei case study - Mei-Ying Lin; Wen-Yih Sun; Huei-Syuan Fu; Chih-Hsin Chang; Wei-Bo Chen; Chieh-Ju Wang; Hsuan-Wei Wang; Yi-Chiang Yu; Yen-Wei Li (Stochastic Environmental Research and Risk Assessment, 2025)

The whole genome sequence of Cordyceps cicadae — an edible and potential medicinal fungus - Yuwei Liu; Xueqian Li; Yiqi Meng; Yifan Wu; Yuting Jin; Xiaotong Ma; Wei Zhou; Yuchong Tan; Fu-Cheng Lin; Hongkai Wang (Molecular Genetics and Genomics, 2025)

Methylene blue in electrochemical (Bio)sensing: Historical evolution, mechanistic insights, and emerging applications—A review - Li Fu; Cheng-Te Lin; Karimi-Maleh Hassan (Analytica Chimica Acta, 2025)

Network pharmacology, molecular docking and experimental validation to elucidate the anti-ulcerative colitis mechanism of Rosa roxburghii Tratt. leaves - Ming-Liang Luo; Shuang Zhang; Qing-Yong Wang; Ling-Wei Fu; Li-Juan Xiang; Chang Lin; Xin Yin (Natural Product Research, 2025)

Structural insight into GPR155-mediated cholesterol sensing and signal transduction - Delin Li; Xiaokang Zhang; Jie Feng; Yufeng Xie; Pu Han; Ming He; Lin Hao; Tianling Guo; Xiaoyi Bai; Kai Yuan; Junqing Sun; Xuefei Pang; et al. (Science Bulletin, 2025)

RNA interference targeting cytochrome P450 cyp303a1 on the performance of Henosepilachna vigintioctopunctata - Kai-Yun Fu; Miao He; Lin Jin; Guo-Qing Li (Pesticide Biochemistry and Physiology, 2025)

Functional characterization of odorant binding proteins in Pharsalia antennata provides insights into diverse binding properties and the importance of C-terminal residues - Shu-Lin Li; Fu-Peng Li; Zi-Xuan Yang; Yu-Jie Zhao; Zhao-Qun Li; Nai-Yong Liu (Pesticide Biochemistry and Physiology, 2025)

Formation of reactive oxidants from Fe(II)-bearing minerals in oxic environments: A review - Jieyun Lin; Juan Zhou; Yu Fu; Jiamin Cai; Shi Chen; Tao Wang; Jiang Li; Shaoqi Zhou; Yuanyuan Liu (Journal of Hazardous Materials, 2025)

Identification of rice taste quality markers using metabolomics techniques - Jun Shu; Weidan Guo; Kangzi Ren; Xiangjin Fu; Zhao Long; Qinlu Lin; Chun Liu; Jiangtao Li (Food Chemistry, 2025)

Layer-by-layer assembly mechanism of particulate-continuous phase for sandwich-like nanoparticles in oral colon-targeted protein delivery - Wen-Xuan Hu; Chang-Sen Jin; Si-Lin Li; Jia-Yang Fu; Liang-Sen Liao; Xiuzhu Yu; Shuang-kui Du (Food Chemistry, 2025)

Pretrain-finetune neural operator for multi-fidelity surrogate modeling of structural dynamic systems - Pei-Lin Li; Shi-Fu Liu; Yi-Qing Ni; Jian-Ming Ling; You-Wu Wang (Engineering Structures, 2025)

Dissecting the role of foulant-spacer interaction energy on membrane fouling with a collision-attachment-based Monte Carlo approach - Junxia Liu; Mingxin Peng; Bingzhi Liu; Wei Fu; Chenxi Lin; Zhiwei Tang; Dongsheng Zhao; Weiwei Huang; Tian Li (Desalination, 2025)

Caulerpa lentillifera extract alleviates the chronic diquat-induced liver oxidative damage in zebrafish (Danio rerio) in association with Nrf2 and AMPK/mTOR signaling pathway - Xiang Lin; Xiaocen Xie; Qijun Fu; Zhongqun Liu; Ye Xiao; Yongqiang Wang; Haiping Li; Xi Xie; Rong Wang; Yingxia Zhang; Yanting Song; Wenting Hu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Influence of prolonged exposure to acetamiprid on the toxicology of the decapod crustacean Pacific white shrimp Penaeus vannamei - Zhen-Fei Li; Zhi Luo; Zhi-Yu Lin; Zhen-Qiang Fu; Feng-Lu Han; Er-Chao Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

The proteo- and chitinolytic coordinate mechanisms of Streptomyces sp. SCUT-3 and its application in chitinous wastes recycling - Ming-Shu Zhang; Zhi-Wei Li; Lei Wu; Zi-Yang Luo; Can Qin; Fu-Gen Zhang; Chu-Yan Liang; Hai-Ning Wang; De-Lin Lu; Jun-Jin Deng; Xiao-Chun Luo (Chemical Engineering Journal, 2025)

Breaking the monopoly of the Zn(002): Phosphoryl-heterocyclic co-adsorption to promote preferential exposure of Zn(101) crystal plane for dendrite-free Zn metal anodes - Haoran Lang; Chao Li; Jingxin Zhao; Chunyuan Xiong; Lieyuan Zhang; Yijia Luo; Qiaoji Zheng; Xin Tan; Hong Fu; Bingang Xu; Dunmin Lin (Chemical Engineering Journal, 2025)

Sugar-based block copolymer/carbon nanotube nanocomposites for thermoelectric applications - Yen-Yu Chen; Hong Li; Chih-Jung Lin; Koshin Tanaka; Meng-Hao Lin; Shao-Huan Hong; Min-Chi Fu; Jian-Fa Ding; Yu-Jane Sheng; Redouane Borsali; Tsuyohiko Fujigaya; Cheng-Liang Liu (Chemical Engineering Journal, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

The recovery mechanism of granular sludge fragmentation and re-granulation caused by long-term high-concentration organic matter erosion in the SAD process: performance, sludge evolution, and metagenomic sequencing - Peng-fei Yu; Ding Wang; Yu-bo Fu; Xing-guan Ma; Hao Zheng; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Xing Jin (Bioresource Technology, 2025)

Enhancing flash flood susceptibility modeling using the optimal parameter geographical detector (OPGD) method - Quankun Liu; Lin Fu; Junnan Xiong; Jun Liu; Gaoyun Shen; Zhiwei Yong; Yinxiang Xu; Qian Jia; Qilong Li (Advances in Space Research, 2025)

Cold Pools Detected by a 356-m Meteorological Tower in a Monsoon Coastal Region - Chuying Mai; Yu Du; Minghua Li; Guixing Chen; Lin Su; Chao Li; Dong Fu; Hoiio Kong (Advances in Atmospheric Sciences, 2025)

Two new withanolides from Physalis minima L - Li-Jie Zhang; Mei-Lin Peng; Shi-Ying Xu; Fu-Rui Wang; Lin-Lin Yu; Qin-Feng Zhu; Shang-Gao Liao; Guo-Bo Xu (Natural Product Research, 2025)

Tight sandstone reservoirs in lacustrine environments: review and perspectives - Chen-Lin Hu; Zi-Qiang Lin; Xin Li; Jonathan Atuquaye Quaye; Zhi-Qiang Fu (International Geology Review, 2025)

Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

The mechanisms of MTOCs maturation in human and mouse oocytes - Hao Gu; Ling Wu; Mingru Yin; Xingzhu Du; Jing Fu; Fangzhou Xu; Zhiqi Ye; Xuelin Zhang; Huixia Jing; Yuxi Luo; Wenzhi Li; Xiaoxi Sun; et al. (Science Bulletin, 2025)

The SDGSAT-1 mission and its role in monitoring SDG indicators - Huadong Guo; Changyong Dou; Dong Liang; Bihong Fu; Hongyu Chen; Ziming Zou; Peng Huang; Xiaoming Li; Fansheng Chen; Chengshan Han; Juanjuan Jing; Tai Hu; et al. (Remote Sensing of Environment, 2025)

New natural products from Rhododendron ciliicalyx subsp. Lyi - Chun-Lin Guo; Si-Xuan Liu; Lu Zhang; Ling Li; Yong-Fu Lu; Si-Yang Dai; Chang Li; Yue-Hu Pei (Phytochemistry Letters, 2025)

The influence of water flow disturbance form on the granulation of algae sludge: Granulation property, treatment effect and algae biological structure - Peng-fei Yu; Ao Wang; Hai-wen Sun; Ding Wang; Xing-guan Ma; Yu-jia Wang; Bo-mei Hu; Li-yao Han; Yu-bo Fu; Dian-lin Jiang; Shi-gang Tu (Journal of Water Process Engineering, 2025)

Simulation of surface water–groundwater interaction in coal mining subsidence areas: A case study of the Kuye River Basin in China - Xiang Li; Song Du; Shihang Hu; Donglin Dong; Dong Jiang; Chenglong Cao; Gang Lin; Jingying Fu (Journal of Hydrology, 2025)

Oxidative pyrolysis of biomass waste: Efficient production of humic substances with enhanced agricultural potential and environmental benefits - Jian Li; Wen Fu; Xiaowei Bai; Ning Mao; Xiangrui Lin; Heping Yang; Mengfei Wang; Guangxuan Liu; Zhenghua Dai (Journal of Cleaner Production, 2025)

Characteristics of atmospheric reduced-sulfur compounds at a suburban site of Shanghai - Kai Deng; Juntao Huo; Yuwei Wang; Lihong Wang; Sijia Yin; Chuang Li; Yueyang Li; Gan Yang; Lei Yao; Qingyan Fu; Lin Wang (Journal of Environmental Sciences, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

Tough, strongly adhesive, and highly conductive eutectogels enabled by homogeneous and stable organic–inorganic hybrid networks - Baochen Gu; Wenzhen Qin; Gaoyuan Li; Hongmin Ji; Bai Huang; Baofeng Lin; Chuanhui Xu; Yen Wei; Lihua Fu (Chemical Engineering Journal, 2025)

Multifunctional flexible multilayer pressure sensor for pressure sensing, energy harvesting and versatile applications - Fu-Rui Teng; Song Sun; Si-Chen Tan; Ying-Jie Ma; Yue Huang; Lin Zhu; Di Wu; Ai-Dong Li (Chemical Engineering Journal, 2025)

Waste cotton thread-derived SnO2 microfibres for enhanced sensing to trace triethylamine and application in meat freshness detection - Jing-Han Wang; Xiao-Na Zhang; Kuo Lin; Wen-Xiao Li; Bao-Yu Song; Fei Ye; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2025)

Linking two types of breccias to sediment-hosted stratiform copper (SSC) and iron oxide-copper-gold (IOCG) deposits in the Kangdian metallogenic belt, SW China - Xue-Qing Yin; Xin-Fu Zhao; Zhi-Kun Su; Hai-Tao Lin; Zhi-Min Zhu; Wen-Lei Song; Martin Yan Hei Li; Kui-Dong Zhao (Mineralium Deposita, 2025)

Both biotic and abiotic soil N₂O productions are lower under organic N than inorganic N deposition in a Moso bamboo forest - Wenting Jiang; Yan Wang; Yongxin Lin; Hiroko Akiyama; Yunying Fang; Tony Vancov; Shenglei Fu; Hojeong Kang; Xinli Chen; Zhengqin Xiong; Zhijie Li; Shuijin Hu; et al. (Biology and Fertility of Soils, 2025)

2-Arylbenzofurans from the stems and leaves of Artocarpus tonkinensis and their potential antiproliferative activities - Jia-Ming Guo; Lin-Xuan Li; Xin-Yi Li; Tian-Yu Wang; En-Ning Zhu; An-Jiao Wu; Shu-Ri Li; Hui- Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2025)

Machine Learning-Based Remote Sensing Inversion and Spatiotemporal Characterization of Chl-a Concentration in the Leizhou Peninsula Coastal Waters - Xia Chai; Bei Liu; Fengcheng Guo; Yuchen Chen; Ye Lin; Yongze Li; Guo Yu; Dongyang Fu (Journal of Marine Science and Engineering, 2025)
The Leizhou Peninsula, located in the northern South China Sea, features coastal waters with dual functions as both marine ranch demonstration zones and ecological protection areas. Remote sensing monitoring of Chlorophyll-a (Chl-a) concentration in this region holds strategic significance for assessing primary productivity, red tide risk, and the sustainability of the blue food economy. This study integrates in situ survey data from four cruises conducted between 2020 and 2024 with Sentinel-3 OLCI remote sensing imagery, constructing and comparing the performance of six machine learning inversion models. The results show that for the inversion scenarios of the Leizhou Peninsula waters, the GBDT model performs best among the evaluated models (R2 = 0.79, RMSE = 0.36 mg/m3, MAE = 0.30 mg/m3). Based on the GBDT model, pixel-by-pixel inversion maps with 300 m spatial resolution were generated for four seasons in 2024, revealing a spatial gradient of “high nearshore–low offshore, high in the east–low in the west” and a seasonal pattern of “low in spring–rise in summer–stable in autumn–high in winter.” In addition, the study verified the operational potential of machine learning in complex type-II waters, analyzed the distribution characteristics and influencing factors of Chl-a concentration in this region, and provided scientific and technical support for marine ranch carrying capacity assessment, eutrophication early warning, and carbon sink accounting in the Leizhou Peninsula.

Vanadium-cobalt oxide nanoflower catalyst for efficient and stable overall water splitting in alkaline and seawater electrolytes - Yong-qi Tian; Song-lin Xu; Jia Li; Shuang-shuang Zhang; Bo-yao Zhang; Rong-da Zhao; Fu-fa Wu; De-peng Zhao (Next Research, 2025)

From pigment to electrocatalyst: The journey of Prussian Blue in electrochemical sensing - Li Fu; Cheng-Te Lin; Hassan Karimi-Maleh (Next Research, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

The emerging threat of hybrid microplastics: Impacts on per(poly)fluoroalkyl substance bioaccumulation and phytotoxicity in floating macrophytes - Zi-wei Chen; Zu-lin Hua; Ye-bing Shi; Li Gu; Fu-zhu Ye; Jia-yun Chen; Peng Guo (Journal of Hazardous Materials, 2025)

AhR-mediated histone lactylation drives cellular senescence during benzo[a]pyrene-evoked chronic obstructive pulmonary disease - Li-Hong Chen; Jun-Ping Wei; Meng-Die Li; Xiu Lu; Yi-Cheng Ma; Yu Wang; Ling Zheng; Jun Fei; Wei Cao; De-Xiang Xu; Jin Yang; Hui Zhao; et al. (Journal of Hazardous Materials, 2025)

The advantages in crop yields and carbon footprints of maize-soybean relay strip intercropping - Zhidan Fu; Ping Chen; Ping Lin; Yiling Li; Kai Luo; Chao Gao; Tian Pu; Yuze Li; Yushan Wu; Xiaochun Wang; Taiwen Yong; Wenyu Yang (Journal of Environmental Management, 2025)

Dynamic changes in metabolites during the manufacture of three distinct flavor types of Tieguanyin - Lin Zeng; Yan-Qing Fu; Jin-Long Liu; Yuan-Chao Li; Shui-lian Gao; Ying Gao; Fang Wang; Yong-Quan Xu (Food Chemistry, 2025)

Comprehensive analysis of volatile flavor components in pear fruit spanning the entire development stages - Lu Shi; Wanlin He; Menghua Lin; Xiaohui Fu; Yahui Li; Ying Liang; Zhiyong Zhang (Food Chemistry, 2025)

Perovskite-socketed FeCoNiCu quaternary alloy nanoparticles for efficient CO2 reduction in solid oxide electrolyzer - Shuo Liu; Lin-Bo Liu; Ming Yang; Yan Li; Qinglin Pan; Yifei Sun; Xian-Zhu Fu; Subiao Liu; Jing-Li Luo (Chemical Engineering Journal, 2025)

Interfacial water masking agent: Dynamic synergistic regulation of anode and cathode for ultra-long-life aqueous zinc metal batteries - Bin Xie; Chao Li; Min Li; Lieyuan Zhang; Zhaodan Fu; Yijia Luo; Gehong Su; Xin Tan; Heng Zhang; Qiaoji Zheng; Yu Huo; Jingxin Zhao; et al. (Chemical Engineering Journal, 2025)

A rapid and efficient microenvironment improving hyaluronic acid microneedle dressing for burn wound synergistic treatment - Lin Lei; Wei Li; Jiajia Wang; Qi Liu; Feng Zeng; Yunqiang Xiang; Xinyuan Fu; Rui Tao; Zhangyou Yang (Carbohydrate Polymers, 2025)

A unique demersal fish fauna in the Chukchi Borderland, Central Arctic Ocean - Ran Zhang; Hai Li; Puqing Song; Rui Wang; Jing Zhang; Tianci Wang; Shusen Fu; Shigang Liu; Yuan Li; Xing Miao; Lei Yang; Longshan Lin (Reviews in Fish Biology and Fisheries, 2025)

Modification effects of socioeconomic, demographic, and geographic factors on the association between temperature and cause-specific mental disorders among Taiwanese population - Gerry Andhikaputra; Li-Wen Deng; Hsi-Yu Hsiao; Yu-Kai Lin; Ta-Chien Chan; Hsuan-Fu Chao; Yu-Chun Wang (International Journal of Biometeorology, 2025)

Canopy Exchange Process of Heavy Metals in Subtropical Urban Forest in Southern China - Han-Wen Zhang; Zhi-Yun Jiang; Yi-Hua Xiao; Lin Huang; Shui-Xia Li; Zhi-Gao Fu; Si-Yi Zhang; Yu-Jun Ma (Environmental Processes, 2025)

Whole-genome resequencing-based assessment of genomic diversity and selection signatures in Rhipicephalus microplus from Shaanxi, China - Yi-yao Mou; FU-wen Wang; YU-kun Kang; Ya-qing Li; YU-ying Yang; Tian-yuan Liu; Chu-zhao Lei; Qing Lin (Veterinary Parasitology, 2025)

Contact-dependent antagonism is mediated by a T7SSb toxin effector–immunity protein pair via ADP-ribosylation - Hongxin Guan; Huan Wu; Mengrou Gan; Jing Zhang; Jiajun Wang; Siyao Liu; Shuyue Chen; Yindi Jiao; Fan Li; Shiqing Huang; Sihuang Lin; Hongwei Chen; et al. (Science Bulletin, 2025)

Primary greisen-type tin mineralization: Insights from unidirectional solidification texture in oxidized, fluorine-rich ores from the Paleocene Kalonta Sn-W deposit, southern Myanmar - Jin-Xiang Li; Wei-Ming Fan; Rui Yuan; Lamu Ciren; Li-Yun Zhang; Fu-Long Cai; Ya-Hui Yue; Jing Xie; Lin Ding (Journal of Asian Earth Sciences, 2025)

Initiatorless solar-photopolymerized heterostructured hydrogel with high performance, environmental adaptability, and recyclability - Chenghao Wang; Ping Li; Mingming Deng; Lin Luo; Boyi Fu; Qi Liu; Chi Huang (Chemical Engineering Journal, 2025)

Micropatterned piezoelectric films induced by modulated corona field for weak signal detection - Fu Lv; Chenghang Yu; Bing Liu; Jiamin Lin; Zijian Hong; Yongjun Wu; Zhaohui Ren; Qilong Zhang; Shurong Dong; Jikui Luo; Juan Li; Yuhui Huang (Chemical Engineering Journal, 2025)

Ecological risks under combined pollution: Toxicological effects of clothianidin and microplastics on Penaeus vannamei - Zhi Luo; Zhi-Yu Lin; Zhen-Fei Li; Zhen-Qiang Fu; Feng-Lu Han; Er-Chao Li (Aquatic Toxicology, 2025)

Exploring Lumbar Ligamentum Flavum, Disc Height and Foraminal Height Variations Across Different Postures: A Cadaveric Computed Tomography Investigation - Yuan-Fu Liu; Nozomu Inoue; Yu-Hua Dean Fang; Jing-Yao Wang; Alejandro A. Espinoza Orías; Chao-Jui Chang; Cheng-Li Lin (Journal of Medical and Biological Engineering, 2025)

Decadal transport of trace elements in a cave system based on 16 years monitoring data: Implications for paleoclimate reconstruction - Xin Fu; Yan Yang; Jingyao Zhao; Yidong Li; Xiaomin Chen; Zhimao Ye; Mingyang Li; Jingfeng Lin; Yanzhi Xu (Applied Geochemistry, 2025)

Mechanisms of endothelial senescence and vascular aging - Qiao Li; Zonghao Qian; Yuzhen Huang; Xiao Yang; Jiankun Yang; Nanyin Xiao; Guangyu Liang; Heng Zhang; Yanguang Fu; Yan Lin; Cuntai Zhang; Anding Liu (Biogerontology, 2025)

The formation of a hybrid fish derived from Labeo rohita ♀ × Cyprinus carpio ♂ and exhibiting stronger low temperature tolerance - Jiali Lin; Haoran Zhang; Jietao Wang; Bing Fu; Zexun Zhou; Wuhui Li; Huirong Yang; Shaojun Liu (Aquaculture, 2025)

Applicability of three remote sensing based soil moisture variables for mapping soil organic matter in areas with different vegetation densities - Chenconghai Yang; Lin Yang; Lei Zhang; Feixue Shen; Di Fu; Shengfeng Li; Zhiqiang Chen; Chenghu Zhou (Journal of Hydrology, 2025)

Amino-functionalized MIL-101(Fe)-NH2 as efficient peracetic acid activator for selective contaminant degradation: Unraveling the role of electron-donating ligands in Fe(IV) generation - Renjie Pan; Zongchen Li; Tian-Yang Zhang; Qi Fu; Zheng-Xiong Zheng; Jun Shi; Jian Lu; Chen-Yan Hu; Yu-Lin Tang; Mohamed Gamal El-Din; Bin Xu (Journal of Hazardous Materials, 2025)

A new approach to color correction and equalization for generating mars global color image mosaics from Tianwen-1 MoRIC images - Xin Ren; Xiaoxia Zhang; Wangli Chen; Wei Yan; Xingguo Zeng; Xu Tan; Xingye Gao; Qiang Fu; Lin Guo; Qing Zhang; Zhaopeng Chen; Guobin Yu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Rapid evaluation of Curcuma origin and quality based on E-eye, flash GC e-nose, and FT-NIR combined with machine learning technologies - Qiang Guo; Ming-xuan Li; Rao Fu; Xin Wan; Wen-hao Dong; Chun-qin Mao; Zhen-hua Bian; De Ji; Tu-lin Lu; Yu Li (Food Chemistry, 2025)

pH-responsive drug-targeted delivery system: Dual-drug loading hollow mesoporous silica for synergistic therapy bacterial enteritis of Micropterus salmoides - Yuan-shuai Fu; Yue Lin; Wen-jun Zhong; Xing-yu Wang; Xi-ke Li; Yun-ao Li; Sheng-bo Ye; Wen-juan Li; Yong-heng Zhu (Chemical Engineering Journal, 2025)

Fabrication of self-supporting hierarchical porous metallic glass for pH-universal hydrogen evolution reaction - Xingran Zhao; Junsheng Liu; Heting Zhang; Jihan Jiang; Jiaqing Lin; Jianan Fu; Yu Zhang; Xin Li; Wenqing Ruan; Jiang Ma (Chemical Engineering Journal, 2025)

Effect of fetch on street canyon flow field and pollutant dispersion - Daniel Ziyue Peng; Bingchao Zhang; Yunfei Fu; Xisheng Lin; Wenke Li; Tim K.T. Tse; Cruz Y. Li (Building and Environment, 2025)

Role of Dorsolateral Prefrontal Cortex During Motor Preparation on Anticipatory Postural Adjustments - Jiajia Yang; Guifang Zhang; Xiaoyu Gao; Xue Cheng; Zengming Hao; Jinjin Ma; Nanhe Lin; Ruochen Fu; Wai Leung; Ambrose Lo; Yan Li; Hao Xie; et al. (Brain Topography, 2025)

Forest conversion and root trenching reshape microbial functions regulating root litter decomposition and soil carbon dynamics - Lixia Wang; Shuangjia Fu; Haoying Gao; Huichao Li; Yang Liu; Lin Xu; Li Zhang; Han Li; Chengming You; Sining Liu; Hongwei Xu; Bo Tan; et al. (Applied Soil Ecology, 2025)

Estimation of rice yield using multi-source remote sensing data combined with crop growth model and deep learning algorithm - Jian Lu; Jian Li; Hongkun Fu; Wenlong Zou; Junrui Kang; Haiwei Yu; Xinglei Lin (Agricultural and Forest Meteorology, 2025)

Chitosan Nano-Selenium Supplementation Improves Production Performance, Egg Quality, and Selenium Deposition in Aging Laying Hens - Gang Shu; Xin Yi; Lei Yang; Jingyi Chen; Kang Fu; Haohuan Li; Funeng Xu; Wei Zhang; Hualing Fu; Bo Jing; Felix Kwame Amevor; Yingjie Wang; et al. (Biological Trace Element Research, 2025)

Alternating electric field as an effective inhibitor of bioavailability and phytotoxicity of heavy metals during electric field-assisted aerobic composting - Tao Fu; Chang Shen; Huan Mi; Jiahuan Tang; Long Li; Hao Lin; Huayuan Shangguan; Zhen Yu (Journal of Hazardous Materials, 2025)

Sulfonamide-linked π-conjugated carbon nitride with enhanced intramolecular carrier generation and transfer for efficient photocatalysis - Jiajun Fu; Si Chen; Xuanhui Lin; Zongrui Li; Zhao Mo; Mingyue Dong; Zhigang Chen; Hui Xu (Journal of Environmental Chemical Engineering, 2025)

Adsorption and oxidation of NO and N2O on soot surfaces: Evolution of functional groups - Shuo Jin; Chenyang Fan; Zheng Fu; Haizhao Li; Ye Liu; Bin Xu; Huiyong Du; Guorong Lin; Mingliang Wei (Fuel, 2025)

Inorganic arsenic in aquatic products in Shenzhen, China from 2018 to 2024: Levels, temporal variation and health risk assessment - Bo Fu; Kai Lin; Sisi Yu; Yiming Ge; Xinjie Li; Wenchao Zhu; Lei Tan; Rui Wang; Jixi Ou; Shaoyou Lu (Food and Chemical Toxicology, 2025)

The shrimp NF-κB pathway is activated to mediate the antioxidant defense and apoptosis under ammonia-N stress - Hongbiao Zhuo; Lanting Lin; Yuan Zhang; Shuo Fu; Jinyan Li; Xiaoxun Zhou; Guangbo Wu; Chaoan Guo; Jianyong Liu (Fish & Shellfish Immunology, 2025)

A novel integrated method for ultrasonic-assisted MSWI fly ash decarbonization with PCDD/Fs detoxification and synergistic heavy metals stabilization - Jie Chen; Congkai Fu; Xiaoqing Lin; Xiaodong Li; Jianhua Yan (Environmental Pollution, 2025)

In situ multifunctional gel for hormone-immune therapy of ovarian cancer and prevention of postoperative adhesion - Yankun Zhang; Yanbin Shi; Hengchang Zang; Xiaogang Zhao; Xianglei Fu; Shengnan Qiu; Yuan Zhang; Yingying Liu; Xiaoyu Wan; Zengmei Li; Yaqi Li; Jiamin Zhou; et al. (Chemical Engineering Journal, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Effects of Environmentally Friendly Aquaculture Chamber Coatings on Enzyme Activities, Histology, and Transcriptome in the Liver of Larimichthys crocea - Xuan Xu; Huayu Song; Huicai Wu; Lu Zhang; Fengjun Lin; Chonghui Chen; Xiaoxu Zhang; Yiying Liu; Chao Li; Qiang Fu (Marine Biotechnology, 2025)

Development of the novel formulations of perospirone for the treatment of schizophrenia - Zijun Zhang; Famin Ke; Jili Wu; Xiyao Li; Xin Chen; Lanxing Zhang; Pei Jing; Zerong Liu; Zhongbing Liu; Ruilin Lu; Shihua Fu; Meiling Zhou; et al. (Drug Delivery and Translational Research, 2025)

Study on seeding delay time and lag distance of automatic section control system for maize seeder - Lin Ling; Hanqing Li; Yuejin Xiao; Weiqiang Fu; Jianjun Dong; Liwei Li; Rui Liu; Xinguang Huang; Guangwei Wu; Zhijun Meng; Bingxin Yan (Computers and Electronics in Agriculture, 2025)

The depletion of TFAM and p-β-catenin(S552) in mitochondria in response to BoAHV-1 productive infection leads to decreased mitochondrial biogenesis - Jiayu Lin; Xiaotian Fu; Xuan Li; Xiuyan Ding; Shitao Li; Filomena Fiorito; Liqian Zhu (Veterinary Microbiology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Woody plant cell walls: Fundamentals and utilization - Wei Li; Ying-Chung Jimmy Lin; Ying-Lan Chen; Chenguang Zhou; Shuang Li; Nette De Ridder; Dyoni M. Oliveira; Lanjun Zhang; Baocai Zhang; Jack P. Wang; Changzheng Xu; Xiaokang Fu; et al. (Molecular Plant, 2025)

Chlorella-regeneration of exhausted D301-Zr nanocomposite adsorbent of phosphate sequestration from water: A multi benefits approach with adsorbent regeneration, phosphorus reuse, and carbon fixation - Mingwei Fu; Mingyang Lin; Sufeng Wang; Jingshan Li (Journal of Water Process Engineering, 2025)

Study on the nitrogen migration of different biomass by activated carbon-based MOF catalyst in hydrothermal environment - Gui-zhong Deng; Xiao-dong Tang; Jing-jing Li; Lin-yu Zhang; Zhi Yang; Fu-xiang Yang (Fuel, 2025)

Mechanisms of urea combined with nitrification inhibitors on prompting cadmium uptake and accumulation in rape (Brassica napus L.) - Li Li; Lin Chen; Xin Fu; Zhong Hu; Qingru Zeng; Xiao Deng; Yang Yang; Si Luo (Plant and Soil, 2025)

Effects of 2-hydroxypropyl-β-cyclodextrin and 28-homobrassinolide on the physiological characteristics, gene expression and terpenoid indole alkaloid accumulation in Catharanthus roseus cambial meristematic cell cultures - Fangfang Fu; Haihua Li; Li Ling; Jiahe Li; Yifei Chen; Weijie Hu; Jiayu Li; Lin Ou; Zhaoxi Chen; Jun Li; Pengfei Zhou (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Ribosomal protein S3A (RPS3A), as a transcription regulator of colony-stimulating factor 1 (CSF1), promotes glioma progression through regulating the recruitment and autophagy-mediated M2 polarization of tumor-associated macrophages - Liang Zhang; Kun Wang; Fei Li; Lingxue Zhang; Lin Wu; Ru Tie; Kamulan Litifu; Yujie Fu; Simeng Liu; Jiaxin Ni; Pan Chang; Jun Xu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Three new dimeric 2-(2-phenethyl)chromones from the agarwood of Aquilaria malaccensis - Xian-Yun Yan; Wei Li; Hao Wang; Wen-Hua Dong; Jun Zeng; Fei Wu; Wen-Li Mei; Lin-Fu Liang; Hao-Fu Dai (Phytochemistry Letters, 2025)

The colorimetric identification chips of artificial visual recognition and rapid digital response for detecting pollutants - Shichao Guo; Li Wang; Lin Hu; Qiangqiang Tao; Qiuyan Hu; Fu Feng; Wei Jin; Chuanbin Li; Ning Hu (Journal of Cleaner Production, 2025)

Oxidative pyrolysis characteristics and exothermic heat release effects of cellulose, hemicellulose, and lignin - Jian Li; Wen Fu; Xiaowei Bai; Xiangrui Lin; Heping Yang; Mengfei Wang; Guangxuan Liu; Zhenghua Dai (Fuel, 2025)

Dietary pyridoxine promoted muscle protein deposition relating to PI3K/AKT/TOR pathway and the ubiquitin proteasome system in grass carp (Ctenopharyngodon idella) - Li-Fu Gong; Xiao-Qiu Zhou; Lin Feng; Pei Wu; Wei-Dan Jiang; Yao-Bin Ma; Xiao-Wan Jin; Hong-Mei Ren; Jia-Yong Tang; Fa-Li Wu; Yang Liu (Food Bioscience, 2025)

A fully Coupled thermal-hydrodynamic–chemical numerical model for simulating gas hydrate-bearing sediments dissociation based on peridynamic differential operator method - Linfeng Zhang; Guorong Wang; Zhiyuan Li; Lin Zhong; Qiang Fu; Jiwei Wu; Mengdi Wu; Dongmei Liang; Yuhang Zheng (Computers and Geotechnics, 2025)

Boosting photocatalytic hydrogen evolution from binary mixture of hydrophilic-hydrophobic conjugated polymer dots with variable saponification degrees and molecular weights - Khanh Do Gia Huynh; Yu-Ting Huang; Meng-Che Tsai; Islam M.A. Mekhemer; Jayachandran Jayakumar; Yu-Tung Lin; Chun-Hao Li; Swatilekha Pratihar; Tse-Fu Huang; Dung Chau Kim Hoang; Shang-Da Yang; Ho-Hsiu Chou; et al. (Chemical Engineering Journal, 2025)

Effects of Fe/Mg-modified lignocellulosic biochar on in vitro ruminal microorganism fermentation of corn stover - Yuping Liu; Jiyu Sun; Taotao Zhao; Lin Wang; Chenyu Zhao; Jingjing Fu; Dawei Li; Haiye Yu (Bioresource Technology, 2025)

Regulatory Roles of Exosomes in Aging and Aging-Related Diseases - Nanyin Xiao; Qiao Li; Guangyu Liang; Zonghao Qian; Yan Lin; Heng Zhang; Yangguang Fu; Xiao Yang; Cun-Tai Zhang; Jiankun Yang; Anding Liu (Biogerontology, 2025)

Winter wheat harvest detection via Sentinel-2 MSI images - Jibo Yue; Yihan Yao; Jianing Shen; Ting Li; Nianxu Xu; Haikuan Feng; Yihao Wei; Xin Xu; Yinghao Lin; Wei Guo; Yuanyuan Fu; Hongbo Qiao; et al. (International Journal of Remote Sensing, 2025)

Deoxygenation preceding the Carnian Pluvial Episode (Late Triassic) in the Qiangtang Basin (Tibetan Plateau): Implications for organic and inorganic geochemistry and petrography - Fei Lin; Jian Wang; Ahmed Mansour; Xiugen Fu; Shaohua Su; Ying Nie; Mohamed S. Ahmed; Shengqiang Zeng; Xueren Li (Marine and Petroleum Geology, 2025)

Activation of persulfates on carbon nanotubes for water decontamination: Is the non-radical process consistently considered across different pH levels? - Jiali Peng; Lun Li; Shihuai Deng; Hongyu Zhou; Yanjun Li; Chenye Fu; Long Lin; Yue Yuan; Wei Wei; Guochun Lv; Gang Yang; Xiaohui Lu; et al. (Journal of Hazardous Materials, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Nontargeted metabolomics combining with intestinal microbiota and hypolipidemia targets elucidates anti-hyperlipidemia effect of Sangju yinzha tea in hyperlipidemia rats - Jinmei Wang; Lin Guo; Xuting Hao; Tianhao Li; Dongqi Liu; Fu Zhang; Xiaoyu Chen; Wenyi Kang (Food Bioscience, 2025)

Effect of oral Mn-based nanozymes Mn3O4 NPs on morphological, antioxidation, mucosa, and fecal microbial community in mice colons - Baoyue Zhang; Lei Yang; Zhengkun Wu; Xianxiang Wang; Xiaoling Zhao; Wei Zhang; Danqin Li; Hualin Fu; Juchun Lin; Funeng Xu; Xiaoyang Ai; Gang Shu (Food and Chemical Toxicology, 2025)

NF-κB inhibitor PDTC involved in regulating the transplantation immunity in the pearl oyster Pinctada fucata martensii - Shirong Fu; Xinyi Lin; Xiaowen Lu; Youmei Qu; Hongxi Chen; Shilin Zheng; Zhihan Li; Yu Jiao; Qingheng Wang; Chuangye Yang; Yuewen Deng (Fish & Shellfish Immunology, 2025)

Research on improving the quality of groundwater self-monitoring via Blockchain technology - Haixiang Li; Dongxue Fu; Meiyue Yang; Sijie Lin; Song Zongzhong; Wei Jiang Liu; Qing Hu (Environmental Impact Assessment Review, 2025)

Combined exposure effects: Multilevel impact analysis of cycloxaprid and microplastics on Penaeus vannamei - Zhi-Yu Lin; Zhi Luo; Zhen-Fei Li; Zhen-Qiang Fu; Feng-Lu Han; Er-Chao Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Tuning photoluminescence and electroluminescence of multi-resonance thermally activated delayed fluorescence emitters through peripheral donor modification for highly efficient deep-blue OLEDs - Chen-Lu Hou; Sai Guo; Yu-Fu Sun; Jia-Xuan Hu; Hong-Jin Liao; Xiao Li; Fu-Lin Lin; Lingyi Meng; Xu-Lin Chen; Can-Zhong Lu (Chemical Engineering Journal, 2025)

High electrocatalytic activity of crystallization-modulated ordered PtCu3/C nanoalloy catalysts for oxygen reduction reaction - Xiaomei Li; Linfeng Fu; Lin Cao; Lihui Lei; Xinxing Zhan; Changgang Hu; Xin Tong; Juan Tian (Chemical Engineering Journal, 2025)

In-situ gel injection of poloxamer-based metamizole provides long-acting antipyretic effects - Yueli Wang; Dongbo Li; Xiaojuan Li; Dandan Ren; Wei Zhang; Gang Shu; Juchun Lin; Haohuan Li; Funeng Xu; Guangneng Peng; Hualin Fu (Drug Delivery and Translational Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

A new diterpenoid alkaloid from the Aconitum scaposum - Cheng-En Fu; Gui-Fang Li; Guo-Qing Sun; Shuai Huang; Lin Chen; Xian-Li Zhou (Phytochemistry Letters, 2025)

Calcium and iron isotope fractionation during felsic magma differentiation - Qiu-Yun Guan; Jin-Xiang Li; Ya-Li Sun; Shi-Lei Tang; Noreen J. Evans; Zhao-Feng Zhang; Li-Yun Zhang; Fu-Long Cai; Wei-Ming Fan; Lin Ding (Lithos, 2025)

Fire dynamics, fire generated pollutants, and acute health implications: A scaling law analysis of heavy-fuel-oil pool fires - Kuang-Chung Tsai; Li-Hsin Cheng; Chi-Fu Yeh; Tzu-Yan Tseng; Tzu-Ping Tseng; Li-Jen Huang; Shu-Hsing Yeh; Hui-Tsung Hsu; Ching-Ho Lin; Chin-Hsing Lai; Peter Brimblecombe; Ming-Jen Chen (Fuel, 2025)

Antibacterial activity of zinc oxide nanoparticles against Shewanella putrefaciens and its application in preservation of large yellow croaker (Pseudosciaena crocea) - Mengqing Liu; Yuhan Mo; Zheyun Dong; Huicheng Yang; Bangchu Lin; Yongyong Li; Yongjiang Lou; Shiqian Fu (Food Research International, 2025)

Analysis of the effect of three different blanching processes on the flavor profile of peeled and unpeeled broad beans - Lu Shi; Xiaohui Fu; Menghua Lin; Yahui Li; Ying Liang; Zhiyong Zhang (Food Research International, 2025)

Exploration of the impact of different drying methods on the quality of Gastrodia elata: A study based on drying kinetics and multidimensional quality evaluation - Ming-xuan Li; Bin Wang; Yu Li; Xin-ru Nie; Jing Mao; Qiang Guo; Nuo Xu; Rao Fu; Zhi-jun Guo; Xiao-li Zhao; Zhen-hua Bian; Tu-lin Lu; et al. (Food Chemistry, 2025)

Improving the bactericidal activity of carvacrol against Bacillus cereus by the formation of sodium casein-stabilized nanoemulsion and its application in milk preservation - Jun Li; Fu-Yu Liu; Bao-Lin He; Rui Cui; Hong Wu (Food Hydrocolloids, 2025)

A systematic review on heavy metals in indoor air: Occurrence, spatial variation, and health risk - Ni Liang; Zekun Li; Jie Sun; Nan Fu; Guoliang Zhong; Xianbiao Lin; Kang Mao; Peng Zhang; Zhaofeng Chang; Dong Yang; Wei Du; Guofeng Shen; et al. (Building and Environment, 2025)

A large-scale FireLine global positioning method based on a single unmanned aerial vehicle - Yifan Fu; Haiyu Zhang; Xingdong Li; Chuanying Lin; Yue Ma; Hongyang Zhao; Shufa Sun (International Journal of Remote Sensing, 2025)

Geochemical Characteristics and Hydrocarbon Generation and Expulsion of Oligocene Yacheng Formation Source Rocks in the Northern Yinggehai Basin - Yanan Wang; Zhipeng Huo; Gaowei Hu; Jianxiang Pei; Lin Wei; Lin Hu; XiaoFei Fu; Weihong Wang; Jianbo Gao; Jingshuang Luo; Jiansheng Li (Natural Resources Research, 2025)

Mitochondrial genomes reveal low genetic diversity in snow leopards - Shiqing Wang; Haimeng Li; Yinping Tian; Yu Lin; Yingna Zhou; Jan E. Janecka; Yuan Fu; Yue Ma; Zhen Wang; Tianming Lan (Conservation Genetics, 2025)

Study on the characteristics of bird communities in urban river corridor parks and green spaces - Yinghong Ding; Dulai Zheng; Yuxin Lin; Junyi Li; Weicong Fu; Ziru Chen; Jin Yang; Xiaoling Xu; Zhipeng Zhu (Environment, Development and Sustainability, 2025)

Inclusion Complex of Nimodipine with Sulfobutylether-β-cyclodextrin: Preparation, Characterization, In Vitro and In Vivo Evaluation - Jiahui Liu; Meichai Li; Yongjie Huang; Xinyu Wang; Youfa Xu; Zhiqin Fu; Zhizhe Lin; Jianming Chen; Xin Wu (AAPS PharmSciTech, 2025)

Inactivated LMBV vaccine with nano‑aluminum adjuvant provided immune protection in largemouth bass (Micropterus Salmoides) - Xia Luo; Ruoxuan Wang; Baofu Ma; Ouqin Chang; Xiaozhe Fu; Hongru Liang; Yinjie Niu; Qiang Lin; Lihui Liu; Aijun Lv; Ningqiu Li (Aquaculture, 2025)

Upcycling Nickel Ions into self-supported Electrocatalyst by using ZIF-8/Bacterial cellulose adsorbent - Jian-Yu Wu; Tian Liu; Lin Ma; Xian-Zhong Fu; Zhi-Yan Guo; Kim Meow Liew; Wen-Wei Li (Resources, Conservation and Recycling, 2025)

Review of vibration induced by gas-liquid two-phase flow inside pipes - Lin Ding; Yitong Fu; Xiang Li; Jingyu Ran (Ocean Engineering, 2025)

Genesis of Botryococcus-rich laminae of the Eocene Upper Xiaganchaigou Formation in the western Qaidam Basin, NW China - Guolong Liu; Mingzhen Zhang; Rongchang Zhao; Dunzhu Jiaoba; Xiangtong Lei; Baoxia Du; Jing Zhang; Shaohua Lin; Peihong Jin; Aijing Li; Jing Peng; Yiqiao Fu; et al. (Marine and Petroleum Geology, 2025)

Dissolved oxygen activated by single-atom-state iron coupled with sodium dithionite for norfloxacin degradation: Efficiency and mechanism - Wei Song; Sen Xu; Caixia Fu; Ruiyi Huang; Hongze Fang; Li Li; Dachao Lin; Yuning Fang; Xing Du; Zhihong Wang (Journal of Cleaner Production, 2025)

Strengthening peroxymonosulfate activation via cotton-derived carbon: Pathway transformation from radical to non-radical - Runbin Su; Yonglin Ma; Lei Liu; Qiangshun Wu; Du Fu; Yu Li; Hongjun Lin; Xiaoxuan Wei; Muhammad Saboor Siddique; Jianrong Chen; Xi-Lin Wu (Journal of Cleaner Production, 2025)

Microbiome changes and characteristics under nutrient injection for enhanced oil production at Daqing oilfield - Zi-Yue Fu; Wen-Tao Chen; Gui-Na Qi; Zhao-wei Hou; Yi-Fan Liu; Li-Bin Shou; Lei Zhou; Shi-Zhong Yang; Xiao-Lin Wu; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2025)

Effect of wall slip of CO2-in-water foams on enhanced oil recovery - Biao Xu; Jiuqing Li; Lin Zhu; Junyan Xu; Runze Wang; Shun Li; Jiajia Fu; Jingyi Yang; Tao Liu (Chemical Engineering Journal, 2025)

Ground ozone rise during the 2022 shanghai lockdown caused by the unfavorable emission reduction ratio of nitrogen oxides and volatile organic compounds - Qian Wang; Yuewu Li; Fangqian Zhong; Wanqi Wu; Hongliang Zhang; Rong Wang; Yusen Duan; Qingyan Fu; Qing Li; Lin Wang; Shaocai Yu; Abdewahid Mellouki; et al. (Atmospheric Environment, 2025)

CircHAT1 regulates the proliferation and phenotype switch of vascular smooth muscle cells in lower extremity arteriosclerosis obliterans through targeting SFRS1 - Xian-ying Huang; Fang-yong Fu; Kai Qian; Qiao-li Feng; Sai Cao; Wei-yu Wu; Yuan-lin Luo; Wei-jie Chen; Zhi Zhang; Shui-chuan Huang (Molecular and Cellular Biochemistry, 2025)

Clinical efficacy and safety of vortioxetine as an adjuvant drug for patients with bipolar depression - Chunxiao Dai; Yaoyang Fu; Xuanwei Li; Meihua Lin; Yinbo Li; Xiao Li; Keke Huang; Chengcheng Zhou; Jian Xie; Qingwei Zhao; Shaohua Hu (Journal of Zhejiang University-SCIENCE B, 2025)

The obesity-related mutation gene on nonalcoholic fatty liver disease - Yen-Yu Chen; Chi-Sheng Chen; Jee-Fu Huang; Wen-Hsiu Su; Chia-Yang Li; Wei-Shiun Chen; En-Sheng Lin; Wan-Long Chuang; Ming-Lung Yu; Shu-Chi Wang (Human Genetics, 2025)

Increased Mineral‐Associated Organic Carbon and Persistent Molecules in Allochthonous Blue Carbon Ecosystems - Yuan Li; Chuancheng Fu; Chenglong Ye; Zhaoliang Song; Yakov Kuzyakov; Tony Vancov; Laodong Guo; Zhongkui Luo; Lukas Van Zwieten; Yidong Wang; Yu Luo; Weiqi Wang; et al. (Global Change Biology, 2025)
Coastal wetlands contain very large carbon (C) stocks—termed as blue C—and their management has emerged as a promising nature‐based solution for climate adaptation and mitigation. The interactions among sources, pools, and molecular compositions of soil organic C (SOC) within blue C ecosystems (BCEs) remain elusive. Here, we explore these interactions along an 18,000 km long coastal line of salt marshes, mangroves, and seagrasses in China. We found that mineral‐associated organic C (MAOC) is enriched in BCEs dominated by allochthonous inputs and abundant active minerals, leading to an increased proportion of persistent organic molecules. Specifically, soils with large allochthonous inputs (> 50%) are characterized by a substantial contribution of MAOC (> 70%) to total SOC with a notable preservation of lipids (36%) across salt marshes, mangroves, and seagrasses. The burial of allochthonous particles, derived from external sources such as rivers or tidal influxes, facilitates the formation of stable MAOC through binding to mineral surfaces or occlusion within microaggregates. The proportions of particulate organic C (POC) and MAOC are important predictors for molecular compositions of soil organic matter. Lipid proportions within molecular composition decrease as POC and autochthonous C proportions increase. These findings provide new insights into the coupled control over SOC sequestration in BCEs, emphasizing the role of allochthonous inputs, proportions of carbon pools, and persistent organic components.

PM2.5-mediated cardiovascular disease in aging: Cardiometabolic risks, molecular mechanisms and potential interventions - Francis Chanda; Kai-xuan Lin; Abdallah Iddy Chaurembo; Jian-yuan Huang; Hui-juan Zhang; Wen-hui Deng; Yun-jing Xu; Yuan Li; Li-dan Fu; Hao-dong Cui; Chi Shu; Yang Chen; et al. (Science of The Total Environment, 2024)

Hydrocyclone-induced classification reduction and spin desorption of contaminated soil remediation with heavy metal and organics - Yi Liu; Jiahui Ren; Kai Ma; Jianping Li; Pengbo Fu; Kuangfei Lin; Hualin Wang (Journal of Hazardous Materials, 2024)

Comparison of the short- and long-term effects of zinc ions on the anaerobic mesophilic co-digestion of food waste and waste activated sludge: Digester performance, antibiotic resistance gene reduction and the microbial community - Bao-Shan Xing; Yi-Meng Su; Yu-Lin Fu; Yi-Fan Wu; Chen-Hao Yan; Xiaochang C. Wang; Yu-You Li; Rong Chen (Journal of Hazardous Materials, 2024)

Insights into pore structure-activity relationships of iron catalysts supported on fluorine–cerium nanosheets for heterogeneous Fenton oxidation - Jing Lv; Hui Ye; Shurui Han; Jinli Zhao; Guodong Yang; Han Zhang; Xiaojian Fu; Jing Zhang; Qingping Xin; Lizhi Zhao; Hong Li; Ligang Lin; et al. (Journal of Environmental Chemical Engineering, 2024)

Mechanisms of radical regulation during carbamazepine degradation by UV-LED/chlorine process with different wavelengths in water - Qi Fu; Zhi Zhang; Yi-Li Lin; Tian-Yang Zhang; Yun-Lu Zhang; Renjie Pan; Meng-Yuan Xu; Zheng-Xiong Zheng; Jian Lu; Zheng-Ning Luo; Chao Zeng; Huan He; et al. (Journal of Environmental Chemical Engineering, 2024)

Black soldier fly larvae promote the resource of cyanobacteria: Frass-mixed compost - Rui Li; YuFeng Jiang; ChangXue Wang; Kai Luo; XiaoLei Fan; TianHui Lin; RongBo Guo; ShanFei Fu (Journal of Environmental Chemical Engineering, 2024)

Insights into novel phosphorus-doped biochar for tetracycline removal: Non-radical oxidation and adsorption - Xi Fu; Xiaojun Niu; Dongqing Zhang; Ling Li; Xingyao Ye; Shan Liao; Maoyu Li; Chuting Lao; Deye Chen; Yu Lin; Zhiquan Yang (Journal of Environmental Chemical Engineering, 2024)

Mechanism and controlling factors of mass transport complexes migration: A case study of the mass transport complexes in the taranaki deep water basin, New Zealand - Yongsheng Zhou; Wei Wu; Jianwei Feng; Guangxu Wang; Aihua Fu; Shiqin Liang; Lulu Wu; Qingchao Li; Weiqing Liu; Zhendong Feng; Changsong Lin; Panpan Chen; et al. (Geomorphology, 2024)

Polygonati Rhizoma varieties and origins traceability based on multivariate data fusion combined with an artificial intelligence classification algorithm - Peng Chen; Chenghao Fei; Rao Fu; Xiaoyan Xiao; Yuwen Qin; Xiaoman Li; Zhijun Guo; Jianmin Huang; De Ji; Lin Li; Tulin Lu; Qiaosheng Guo; et al. (Food Chemistry, 2024)

Surfactin conjugated ZIF-8-NH2 based MOF with the antibacterial ability against Pseudomonas fluorescens and its application in salmon preservation - Yongfa Cheng; Yongyong Li; Jinjie Zhang; Huicheng Yang; Bangchu Lin; Zheyun Dong; Yongjiang Lou; Shiqian Fu (Food Bioscience, 2024)

Effect of low-salinity seawater transient on antioxidant capacity, muscle quality and intestinal microorganism of crucian carp (Carassius auratus gibelio) - Yawen Hong; Yunyun Pan; Qijian Zhu; Yongyong Li; Huicheng Yang; Bangchu Lin; Zheyun Dong; Yongjiang Lou; Shiqian Fu (Food Bioscience, 2024)

Specific detection of crustacean allergens in food: Development of indirect competitive and sandwich ELISA targeting sarcoplasmic calcium binding protein - Wenye Zhu; Zhihui Qin; Yuhao Huang; Qi Fu; Hao Wang; Ziye Zhang; Xiang Gao; Yinghui Liu; Hong Lin; Zhenxing Li (Food Bioscience, 2024)

Acesulfame potassium induces hepatic inflammation and fatty acids accumulation via disturbance of carnitine metabolism and gut microbiota - Na Shou; Christopher Rensing; Qiwen Lin; Wenqian Xu; Keyi Fu; Xuefeng Yuan; Dandan Wu; Fan Wang; Yanzhong Li; Zunji Shi (Food Bioscience, 2024)

Structural characterization and prebiotic activity evaluation of novel fucosylated disaccharides prepared from bacterial exopolysaccharides - Shihao Nan; Xinmiao Ren; Mengshi Xiao; Lin Zhu; Haijin Mou; Ningyang Li; Rong Li; Shaoping Nie; Xiaodan Fu (Food Bioscience, 2024)

Exposure to toluene diisocyanate induces dysbiosis of gut-lung homeostasis: Involvement of gut microbiota - Yuxuan Gou; Fu Lin; Li Dan; Dianyu Zhang (Environmental Pollution, 2024)

Alterations in leukocyte telomere length and mitochondrial DNA copy number in benzene poisoning patients - Dianpeng Wang; Dafeng Lin; Xiangli Yang; Dongpeng Wu; Peimao Li; Zhimin Zhang; Wen Zhang; Yan Guo; Song Fu; Naixing Zhang (Molecular Biology Reports, 2024)

Molecular phylogeny of Podoscypha (Basidiomycota, Podoscyphaceae) with descriptions of four new species, inferred from nuclear rDNA sequences - Fu-Chang Huang; Jian-Tian Lin; Hai-Fu Zheng; Yun-Long Liang; Miao-Miao Li; Cheng-Pei Ding (Mycological Progress, 2024)

Lymph nodes in oral squamous cell carcinoma: a comprehensive anatomical perspective - Guang-Rui Wang; Nian-Nian Zhong; Lei-Ming Cao; Xuan-Hao Liu; Zi-Zhan Li; Yao Xiao; Kan Zhou; Yi-Fu Yu; Bing Liu; Lin-Lin Bu (Clinical & Experimental Metastasis, 2024)

Physical, Chemical, Biological, and Synergistic Technologies for Remediation of Pesticide-Contaminated Soil - Qian Li; Dongdong Wen; Caidie Qin; Yuting Qian; Rongbing Fu; Sijie Lin (Reviews of Environmental Contamination and Toxicology, 2024)

Effects of Temporary Rearing with Edetate Disodium on Shrimp ( Litopenaeus vannamei ) Based on UPLC-MS Untargeted Metabolomics - Yutong Wu; Jing Yang; Zixuan Kang; Yongyong Li; Huicheng Yang; Bangchu Lin; Zheyun Dong; Yongjiang Lou; Shiqian Fu (Journal of Aquatic Food Product Technology, 2024)

Unraveling the toxicity mechanisms of nanoplastics with various surface modifications on Skeletonema costatum: Cellular and molecular perspectives - Ting-Ting Xu; Zhen-Liang Li; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Tao Li; Eddy Y. Zeng; Ke-Fu Yu; Xiang-Rong Xu (Science of The Total Environment, 2024)

Shallow groundwater table fluctuations weaken nitrogen accumulation in the thin layer vadose zone of cropland around plateau lakes, Southwest China - Qingfei Chen; Anqiang Chen; Jinheng Min; Lin Li; Wanli Hu; Chi Wang; Bin Fu; Shufang Guo; Dan Zhang (Science of The Total Environment, 2024)

Efficient degradation of ciprofloxacin by innovative VUV/BN system: Kinetics, mechanism and toxicity assessment - Hongda Zhan; Zili Lin; Lingrong Chen; Zhenjun Xiao; Dezhu Liu; Yishun Wang; Zhihong Chen; Zhenchao Li; Zengkai Fu; Linsheng Liu; Zihong Xu; Shuyue Chen; et al. (Journal of Water Process Engineering, 2024)

Folding of a single layer in an anisotropic viscous matrix under layer-parallel shortening - Yuan-bang Hu; Paul D. Bons; Tamara de Riese; Shu-gen Liu; Maria-Gema Llorens; Eloi González-Esvertit; Enrique Gomez-Rivas; Dian Li; Yu-zhen Fu; Xue-lin Cai (Journal of Structural Geology, 2024)

Comprehensive evaluation of the distribution, transport and ecological risk of heavy metals in intra-urban river sediments using high-resolution techniques - Kang Liao; Weijie Li; Zhiwei Huang; Shu Lin; Lingfang Fu; Wei Liu; Huaiyang Fang; Hong Deng (Environmental Pollution, 2024)

In-situ fabrication of defect rich Cu2+1O on electrodeposited Cu cone arrays for promoting electrocatalytic anode hydrogen production - Yanhong Weng; Huanhua You; Danni Liu; Hao Chen; Hao Lin; Guodong Fu; Fengzhan Si; Jiujun Zhang; Xian-Zhu Fu; Jing-Li Luo (Chemical Engineering Journal, 2024)

Comprehensive investigation of daytime radiative cooling technology for sustainable grain storage: A combined approach of field measurement and CFD simulations - Chongjia Lin; Yunlong Wang; Zhihang Zhao; Xisheng Lin; Rui Li; Zhaoping Zheng; Xuhua Shen; Zhongqing Lang; Weizhi Zhou; Jinbei Wang; Dan Yuan; Yankai Sun; et al. (Building and Environment, 2024)

Correction to: Identification and map‑based cloning of an EMS‑induced mutation in wheat gene TaSP1 related to spike architecture - Lin Zhang; Huidan Zhou; Xian Fu; Niuniu Zhou; Mengjie Liu; Shenglong Bai; Xinpeng Zhao; Ruiru Cheng; Suoping Li; Dale Zhang (Theoretical and Applied Genetics, 2024)

Exploring the short-term effects of extreme temperatures on tuberculosis incidence in Shantou, China: a Coastal City perspective - Yaqian Su; Ruiming Chen; Zhuanghao Chen; Jianxiong Lin; Hui Fu; Zicheng Cao; Qiaocheng Chang; Liping Li; Suyang Liu (International Archives of Occupational and Environmental Health, 2024)

Correction to: A rho-type GTPase activating protein affects the growth and development of Cordyceps cicadae - Xueqian Li; Yu Zou; Neeraj Shrivastava; Jiandong Bao; Fu-Cheng Lin; Hongkai Wang (Archives of Microbiology, 2024)

Advantages of targeted ventilation for farrowing houses: An analysis from perspectives of thermal environment, biosecurity and ventilation efficacy - Longhuan Du; Xuan Tao; Lin Zhu; Jinchuan Li; Min Fu; Jingwen Lai; Chaowu Yang; Zhiping He (Computers and Electronics in Agriculture, 2024)

Anthropogenic shrub encroachment has accelerated the degradation of desert steppe soil over the past four decades - Yanan Zhao; Hongmei Wang; Zhigang Li; Gang Lin; Jingying Fu; Zhili Li; Zhenjie Zhang; Dong Jiang (Science of The Total Environment, 2024)

Female urinary incontinence in China after 15 years’ efforts: Results from large-scale nationwide surveys - Jiming Zhu; Haiyu Pang; Peicheng Wang; Yanhua Chen; Huihui Li; Qing Liu; Luwen Wang; Hangmei Jin; Liyan Gong; Jingyan Xie; Ting Lai; Aiyang Li; et al. (Science Bulletin, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

New insight into catalytic performance and reaction mechanism for butyl acetate over CeO2 catalysts: Oxygen vacancy and surface reactive oxygen species - Jiajia Lin; Wenjing Kong; Chuying Qiu; Xueyun Zhong; Yanjun Li; Mingli Fu; Zhenguo Li (Journal of Environmental Chemical Engineering, 2024)

A naturaly attenuated largemouth bass ranavirus strain provided protection for Micropterus salmoides by immersion immunization - Xiaozhe Fu; Wenxian Li; Cong Liu; Xia Luo; Qiang Lin; Yinjie Niu; Hongru Liang; Baofu Ma; Ningqiu Li (Fish & Shellfish Immunology, 2024)

Positively charged loose nanofiltration membranes via the assembly of amino-quinone networks for efficient dye/salt separation - Tian Gao; Ping Fu; Wan-Long Li; Wan-Ting Lin; Yuan-Hui Yu; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2024)

A tetrahedral framework nucleic acids-based gene therapeutic nanococktail alleviates cartilage damage and protects against osteoarthritis progression - Liwei Fu; Jiang Wu; Sirong Shi; Zhichao Zhang; Yazhe Zheng; Pinxue Li; Xun Yuan; Zhengang Ding; Chao Ning; Xiang Sui; Shuyun Liu; Quanyi Guo; et al. (Chemical Engineering Journal, 2024)

Enhanced electrochemical cyclability of composite sodium metal anode with inorganic-rich solid electrolyte interphase - Changqun Cen; Xiaoxue Yang; Xiancheng Wang; Lin Fu; Yuanjian Li; Ke Lu; Liqing He; Yongming Sun (Chemical Engineering Journal, 2024)

Integration of single-cell and bulk RNA sequencing revealed immune heterogeneity and its association with disease activity in rheumatoid arthritis patients - Xiaofan Mao; Maohua Shi; Beiying Zhang; Rongdang Fu; Mengyun Cai; Sifei Yu; Kairong Lin; Chuling Zhang; Dingru Li; Guoqiang Chen; Wei Luo (Immunologic Research, 2024)

Interpenetrating LiB/Li3BN2 phases enabling stable composite lithium metal anode - Piao Qing; Shaozhen Huang; Tuoya Naren; Quan Li; Haifeng Huang; Kecheng Long; Zhijian Liu; Lin Mei; Fu Sun; Weifeng Wei; Yu Zhang; Jianmin Ma; et al. (Science Bulletin, 2024)

Utilizing spontaneous plants for sustainable development in residential green spaces: Insights from environmental drivers and niche analysis in Fuzhou City, China - Chengyu Ran; Junyi Pan; Yuxin Lin; Tongyan Li; Yaling Huang; Jingkai Huang; Shiyuan Fan; Wenqiang Fang; Shuang Zhao; Yuxiang Liu; Jiali Jin; Weicong Fu (Journal of Environmental Management, 2024)

Transcriptomics to evaluate the influence mechanisms of ethanol on the ester production of Wickerhamomyces anomalus with the induction of lactic acid - Wenqin Cai; Yin Wan; Yanru Chen; Haowei Fan; Mengxiang Li; Shengwen Wu; Pei Lin; Tingting Zeng; Huibo Luo; Dan Huang; Guiming Fu (Food Microbiology, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Hierarchical supramolecules composed of starch-based nanocluster aggregates with light-responsive mechanical strain for remotely rapid and precise actuation - Fu-Xiang Wei; Xu Yuan; Feng-Qiong Jiang; Zhen Wang; Yong-Fu Deng; Chuan-Hui Xu; Li-Hua Fu; Bao-Feng Lin (Carbohydrate Polymers, 2024)

Losses and destabilization of soil organic carbon stocks in coastal wetlands converted into aquaculture ponds - Shaoying Lin; Yaxin Zhou; Weiqi Wang; Jordi Sardans; Yuan Li; Chuancheng Fu; Fanjiang Zeng; Zhaoliang Song; Akash Tariq; Josep Peñuelas (Global Change Biology, 2024)
Coastal‐wetlands play a crucial role as carbon (C) reservoirs on Earth due to their C pool composition and functional sink, making them significant for mitigating global climate change. However, due to the development and utilization of wetland resources, many wetlands have been transformed into other land‐use types. The current study focuses on the alterations in soil organic‐C (SOC) in coastal‐wetlands following reclamation into aquaculture ponds. We conducted sampling at 11 different coastal‐wetlands along the tropical to temperate regions of the China coast. Each site included two community types, one with solely native species ( Suaeda salsa , Phragmites australis and Mangroves) and the other with an adjacent reclaimed aquaculture pond. Across these 11 locations we compared SOC stock, active OC fractions, and soil physicochemical properties between coastal wetlands and aquaculture ponds. We observed that different soil uses, sampling sites, and their interaction had significant effects on SOC and its stock ( p p p

Highly alkaline electrokinetic extraction: Characteristics of chromium mobilization, conversion and transport in high alkalinity soil - Junnian Wu; Changze Wang; Zihuang Lin; Naichen Li; Yupeng Fu; Jiang Li; Chang Chen; Yinliu Li (Chemosphere, 2024)

Relating the carbon sources to denitrifying community in full-scale wastewater treatment plants - Jinling Chen; Xia Tang; Xuewei Wu; Biping Li; Xia Tang; Xueran Lin; Pengfei Li; Hang Chen; Fu Huang; Xuhan Deng; Xiaojing Xie; Chaohai Wei; et al. (Chemosphere, 2024)

Effects of Fe(III) on the formation and toxicity alteration of halonitromethanes, dichloroacetonitrile, and dichloroacetamide from polyethyleneimine during UV/chlorine disinfection - Tingting Huang; Lin Deng; Shui Wang; Chaoqun Tan; Jun Hu; Bingqing Zhu; Mengya Li; Lianghua Lu; Zhihua Yin; Bowen Fu (Water Research, 2024)

Establishment of a callus induction system of Saxifraga stolonifera Meerb. and its response to different elicitors - Lin Song; Ta Zhao; Chun-Li Luo; Jin-Ling Li; Song-Shu Chen; Dan-Dan Li; Jin Liang; Hong-Chang Liu; Fu-Lai Luo; Ming-Jin Huang; Hua-Lei Wang (South African Journal of Botany, 2024)

Deep learning-based geological map generation using geological routes - Chaoling Li; Fengdan Li; Chang Liu; Zhen Tang; Si Fu; Min Lin; Xia Lv; Shuang Liu; Yuanyuan Liu (Remote Sensing of Environment, 2024)

First identification of Mid-Miocene north–south trending dikes in the eastern Qiangtang terrane, eastern Tibet: Mantle melting and implications for plateau uplift - Chuan-Bing Xu; Jun Wang; Qiang Wang; Andrew C. Kerr; Wu-Fu Li; Jin-Heng Liu; Bing-Zhang Wang; Shan-Ping Li; Chun-Tao Wang; Zi-Long Wang; Lin Gong (Lithos, 2024)

Developmental toxicity of the neonicotinoid pesticide clothianidin to the larvae of the crustacean Decapoda, Penaeus vannamei - Zhi Luo; Zhi-Yu Lin; Zhen-Fei Li; Zhen-Qiang Fu; Feng-Lu Han; Er-Chao Li (Journal of Hazardous Materials, 2024)

Multiple metabolite profiles uncover remarkable bioactive compounds and metabolic characteristics of noni fruit (Morinda citrifolia L.) at various stages of ripeness - Congyan Su; Ming Yang; Shuai Chen; Chuanxian Fu; Lin Zhang; Sixin Liu; Jiamu Kang; Congfa Li (Food Chemistry, 2024)

Long-range infrared absorption spectroscopy and fast mass spectrometry for rapid online measurements of volatile organic compounds from black tea fermentation - Chongshan Yang; Leizi Jiao; Chunwang Dong; Xuelin Wen; Peng Lin; Dandan Duan; Guanglin Li; Chunjiang Zhao; Xinglan Fu; Daming Dong (Food Chemistry, 2024)

Cross-linked g-C3N4 nanofibers enable thermal stable composite membranes for high-performance loose nanofiltration - Wan-Ting Lin; Ping Fu; Wan-Long Li; Yuan-Hui Yu; Zi-Lu Zhang; Hong-Yu Fan; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Chemical Engineering Journal, 2024)

Stabilizing Cu0/Cu2+ interface by hydroxy-rich amorphous SiO2 for enhanced electrocatalytic CO2 reduction to ethylene - Jie Zhu; Sifan Wang; Jiaji Zhang; Zhecheng Fang; Weitao Ji; Gaobo Lin; Lei Guo; Bolong Li; Jianghao Wang; Jie Fu (Chemical Engineering Journal, 2024)

High dimensional proteomic mapping of bone marrow immune characteristics in immune thrombocytopenia - Feng-Qi Liu; Qing-Yuan Qu; Ying Lei; Qi Chen; Yu-Xiu Chen; Meng-Lin Li; Xue-Yan Sun; Ye-Jun Wu; Qiu-Sha Huang; Hai-Xia Fu; Yuan Kong; Yue-Ying Li; et al. (Science China Life Sciences, 2024)

MSC-Derived Extracellular Vesicles Alleviate NLRP3/GSDMD-Mediated Neuroinflammation in Mouse Model of Sporadic Alzheimer’s Disease - Lishan Lin; Longxin Huang; Sen Huang; Weineng Chen; Heng Huang; Li Chi; Fengjuan Su; Xiaoqing Liu; Kang Yuan; Qiuhong Jiang; Changu Li; Wanli W. Smith; et al. (Molecular Neurobiology, 2024)

Relay intercropping boosts soybean recovery growth and delays nodule senescence to achieve yield advantages - Ping Chen; Benchuan Zheng; Huan Yang; Qing Du; Zhidan Fu; Kai Luo; Yilin Li; Ping Lin; Xihong Peng; Tian Pu; Yushan Wu; Xiaochun Wang; et al. (Agriculture, Ecosystems & Environment, 2024)

A rho-type GTPase activating protein affects the growth and development of Cordyceps cicadae - Xueqian Li; Yu Zou; Neeraj Shrivastava; Jiandong Bao; Fu-Cheng Lin; Hongkai Wang (Archives of Microbiology, 2024)

A 76-m per pixel global color image dataset and map of Mars by Tianwen-1 - Jianjun Liu; Xin Ren; Wei Yan; Wangli Chen; Xingguo Zeng; Xiaoxia Zhang; Xu Tan; Xingye Gao; Qiang Fu; Dingxin Liu; Lin Guo; Qing Zhang; et al. (Science Bulletin, 2024)

Tomato NAC transcription factor NOR-like1 positively regulates tomato fruit softening - Zhen-Zhen Peng; Hong-Li Li; Gang-Shuai Liu; Xiao Su; Xiaodan Zhao; Donald Grierson; Lan-Ting Xiang; Jian-Lin He; Gui-Qin Qu; Hong-Liang Zhu; Ben-Zhong Zhu; Yun-Bo Luo; et al. (Postharvest Biology and Technology, 2024)

Reduction of haemoglobin is related to metal mixtures exposure in Chinese preschoolers: Joint effect models - Ye Fu; Minghui He; Yang Liu; Mingzhu Li; Meiqin Zhu; Yan Wang; Wei Lin; Lili Yu; Liting Yang; Yao Zhang; Yanli Liu; Hongxian Ji; et al. (Journal of Trace Elements in Medicine and Biology, 2024)

Bacterial assembly and succession patterns in conventional and advanced drinking water systems: From source to tap - Jie Liu; Renxin Zhao; Jie Feng; Wenjie Fu; Lijia Cao; Jiayu Zhang; Yusha Lei; Jiajin Liang; Lin Lin; Xiaoyan Li; Bing Li (Journal of Hazardous Materials, 2024)

Benzo[a]pyrene evokes epithelial-mesenchymal transition and pulmonary fibrosis through AhR-mediated Nrf2-p62 signaling - Meng-Die Li; Li-Hong Chen; Hui-Xian Xiang; Ya-Lin Jiang; Bian-Bian Lv; De-Xiang Xu; Hui Zhao; Lin Fu (Journal of Hazardous Materials, 2024)

Constructing hydroxyoxime-functionalized ionic liquid [BHIB][NTf2] for the separation of Mo(VI) from U(VI) - Feng Liu; Tao-Yuan Xiu; Wei Jin; Xuan Fu; Lin Wang; Xin-Peng Wang; Wei-Qun Shi; Li-Yong Yuan (Chemical Engineering Journal, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Next-generation neonicotinoid: The impact of cycloxaprid on the crustacean decapod Penaeus vannamei - Zhi Luo; Zhi-Yu Lin; Zhen-Fei Li; Zhen-Qiang Fu; Feng-Lu Han; Er-Chao Li (Chemosphere, 2024)

Low temperature acclimation of electroactive microorganisms may be an effective strategy to enhance the toxicity sensing performance of microbial fuel cell sensors - Yazhi Nong; Min Xu; Bingchuan Liu; Jianfeng Li; Dongye He; Chuanfu Li; Pinyi Lin; Yin Luo; Chenyuan Dang; Jie Fu (Water Research, 2024)

Exploring the chemical diversity of sesquiterpenes from the rarely studied south China sea soft coral Sinularia tumulosa assisted by molecular networking strategy - Sheng-Hui Zhu; Yuan-Min Chang; Song-Wei Li; Ming-Zhi Su; Li-Gong Yao; Lin-Fu Liang; Hong Wang; Yue-Wei Guo (Phytochemistry, 2024)

A new acetophenone derivative from Rhododendron irroratum subsp. pogonostylum - Yong-Fu Lu; Si-Xuan Liu; Chun-Lin Guo; Si-Yang Dai; Yi-Hui Yang; Chang Li; Yue-Hu Pei (Phytochemistry Letters, 2024)

Tissue factor pathway inhibitors disrupt structures of rhabdovirus/ranairidovirus and inhibit viral infection in Chinese perch, Siniperca chuatsi - Baofu Ma; Jingkang Li; Min Zhang; Xiaozhe Fu; Hongru Liang; Yinjie Niu; Qiang Lin; Xia Luo; Lihui Liu; Jianguo Su; Jin Zhou; Ningqiu Li (Fish & Shellfish Immunology, 2024)

Flexible fiber composite functional materials based on Fe-MOFs nanozyme catalytic activity for efficient point-of-use water disinfection - Hao Fu; Hao Li; Qiuwen He; Guangwu Du; Jianfang Li; Yuancheng Zhang; Yuntong Liang; Baofeng Lin (Chemical Engineering Journal, 2024)

Identification and map-based cloning of an EMS-induced mutation in wheat gene TaSP1 related to spike architecture - Lin Zhang; Huidan Zhou; Xian Fu; Niuniu Zhou; Mengjie Liu; Shenglong Bai; Xinpeng Zhao; Ruiru Cheng; Suoping Li; Dale Zhang (Theoretical and Applied Genetics, 2024)

Paleoclimatic application of spectral parameters to the eolian red clay of the Jianzha Basin, northeastern margin of the Tibetan Plateau - Chaofeng Fu; Ju’e Tian; Xinwen Xu; Yougui Song; Jun Zuo; Feng Wang; Lin Chen; Pengfei Li; Xiaoke Qiang (Science China Earth Sciences, 2024)

Heavy metal spatial distribution, source analysis, and ecological risks in the central hilly area of Hainan Island, China: results from a high-density soil survey - Jingjing Gong; Jianweng Gao; Hui Wu; Lujun Lin; Jianzhou Yang; Shixin Tang; Zhengliang Wang; Zhuang Duan; Yangang Fu; Yongwen Cai; Shuqi Hu; Yong Li (Environmental Geochemistry and Health, 2024)

Algae-bacteria consortia promotes the cell growth of marine microalgae Phaeodactylum tricornutum and Chrysotila roscoffensis - Jiaqi Fang; Yan Sun; Zhujun Zhu; Jian Li; Pengfei Cheng; Spiros N. Agathos; Yuanyuan Fu; Lin Zhang; Chengxu Zhou; Jichang Han (Algal Research, 2024)

Dictyosphaerium sp.-treated aerobic digestate of perishable waste as substitution for vegetable hydroponic nutrient solution - Mengjie Zhang; Xiaoyan Zhang; Qilu Cheng; Feifan Shi; Yuan Fu; Jianlin Xu; Bing Gu; Junwei Ma; Li Yang; Qifa Zhou; Hui Lin (Algal Research, 2024)

Mechanisms for improving the quality of crucian carp (Carassius auratus) by short-term low-salinity treatment revealed by UPLC-MS and GC–MS - Yawen Hong; Yunyun Pan; Qijian Zhu; Yongyong Li; Huicheng Yang; Bangchu Lin; Zheyun Dong; Yongjiang Lou; Shiqian Fu (Aquaculture International, 2024)

Effects of Natural and Artificial Seawater Temporary Rearing on Flavor and Immunomodulation of Acanthopagrus schlegelii : A Study Based on GC-MS and UPLC-MS Untargeted Metabolomics - Yunyun Pan; Yawen Hong; Shiqian Fu; Huicheng Yang; Bangchu Lin; Yongjiang Lou; Yongyong Li (Journal of Aquatic Food Product Technology, 2024)

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

Natural versus artificial seawater: Impacts on antioxidant capacity, muscle quality and gut microbiota of Acanthopagrus schlegelii during temporary rearing - Yunyun Pan; Chang Liu; Yawen Hong; Yongyong Li; Huicheng Yang; Bangchu Lin; Zheyun Dong; Yongjiang Lou; Shiqian Fu (Aquaculture, 2024)

Wavelength dependency and photosensitizer effects in UV-LED photodegradation of iohexol - Meng-Yuan Xu; Chao Zeng; Yi-Li Lin; Tian-Yang Zhang; Qi Fu; Heng-Xuan Zhao; Zhen-Ning Luo; Zheng-Xiong Zheng; Tong-Cheng Cao; Chen-Yan Hu; Bin Xu (Water Research, 2024)

Dinotefuran exposure alters biochemical, metabolomic, gut microbiome, and growth responses in decapoda pacific white shrimp Penaeus vannamei - Zhenqiang Fu; Zhiyu Lin; Kaiqi Huang; Zhenfei Li; Zhi Luo; Fenglu Han; Erchao Li (Journal of Hazardous Materials, 2024)

Experimental study on metal removal characteristics of Zhundong coal to produce ultra-clean coal using acid-alkali method - Yuanmao Chen; Chang'an Wang; Yang Li; Maoyun Luo; Chenglong Yang; Lin Zhao; Zhefan Wang; Ning Fu; Defu Che (Fuel, 2024)

Fabrication of starch-based oleogels using capillary bridges: Potential for application as edible inks in 3D food printing - Wenbo Miao; Yijie Fu; Zhiheng Zhang; Qianzhu Lin; Xiaojing Li; Shangyuan Sang; David Julian McClements; Han Jiang; Hangyan Ji; Chao Qiu; Zhengyu Jin (Food Hydrocolloids, 2024)

In situ conversion of ZnO anchored on porous carbon foams to antiflexible ZIF-8-X (X = Co or NH2) for sieving linear and mono-branched hexane isomers - Xufei Li; Yankang Zhou; Weiqiu Huang; Xinya Wang; Yuning Li; Lipei Fu; Jing Zhong; Lin Liu (Chemical Engineering Journal, 2024)

Environmental concentrations of acetaminophen and its metabolites promote the spread of antibiotic resistance genes through pheromone signaling pathway - Xinyue Fu; Xiaobo Yang; Xiaoli Lin; Li Zhu; Panpan Yang; Feng Wang; Zhiqiang Shen; Jingfeng Wang; Yun Ling; Zhigang Qiu (Chemical Engineering Journal, 2024)

BMSCs-laden mechanically reinforced bioactive sodium alginate composite hydrogel microspheres for minimally invasive bone repair - Shengjie Jiang; Hua Jing; Yu Zhuang; Jinjie Cui; Zeyu Fu; Dejian Li; Cancan Zhao; Usman Liaqat; Kaili Lin (Carbohydrate Polymers, 2024)

A new substrate equalization method for optimizing the influent conditions and fluid flow patterns of a multifed upflow anaerobic sludge blanket reactor with mature anammox granules - Bao-Shan Xing; Xi-Fang Tang; Ling-Hu Li; Yu-Lin Fu; Jia-Yi Liu; Ya-Ge Wang; Xin-Xin Sun; Yu-You Li; Rong Chen; Ren-Cun Jin (Bioresource Technology, 2024)

MAPK/NF-κB signaling mediates atrazine-induced cardiorenal syndrome and antagonism of lycopene - Fu-Wei Jiang; Jian-Ying Guo; Jia Lin; Shi-Yong Zhu; Xue-Yan Dai; Muhammad Asmat Ullah Saleem; Yi Zhao; Jin-Long Li (Science of The Total Environment, 2024)

The association between artificial light at night and gestational diabetes mellitus: A prospective cohort study from China - Junhao Liao; Chuan Yu; Jiarui Cai; Run Tian; Xingyue Li; Hong Wang; Lin Li; Guishuang Song; Leyao Fu; Xinxi Li; Qiaoyue Ge; Ling Zhang; et al. (Science of The Total Environment, 2024)

Two unprecedented neuroprotective 2-(2-phenylethyl)chromone derivatives from cultivated “Qi-Nan” agarwood of Aquilaria sinensis - Lin Zhang; Hao Wang; Wen-Hua Dong; Jun Zeng; Li Yang; Wei Li; Hui-Qin Chen; Jing-Zhe Yuan; Cai-Hong Cai; Zhen-Yu Li; Wen-Li Mei; Hao-Fu Dai (Phytochemistry Letters, 2024)

ALKBH5 SUMOylation-mediated FBXW7 m6A modification regulates alveolar cells senescence during 1-nitropyrene-induced pulmonary fibrosis - Se-Ruo Li; Ning-Ning Kang; Rong-Rong Wang; Meng-Die Li; Li-Hong Chen; Peng Zhou; De-Xiang Xu; Hui Zhao; Lin Fu (Journal of Hazardous Materials, 2024)

The effect of electron beam irradiation combined with slurry ice on physicochemical parameters and bacterial communities of shrimp (Litopenaeus vannamei) during refrigerated storage - Chang Liu; Yunyun Pan; Yongyong Li; Huicheng Yang; Bangchu Lin; Zheyun Dong; Yongjiang Lou; Shiqian Fu (Food Control, 2024)

A flexible wearable phase change composite with electro-/photo-thermal heating for personal thermal management and human body motion detection - Tianwen Luo; Lingli Kong; Luji Li; Junjie Lu; Zhiyu Yu; Baofeng Lin; Lihua Fu; Chuanhui Xu (Chemical Engineering Journal, 2024)

Optical sensors of volatile organic compounds for non-invasive diagnosis of diseases - Xiaoyun Qu; Yaping Hu; Chenggang Xu; Yue Li; Lin Zhang; Qiao Huang; Sareh Sadat Moshirian-Farahi; Jianmin Zhang; Xiahong Xu; Ming Liao; Yingchun Fu (Chemical Engineering Journal, 2024)

Diterpenoid alkaloids with chemotaxonomic significance from Aconitum polycarpum - Lin Chen; Jie Wen; Jia-Yi Ma; Ke Xu; Cheng-En Fu; Wen-Cheng Liang; Chen-Ying Zhu; Jin-Qiu Wang; Shuai Huang; Xian-Li Zhou (Biochemical Systematics and Ecology, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Dynamic changes in butyrate levels regulate satellite cell homeostasis by preventing spontaneous activation during aging - Shujie Chen; Liujing Huang; Bingdong Liu; Huimin Duan; Ze Li; Yifan Liu; Hu Li; Xiang Fu; Jingchao Lin; Yinlan Xu; Li Liu; Dan Wan; et al. (Science China Life Sciences, 2024)

The longevity evaluation of multi-metal stabilization by MgO in Pb/Zn smelter–contaminated soils - Ze-Lin Xu; Da-Mao Xu; Hai-Xuan Li; Hao-Kai Li; Rong-Bing Fu (Environmental Science and Pollution Research, 2024)

One-pot synthesis of interfacially bonded Bi4O5Br2/Bi2S3 Z-scheme heterostructures with boosted photocatalysis towards dodecylbenzenesulfonate and real hotel laundry wastewater - Wenqian Lian; Lei Wang; Lin Xu; Xiaofei Fu; Zuming He; Junwu Tao; Yongmei Xia; Huimin Li; Xinyue Xu (Chemosphere, 2024)

Ferrostatin‑1 alleviates liver injury via decreasing ferroptosis following ricin toxin poisoning in rat - Ruijiao Lin; Zijie Jia; Hongbing Chen; Hongli Xiong; Cunhao Bian; Xin He; Bi Wei; Junfeng Fu; Minzhu Zhao; Jianbo Li (Toxicology, 2024)

Timing of India-Asia suturing: Evidence from a remnant peripheral foreland basin in Xigaze, South Tibet - Xu-Dong Guo; Lin Ding; Qiu-yun Guan; Deng Zeng; Chao Wang; Gui-zhen Guo; Hou-Qi Wang; Mei-Yu Liu; Xiang-Li Ding; Muhammad Qasim; Ya-Hui Yue; Jing Xie; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Co-occurrence of organophosphate esters and phosphorus fractions in river sediments: Implications for pollution prediction and environment risk assessment - Lingfang Fu; Yuxin Liu; Shu Lin; Jieer Xiao; Weijie Li; Yang Yu; Hailong Zeng; Ping Li; Huaiyang Fang (Journal of Hazardous Materials, 2024)

Flutter control optimization for a 5000 m suspension bridge with active aerodynamic flaps: a CFD-enabled strategy - Zilong Wang; Lin Zhao; Yiheng Fu; Genshen Fang; Wei Cui; Ke Li; Yaojun Ge (Engineering Structures, 2024)

Constructing light-insensitive Ag(I) sites by in situ integration of nanoheaters for efficient adsorptive desulfurization - Jun Liu; Zhen Fu; Peng Tan; Min Li; Xiao-Qin Liu; Lin-Bing Sun (Chemical Engineering Journal, 2024)

Norepinephrine-induced hydrophilic Pd aerogels with photothermal-boosted multienzyme-like activity for chemodynamic therapy of MRSA infections - Minghui Wang; Na Li; Nanyun Lin; Yingying Wu; Wei Zhou; Ximei Sun; Peixian Wu; Qian Fu; Wenjie Wang; Zheng Liu; Shuiyuan He; Mengyu Zhou; et al. (Chemical Engineering Journal, 2024)

Contrasting range changes of Bergenia (Saxifragaceae) species under future climate change in the Himalaya and Hengduan Mountains Region - Li Qiu; Qing-Li Fu; Hans Jacquemyn; Kevin S. Burgess; Jia-Jing Cheng; Zhi-Qiong Mo; Xiao-Dong Tang; Bo-Yun Yang; Shao-Lin Tan (Theoretical and Applied Climatology, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Corrigendum to “Would it be better for partition prediction of heavy metal concentration in soils based on the fusion of XRF and Vis-NIR data?” [Sci. Total Environ. 908 (2024) 168381] - Taoran Shi; Zhaocong Fu; Xuhua Miao; Fenfang Lin; Jianyuan Ma; Shouyuan Gu; Li Li; Chunfa Wu; Yongming Luo (Science of The Total Environment, 2024)

An intrusion and environmental effects of man-made silver nanoparticles in cold seeps - Kelei Zhu; Jiawei Liu; Mingyu Zhao; Lulu Fu; Zengfeng Du; Fanqi Meng; Lin Gu; Peiyu Liu; Yan Liu; Chaoqun Zhang; Xin Zhang; Jinhua Li (Science of The Total Environment, 2024)

Self-assembly kieselguhr-based ZSM-5 for catalytic pyrolysis of mask waste to produce high value-added aromatics - Yufei Gu; Hucheng Ge; Yuke Liu; Qi Wei; Tianhua Gao; Hengshuo Gu; Hongbing Fu; Fuwei Li; Hongfei Lin; Lei Miao; Zhixia Li (Fuel, 2024)

Insight on the emulsifying mechanisms of low-salt type emulsions stabilized by Maillard conjugates: Myofibrillar protein peptide-dextrin with different degrees of hydrolysis - Zhiyu Li; Lin Lin; Gaofeng Fu; Zebin Guo; Chen Zhang (Food Chemistry, 2024)

Study on remediation of chromium contaminated soil by an improved electrokinetic extraction device with auxiliary liquid chamber - Junnian Wu; Zihuang Lin; Changze Wang; Yupeng Fu; Jiang Li; Yinliu Li; Chang Chen (Chemical Engineering Journal, 2024)

Simultaneous generation of free radicals, Fe(IV) and Fe(V) by ferrate activation: A review - Feilong Dong; Chuyun Fu; Mingbao Feng; Da Wang; Shuang Song; Cong Li; Eric Lichtfouse; Jinzhe Li; Qiufeng Lin; Virender K. Sharma (Chemical Engineering Journal, 2024)

Synthesis of nano-MgO hybrid SDB hydrophobic catalyst carriers and its adsorption behavior of Fe3+ - Y. Fan; H. R. Peng; C. Li; K. Fu; X. Y. Ren; H. J. Yang; S. D. Lin; C. L. Liu (International Journal of Environmental Science and Technology, 2024)

Corrigendum to “Leaf hydraulic distance is a good predictor of growth within and across conifer species in a Taiga ecosystem” [AgriculturalandForestMeteorology342(2023)109710] - Xingyue Li; Dayong Fan; Zhengxiao Liu; Zengjuan Fu; Changqing Gan; Zeyu Lin; Chengyang Xu; Han Sun; Xiangping Wang (Agricultural and Forest Meteorology, 2024)

The dynamic mechanism of scientific and technological innovation in China’s marine biomedical industry - Xiu-Mei Fu; Yan-Xin Tan; Ying Liu; Ying-Hui Han; Qiao-Qiao Qi; Jing-Hang Li; Chun-Yu Lin (Frontiers in Marine Science, 2024)
As one of the important forces promoting the development of the marine economy, the marine biomedical industry (MBI) shows typical knowledge and technology-intensive characteristics. It is of great significance to explore the industrial innovation dynamic mechanism for breaking through the bottleneck of innovative development as well as achieving high-quality development. This paper constructed a system dynamics model for scientific and technological innovation (STI) in the MBI and then explored the dynamic mechanism of STI in the industry through simulation. The study found that, in the innovation environment subsystem, the two factors of the intellectual property protection intensity and the government’s scientific research funding input had the most significant positive driving effects on STI of the MBI; the promotion of government education funding input showed a significant strengthening trend over time, while the marine environmental regulation intensity had comparatively little effect on the level of STI. In the subsystem of innovation input, both innovation funding input and innovation personnel input were the direct driving forces for the improvement of the STI level. And enterprises played a dominant role in STI because the STI level of the MBI was more sensitive to the changes in enterprise innovation input. Compared with the individual factor input, the synergistic promotion effect of multiple factors is more significant. In addition, it was found that there was a low conversion rate of scientific research achievements in China’s MBI by analyzing the influence of various factors changing on technological output and economic output. Based on the research results, this paper puts forward corresponding policy suggestions in order to provide theoretical support and a practical basis for promoting the technological innovation level of China’s MBI as well as references for other countries.

Vitamin D3 activates the innate immune response and xenophagy against Nocardia seriolae through the VD receptor in liver of largemouth bass (Micropterus salmoides) - Quanquan Cao; Ju Zhao; Mingyao Yan; Zhong Luo; Fu Luo; Lin Feng; Weidan Jiang; Pei Wu; Yan Wang; Debin Li; Haifeng Liu; Jun Jiang (Aquaculture, 2024)

Tigecycline-resistance mechanisms and biological characteristics of drug-resistant Salmonella Typhimurium strains in vitro - Lin Li; Longbo Wang; Shuo Yang; Yanfang Zhang; Yiming Gao; Qianyu Ji; Linran Fu; Qiling Wei; Feifei Sun; Shaoqi Qu (Veterinary Microbiology, 2024)

CFD- and BPNN- based investigation and prediction of air pollutant dispersion in urban environment - Xisheng Lin; Yunfei Fu; Daniel Z. Peng; Chun-Ho Liu; Mengyuan Chu; Zengshun Chen; Fan Yang; Tim K.T. Tse; Cruz Y. Li; Xinxin Feng (Sustainable Cities and Society, 2024)

Would it be better for partition prediction of heavy metal concentration in soils based on the fusion of XRF and Vis-NIR data? - Taoran Shi; Zhaocong Fu; Xuhua Miao; Fenfang Lin; Jianyuan Ma; Shouyuan Gu; Li Li; Chunfa Wu; Yongming Luo (Science of The Total Environment, 2024)

Microplastics elicit an immune-agitative state in coral - Chuan-Ho Tang; Ching-Yu Lin; Hsing-Hui Li; Fu-Wen Kuo (Science of The Total Environment, 2024)

A two-stage Fe(VI) oxidation process enhances the removal of bisphenol A for potential application - Feilong Dong; Chuyun Fu; Zhu Meng; Qiufeng Lin; Jinzhe Li; Tao Zeng; Da Wang; Juntao Tang; Shuang Song (Science of The Total Environment, 2024)

Woody plant cell walls: Fundamentals and utilization - Wei Li; Ying-Chung Jimmy Lin; Ying-Lan Chen; Chenguang Zhou; Shuang Li; Nette De Ridder; Dyoni M. Oliveira; Lanjun Zhang; Baocai Zhang; Jack P. Wang; Changzheng Xu; Xiaokang Fu; et al. (Molecular Plant, 2024)

Garnet geochemistry reveals late-stage oxidation of tin-bearing fractionated granite - Jin-Xiang Li; Lin Ding; Noreen J. Evans; Fang Xu; Wei-Ming Fan; Li-Yun Zhang; Fu-Long Cai; Qiu-Yun Guan; Ya-Hui Yue; Jing Xie (Lithos, 2024)

An indeterministic fractional two-stage inter-regional energy system optimization model: A case study for the Province of Shanxi, China - Y.L. Zheng; G.H. Huang; Y.P. Li; J.P. Chen; X. Zhou; B. Luo; Y.P. Fu; L.J. Lin; Z.P. Xu; W.C. Tang (Journal of Cleaner Production, 2024)

How do the occurrence patterns of potentially toxic elements (PTEs) control their release behaviours from Pb/Zn smelter contaminated soils? - Da-Mao Xu; Hao-Kai Li; Ze-Lin Xu; Rong-Bing Fu (Journal of Cleaner Production, 2024)

Removal of multiple pollutants in air pollution control devices of a coal-fired boiler installed with a flue gas condensation scrubber - Tailin Chen; Lejun Deng; Yuzhong Li; Jingwei Li; Xiling Zhao; Lin Fu (Journal of Cleaner Production, 2024)

Mechanical-Effect descriptor for oxygen reduction reaction and hydrogen evolution reaction on Single-Atomic Ni-Graphene catalysts - Wei Zhang; Fu-li Sun; Xue-long Zhang; Shuang-te Zhao; Wen-xian Chen; Gui-lin Zhuang (Fuel, 2024)

Bacterial, short-chain fatty acid and gas profiles of partially hydrolyzed guar gum in vitro fermentation by human fecal microbiota - Xiong-E Pi; Hao Fu; Xiao-Xia Yang; Zai-Chun Yu; Wei-Lin Teng; Yinjun Zhang; Xue-Wei Ye; Hui Hui Quan; Li-Zhi Lu; Wei Liu (Food Chemistry, 2024)

Effects of salinity in food waste on the growth of black soldier fly larvae and global warming potential analysis - Rui Li; TianHui Lin; XiaoLei Fan; XiaoFeng Dai; JieHua Huang; YiFeng Zhang; RongBo Guo; ShanFei Fu (Chemical Engineering Journal, 2024)

4-Hydroxybenzenesulfonic acid triggers rapid preparation of phenolic aerogel composites by ambient pressure drying - Xi Zhao; Lin Chen; Peng-Gang Su; Lin-Xi Xiao; Hai-Bo Zhao; Teng Fu; Xiu-Li Wang; Yu-Zhong Wang (Chemical Engineering Journal, 2024)

Interfacial coordination-assisted construction of mechanically robust, fluorescent and intumescent flame retardant epoxy resins - Xin-Miao Li; Wei-Bin Bai; Yu-Cai Lin; Fu-Chuan Ding; Rong-Kun Jian (Chemical Engineering Journal, 2024)

Metabolic engineering of Paenibacillus polymyxa for effective production of 2,3-butanediol from poplar hydrolysate - Jikun Zhang; Jianzhi Zhao; Quanbin Fu; Haiyang Liu; Min Li; Zhongyue Wang; Wei Gu; Xueming Zhu; Rongshan Lin; Li Dai; Kai Liu; Chengqiang Wang (Bioresource Technology, 2024)

Progression of an emission inventory of China integrating CO2 with air pollutants: A chance to learn the influence of development on emissions - Guorui Zhi; Jinhong Du; Aizhong Chen; Wenjing Jin; Na Ying; Zhihui Huang; Peng Xu; Di Wang; Jinghua Ma; Yuzhe Zhang; Jiabao Qu; Hao Zhang; et al. (Atmospheric Environment, 2024)

Climate and mineral accretion as drivers of mineral‐associated and particulate organic matter accumulation in tidal wetland soils - Chuancheng Fu; Yuan Li; Lin Zeng; Chen Tu; Xiaoli Wang; Haiqing Ma; Leilei Xiao; Peter Christie; Yongming Luo (Global Change Biology, 2024)
Tidal wetlands sequester vast amounts of organic carbon (OC) and enhance soil accretion. The conservation and restoration of these ecosystems is becoming increasingly geared toward “blue” carbon sequestration while obtaining additional benefits, such as buffering sea‐level rise and enhancing biodiversity. However, the assessments of blue carbon sequestration focus primarily on bulk SOC inventories and often neglect OC fractions and their drivers; this limits our understanding of the mechanisms controlling OC storage and opportunities to enhance blue carbon sinks. Here, we determined mineral‐associated and particulate organic matter (MAOM and POM, respectively) in 99 surface soils and 40 soil cores collected from Chinese mangrove and saltmarsh habitats across a broad range of climates and accretion rates and showed how previously unrecognized mechanisms of climate and mineral accretion regulated MAOM and POM accumulation in tidal wetlands. MAOM concentrations (8.0 ± 5.7 g C kg −1 ) (±standard deviation) were significantly higher than POM concentrations (4.2 ± 5.7 g C kg −1 ) across the different soil depths and habitats. MAOM contributed over 51.6 ± 24.9% and 78.9 ± 19.0% to OC in mangrove and saltmarsh soils, respectively; both exhibited lower autochthonous contributions but higher contributions from terrestrial or marine sources than POM, which was derived primarily from autochthonous sources. Increased input of plant‐derived organic matter along the increased temperature and precipitation gradients significantly enriched the POM concentrations. In contrast, the MAOM concentrations depended on climate, which controlled the mineral reactivity and mineral–OC interactions, and on regional sedimentary processes that could redistribute the reactive minerals. Mineral accretion diluted the POM concentrations and potentially enhanced the MAOM concentrations depending on mineral composition and whether the mineral accretion benefited plant productivity. Therefore, management strategies should comprehensively consider regional climate while regulating sediment supply and mineral abundance with engineering solutions to tap the OC sink potential of tidal wetlands.

In vivo and in vitro, antiviral effects of two mixture of Chinese herbal drug active monomers against MSRV and LMBV in largemouth bass (Micropterus salmoides) - Yinjie Niu; Xiaozhe Fu; Qiang Lin; Hongru Liang; Xia Luo; Shaozhi Zuo; Lihui Liu; Ningqiu Li (Aquaculture, 2023)

Spatialized importance of key factors affecting park cooling intensity based on the park scale - Zhihua Liu; Lizhao Fu; Chaofan Wu; Zhenzhen Zhang; Zhaoyang Zhang; Xingwen Lin; Xuan Li; Yuhong Hu; Haixian Ge (Sustainable Cities and Society, 2023)

Westerly aridity in the western Tarim Basin driven by global cooling since the mid-Pleistocene transition - Hongye Liu; Rui Zhang; Yansheng Gu; Gaowen Dai; Lin Li; Shuo Guan; Zhongbiao Fu (Quaternary Science Reviews, 2023)

Application of engineered heme enzymes based on myoglobin with high peroxidase activity for efficient degradation of various emerging pollutants - Guang-Rong Wu; Jia-Kun Xu; Li-Juan Sun; Ying-Fu Li; Shu-Qin Gao; Ying-Wu Lin (Journal of Environmental Chemical Engineering, 2023)

N-doped porous carbon material derived by MOFs calcined in proper oxygen atmosphere as high-performance catalyst for the low-temperature NH3-SCR - Jiexuan Zhu; Donghai Mo; Lin Tao; Jinfeng Li; Shiying Fu; Lihui Dong; Bin Li; Zhengjun Chen; Minguang Fan (Journal of Environmental Chemical Engineering, 2023)

Effects of static magnetic field-assisted freezing on physicochemical indices and bacterial communities of shrimp (Penaeus vannamei) - Qijian Zhu; Shiqian Fu; Huicheng Yang; Bangchu Lin; Yongjiang Lou; Yongyong Li (Food Bioscience, 2023)

Multifunctional cinnamaldehyde-tannic acid nano-emulsion/chitosan composite film for mushroom preservation - Hao Fu; Renpeng Huang; Jianfang Li; Zhenhao Lin; Fuxiang Wei; Baofeng Lin (Food Hydrocolloids, 2023)

Janus photothermal adsorbent for solar-powered simultaneous uranium extraction and co-production of freshwater and sea salt from seawater - Mengtao Fu; Li Han; Chen Huang; Lin Ma; Yunyou Yao; Kang Chen; Peng Sun; Haiyang Shao; Minghong Wu; Bowu Zhang; Hongjuan Ma (Chemical Engineering Journal, 2023)

Modelling of physical and mechanical properties and adiabatic temperature rise of cement-stabilized macadam - Tao Fu; Junlin Liang; Hongliu Rong; Yanliang Li; Ye Lin (Innovative Infrastructure Solutions, 2023)

CDK6 is a novel predictive and prognosis biomarker correlated with immune infiltrates in multiple human neoplasms, including small cell lung carcinoma - Guo-Sheng Li; Zhi-Guang Huang; Dong-Ming Li; Yu-Lu Tang; Jin-Hua Zheng; Lin Yang; Yue Feng; Jun-Xi Peng; Jing-Xiao Li; Yu-Xing Tang; Neng-Yong Zeng; Mei-Hua Jin; et al. (Functional & Integrative Genomics, 2023)

Establishment and characterization of a novel hilar cholangiocarcinoma cell line, CBC3T-1 - Mingzhen Bai; Ningzu Jiang; Wenkang Fu; Chongfei Huang; Liang Tian; Ningning Mi; Long Gao; Haidong Ma; Yawen Lu; Jie Cao; Chao Zhang; Ping Yue; et al. (Human Cell, 2023)
Cholangiocarcinoma (CCA) is a group of malignant heterogeneous cancer arising from the biliary tree. The tumor is characterized by insidious onset, high degree of malignancy, poor prognosis, and high recurrence rate. Immortalized cancer cell lines are the best and easiest models for in vitro cancer research. Here, we established a naturally immortalized highly tumorigenic hilar cholangiocarcinoma (hCCA) cell line, CBC3T-1. The CBC3T-1 cell line was cultured for over 60 passages. Thorough analysis showed that CBC3T-1 cells share characteristics similar to original tumor cells from patients with cholangiocarcinoma and display a stable phenotype, including features of epithelial origin, stem cell-like properties, as well as a high invasive and migratory capability and tumorigenicity in mice. Furthermore, this cell line showed the best sensitivity to paclitaxel, followed by gemcitabine. RNA sequencing and whole‑exome sequencing showed that cancer-associated pathways and somatic mutations played a dominant role in the development of CCA. We established and characterized a new hCCA cell line, CBC3T-1, which contributes to a better understanding of bile duct cancer, and can be used to study tumorigenesis and progression and the role of anticancer drugs.

Human dental pulp stem cells have comparable abilities to umbilical cord mesenchymal stem/stromal cells in regulating inflammation and ameliorating hepatic fibrosis - Peixing Chen; Yanchun Lin; Wenbo Lin; Yun Li; Ting Fu; Yuanyue Liu; Tian Guan; Man Xin; Ling Ye; Peiluan Wang; Haoyu Zeng; Kaitao Yao (Human Cell, 2023)

Differentiating environmental scenarios to establish geochemical baseline values for heavy metals in soil: A case study of Hainan Island, China - Yanling Sun; Jianzhou Yang; Kai Li; Jingjing Gong; Jianweng Gao; Zhenliang Wang; Yongwen Cai; Keqiang Zhao; Shuqi Hu; Yangang Fu; Zhuang Duan; Lujun Lin (Science of The Total Environment, 2023)

Scene-aware refinement network for unsupervised monocular depth estimation in ultra-low altitude oblique photography of UAV - Kailong Yu; Hao Li; Linjie Xing; Tao Wen; Die Fu; Yang Yang; Chengjiang Zhou; Rong Chang; Shan Zhao; Lin Xing; Haicheng Bai (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Stability evaluation of salt cavern hydrogen storage and optimization of operating parameters under high frequency injection production - De-Peng Li; Wei Liu; Pan Fu; Lin Li; Fan-Sheng Ban; Qi-Hang Li; Jin-Yang Fan; De-Yi Jiang; Zhi-Xin Zhang (Gas Science and Engineering, 2023)

Polyphenols modulate microalgae metabolism with a particular increment in lipid accumulation - Li-Gong Zou; Dan-Lin Zheng; Yi-Tong Yao; Fu-Fang Wen; Da-Wei Li; Yu-Feng Yang; Wei-Dong Yang; Srinivasan Balamurugan; Hang Fai Kwok; Hong-Ye Li (Fuel, 2023)

Arsenic exposure and lung function decline in chronic obstructive pulmonary disease patients: The mediating influence of systematic inflammation and oxidative stress - Yun-Feng Liu; Min-Min Tang; Jing Sun; Jia-Fei Li; Ya-Lin Jiang; Hui Zhao; Lin Fu (Food and Chemical Toxicology, 2023)

Planktonic microbial community and biological metabolism in a subtropical drinking water river-reservoir system - Lin Liu; Yu Xin; Shan-Bin Guang; Guo-Fu Lin; Chao-Xiang Liu; Li-Qin Zeng; Shao-Qin He; Yu-Ming Zheng; Guan-Yu Chen; Quan-Bao Zhao (Environmental Research, 2023)

Salt tide affecting algae-laden micropolluted surface water treatment and membrane performance based on BDD electro-oxidation coupled with ceramic membrane process - Xing Du; Bingxuan Li; Zhongjian Zhuang; Ke Kuang; Wei Song; Dachao Lin; Caixia Fu; Zhihong Wang (Environmental Research, 2023)

Analysis of the spatial-temporal evolution of Green and low carbon utilization efficiency of agricultural land in China and its influencing factors under the goal of carbon neutralization - Jun Fu; Rui Ding; Yu-qi Zhu; Lin-yu Du; Si-wei Shen; Li-na Peng; Jian Zou; Yu-xuan Hong; Juan Liang; Ke-xin Wang; Wen-qian Xiao (Environmental Research, 2023)

Antibiotic resistant genes profile in the surface water of subtropical drinking water river-reservoir system - Lin Liu; Shan-Bin Guang; Yu Xin; Jie Li; Guo-Fu Lin; Li-Qin Zeng; Shao-Qin He; Yu-Ming Zheng; Guan-Yu Chen; Quan-Bao Zhao (Environmental Pollution, 2023)

Laccase-triggered one-step fabrication of positively charged phenolic acid-amine networks for nanofiltration - Ping Fu; Di Zhou; Wan-Long Li; Wan-Ting Lin; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2023)

Immune-microenvironment modulatory polyurethane-hyaluronic acid hybrid hydrogel scaffolds for diabetic wound treatment - Yuan Feng; Kecen Xiao; Jinlin Chen; Jingjing Lin; Yuanyuan He; Xueling He; Fuyi Cheng; Zhen Li; Jiehua Li; Feng Luo; Hong Tan; Qiang Fu (Carbohydrate Polymers, 2023)

Flooding dominates soil microbial carbon and phosphorus limitations in Poyang Lake wetland, China - Xingyun Huang; Yaxuan Li; Huiyin Lin; Xiuting Wen; Jie Liu; Zhifen Yuan; Chun Fu; Bofu Zheng; Leiqiang Gong; Huiying Zhan; Yu Ni; Yang Hu; et al. (CATENA, 2023)

Magmatic fluids responsible for lode gold mineralization in the giant Linglong deposit at Jiaodong, North China Craton: Constraints from LiO isotopes - Shao-Rui Zhao; Zhan-Ke Li; Zu-Wei Lin; Jian-Feng Gao; Hua-Shan Sun; Martin Yan Hei Li; Xin-Fu Zhao (Chemical Geology, 2023)

The NOx-O3 photochemical reactive air pollutant dispersion around an isolated building—the role of turbulence model and building aspect ratio - Yunfei Fu; Xisheng Lin; Lu Li; Mengyuan Chu; Chun-Ho Liu; Zengshun Chen; Cruz Y. Li; K.T. Tse (Building and Environment, 2023)

Transcriptome Analysis Revealed the Differential Molecular Response Mechanisms of Roots, Stems, and Leaves in Mung Bean to Cadmium Stress - Ping-min Wu; Yan Leng; Shi-Weng Li; Yu-Lin Wang; Fu-Jun Qiao (Journal of Plant Growth Regulation, 2023)

Leaf hydraulic distance is a good predictor of growth response to climate aridity within and across conifer species in a Taiga ecosystem - Xingyue Li; Dayong Fan; Zhengxiao Liu; Zengjuan Fu; Changqing Gan; Zeyu Lin; Chengyang Xu; Han Sun; Xiangping Wang (Agricultural and Forest Meteorology, 2023)

The Effect of Water Spinach on the Water Quality, Antioxidant System, Non-Specific Immune Response, Growth Performance, and Carbon Balance in Red Tilapia Production - Yuan-Yuan Luo; Xian-Can Chen; Rui-Lin Xie; Zhuo-Hao Ruan; Zhi-Qiang Lu; Liang-Sen Jiang; Yi-Fu Li; Wen-Sheng Liu (Fishes, 2023)
In this study, the compound aquaculture model of red tilapia (O. mossambicus albina × O. urolepis hornorum) and water spinach (Ipomoea aquatica) was used to investigate the effect of water spinach rafts on the water quality, antioxidant system, non-specific immune response, and growth performance of red tilapia and the carbon balance of payments. Red tilapia is characterized by its high adaptability to different production environments and food sources, as one of the most productive fish in aquaculture, and is well accepted in the market due to its nutritional and organoleptic characteristics. The experiment lasted for nine weeks and included two systems: the red tilapia-water spinach raft aquaponics (AP) system with 10% cover ratio with water spinach floating beds, and the aquatic monoculture (AM) system with only red tilapia. The total phosphorus (TP), total nitrogen (TN), and nitrate nitrogen (NO−3-N) in the AM were higher than those in AP from the fifth to ninth week. On the second, third, fifth, and sixth weeks, the ammonia nitrogen (NH4+-N), in the AM was higher than those in the AP. From the seventh week, the pH of the AM was significantly lower than the AP, while the nitrite nitrogen (NO−2-N) was significantly higher than the AP. The water quality index of the AP was better than that of the AM, indicating that water spinach can remove the nutrients from aquaculture water bodies. The average daily gain and specific growth rate (SGR) of fish in AP were higher than those in the AM. The acid phosphatase (ACP), alkaline phosphatase (AKP), and catalase (CAT) activities in the hepatopancreas of red tilapia in the AP were also significantly higher than those in the AM, while the malondialdehyde (MDA) in the AP was lower than the AM. The serum ACP and CAT of red tilapia in the AP were also higher than those in the AM, while the MDA of fish in the AP was lower than the AM. The results showed that both the experimental group and the control group were carbon sources and released greenhouse gases into the atmosphere, but the total carbon emissions of the red tilapia and the water spinach symbiotic system in the experimental group was significantly lower than that of the control group (p

Coupling the digital twin technology and life cycle assessment: Carbon dioxide emissions from polysilicon production - Shengqiang Yang; Zhiqiang Yu; Wenhui Ma; Lin Ma; Chaochun Li; Ling Fu; Ming Li; Zewen Zhao; Yuchen Yang (Sustainable Production and Consumption, 2023)

Carboxyl-containing components delineation via feature-based molecular networking: A key to processing conditions of fermented soybean - Yuye Gao; Yu Fu; Na Li; Yuetong Jiang; Xiaojing Liu; Congcong Gao; Lishuang Wang; Jian-Lin Wu; Tingting Zhou (Food Chemistry, 2023)

Pectin-nanolignin composite films with water resistance, UV resistance, and antibacterial activity - Shikai Zhang; Xinxin Cheng; Quanbin Fu; Yijing Li; Peng Wu; Yiheng Qiao; Jianfeng Yan; Lin Si; Geoffrey I.N. Waterhouse; Houshen Li; Shiyun Ai (Food Hydrocolloids, 2023)

Association of greenness surrounding school with aggression among adolescents: A multi-site study in China - Yi Zhang; Yanqi Li; Xinyi Xie; Xiaoyi Lin; Mengxin Huang; Huihang Fu; Weiju Zhou; John S. Ji; Yizhen Yu; Jie Tang (Environmental Research, 2023)

Impact of COVID-19 pandemic on profiles of antibiotic-resistant genes and bacteria in hospital wastewater - Liang Zhao; Ziquan Lv; Liangqiang Lin; Xiaowei Li; Jian Xu; Suli Huang; Yuhua Chen; Yulin Fu; Changfeng Peng; Tingting Cao; Yuebin Ke; Xi Xia (Environmental Pollution, 2023)

A zinc-octacarboxylate MOF with an unusual (6, 8)-connected ocu topology for high-capacity adsorptive separation of C8 alkylaromatics - Xiuping Deng; Maojun Deng; Yu-Lin Li; Zewei Liu; Tian-Fu Liu; Xin Chen; Shuhan Cai; Biying Liu; Jiesen Li; Daofei Lv; Jing Li; Wenbing Yuan (Chemical Engineering Journal, 2023)

Advanced electrooxidation of florfenicol using 3D printed Nb2O5/Ti electrodes: Degradation efficiency, dehalogenation performance, and toxicity reduction - Yun-fei Zhang; Jia-le Gao; Shen-gui Chen; Lei Li; Jian-hui Xu; Dan Li; Yu-feng Liu; Xin Quan; Xin Fu; Ya-zi Xie; Jing-nan Wu; Dan-ying Lin; et al. (Chemical Engineering Journal, 2023)

A novel starch-based ethanol gel with contact-killing bacteria to cut off contact transmission of bacteria - Fu-Xiang Wei; Tian-Rui Zhou; Shao-Wei Zhong; Yong-Fu Deng; Chuan-Hui Xu; Li-Hua Fu; Bao-Feng Lin (Chemical Engineering Journal, 2023)

Targeting mitochondrial dynamics by AZD5363 in triple-negative breast cancer MDA-MB-231 cell–derived spheres - Yingqiang Fu; Wei Dong; Yuting Xu; Lin Li; Xin Yu; Yuheng Pang; Liujia Chan; Yuhan Deng; Cheng Qian (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Breast cancer stem cells (BCSCs) have been suggested to contribute to chemotherapeutic resistance and disease relapse in breast cancer. Thus, BCSCs represent a promising target in developing novel breast cancer treatment strategies. Mitochondrial dynamics in BCSCs were recently highlighted as an available approach for targeting BCSCs. In this study, a three-dimensional (3D) cultured breast cancer stem cell spheres model was constructed. Mitochondrial dynamics and functions were analyzed by flow cytometry and confocal microscopy. We have demonstrated that the protein levels of FIS 1 and Mitofusin 1 were significantly increased in BCSCs. Moreover, Capivasertib (AZD5363) administration could suppress Mitofusin1 expression in BCSCs. Our use of MitoTracker Orange and annexin V double-staining assay suggested that AZD5363 could induce apoptosis in BCSCs. The sensitivity of stem cell spheres to doxorubicin was investigated by CCK8 assay, and our results indicated that AZD5363 could re-sensitize BCSCs to Doxo. Flow cytometry analysis identified doxo-induced CD44 and CD133 expression in BCSCs could be suppressed by AZD5363. In combination with AZD536, doxo-induced apoptosis in the BCSCs was significantly increased. In conclusion, our study explored, for the first time, that AZD5363 could target mitochondrial dynamics in 3D cultured stem cell spheres (BCSCs) by regulating Mitofusin.

USP14 Regulates ATF2/PIK3CD Axis to Promote Microvascular Endothelial Cell Proliferation, Migration, and Angiogenesis in Diabetic Retinopathy - Fu-Tao He; Xiao-Lin Fu; Mo-Han Li; Chun-Yan Fu; Jian-Zhi Chen (Biochemical Genetics, 2023)

Accelerated verification method for the reliability of the motor drive mechanism of the corn precision seed-metering device - Changkai Wen; Jing Zhang; Kan Zheng; Hanqing Li; Lin Ling; Zhijun Meng; Weiqiang Fu; Bingxin Yan (Computers and Electronics in Agriculture, 2023)

Transcriptome analysis revealed water balance controlled by ZxOSCA1.1 and lateral root development are crucial strategies for Zygophyllum xanthoxylon - Gaofei Fu; Yulu Ma; Lin Li; Yue Wang; Shengdan Wu; Haiyang Guo; Linjing Zhang (South African Journal of Botany, 2023)

Optical properties and molecular composition of wintertime atmospheric water-soluble organic carbon in different coastal cities of eastern China - Haibiao Chen; Caiqing Yan; Qinglong Fu; Xinfeng Wang; Jiao Tang; Bin Jiang; Honglei Sun; Tiancheng Luan; Qiaoyun Yang; Qianbiao Zhao; Jun Li; Gan Zhang; et al. (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Skeleton engineering of rigid covalent organic frameworks to alter the number of binding sites for improved radionuclide extraction - Xiangbin Lin; Weiwen Xin; Shusen Chen; Yan Song; Linsen Yang; Yongchao Qian; Lin Fu; Yanglansen Cui; Xiaofeng He; Tinyang Li; Zhehua Zhang; Yadong Wu; et al. (Journal of Hazardous Materials, 2023)

The occurrence of "yellowing" phenomenon and its main driving factors after the remediation of chromium (Cr)-contaminated soils: A literature review - Hao-Kai Li; Da-Mao Xu; Jun-Xian Wang; Ze-Lin Xu; Rong-Bing Fu (Journal of Hazardous Materials, 2023)

A novel bacteriocin RSQ01 with antibacterial activity and its application and metabolomic mechanism in milk preservation - Yan-Mei Zhang; Lin-Yu Yang; Jian-Ping Ying; Chao-Min Fu; Gang Wu; Xiao-Ran Li; Qi-Lin Zhang (Food Control, 2023)

Clinical poisoning events involving yunaconitine may be highly correlated with metabolism-based interactions: A critical role of CYP3A4 - Xiaocui Li; Yu Fu; Huawei Qiu; Xueyu Xu; Tingting Lin; Weiqing Hou; Weiying Chen; Rong Zhang; Zhongqiu Liu; Lijun Zhu (Food and Chemical Toxicology, 2023)

Maternal di-(2-ethylhexyl) phthalate exposure elicits offspring IFN-λ upregulation: Insights from birth cohort, murine model, and in vitro mechanistic analysis - Fu-Chen Kuo; Mei-Lan Tsai; Shin-Ting Wu; Sih-Syuan Li; Chia-Fang Wu; Shu-Lin Wang; Michael W.Y. Chan; Jau-Ling Suen; Ming-Tsang Wu; Chih-Hsing Hung (Food and Chemical Toxicology, 2023)

Resource utilization of ultrasonic carbonated MSWI fly ash as cement aggregates: Compressive strength, heavy metal immobilization, and environmental-economic analysis - Jie Chen; Wanchen Zhu; Yizhe Shen; Congkai Fu; Minjie Li; Xiaoqing Lin; Xiaodong Li; Jianhua Yan (Chemical Engineering Journal, 2023)

Performance and mechanism of calcium peroxide reducing H2S production from sludge anaerobic fermentation - Yunhao Xu; Qizi Fu; Wenming Wang; Fan Yang; Xuemei Li; Fengming Song; Yanguang Qing; Ziqi Lin; Weiqi Long; Dongbo Wang (Chemical Engineering Journal, 2023)

Pan-cancer evidence of prognosis, immune infiltration, and immunotherapy efficacy for annexin family using multi-omics data - Chong Shen; Siyang Zhang; Zhe Zhang; Shaobo Yang; Yu Zhang; Yuda Lin; Chong Fu; Zhi Li; Zhouliang Wu; Zejin Wang; Zhuolun Li; Jian Guo; et al. (Functional & Integrative Genomics, 2023)

Driving forces and their interactions of soil erosion in soil and water conservation regionalization at the county scale with a high cultivation rate - Bang-lin Luo; Jiang-wen Li; Chun-ming Gong; Shou-qin Zhong; Chao-fu Wei (Journal of Mountain Science, 2023)

A novel electrochemical aptasensor based on eco-friendly synthesized titanium dioxide nanosheets and polyethyleneimine grafted reduced graphene oxide for ultrasensitive and selective detection of ciprofloxacin - Yangguang Zhu; Xiufen Li; Mengfan Wu; Mingjiao Shi; Qichen Tian; Li Fu; Hsu-Sheng Tsai; Wan-Feng Xie; Guosong Lai; Gang Wang; Nan Jiang; Chen Ye; et al. (Analytica Chimica Acta, 2023)

Seasonal–interannual–decadal variations of sea level in the South China Sea and connections with the tropical–subtropical Pacific - Juan Li; Wei Tan; Wenjin Sun; Lina Yang; Lei Lin; Qingjun Fu (International Journal of Climatology, 2023)
Different timescale contributions to the sea‐level variation in the South China Sea (SCS) are evaluated in this paper. On seasonal timescale, the large variance of the sea‐level anomaly (SLA) could account for more than 70% of the monthly sea‐level variation in the western shallow continental shelf and the area of Luzon cold eddy. Besides, the seasonal explained variance percentage (skill) has 2 weak centres (50%–70%) off eastern Vietnam, which is related to the summertime eddy pair in the SCS. On interannual‐to‐decadal (low‐frequency) timescale, the skill has two large‐value regions (Zone A and Zone B). Zone A is characterized by double centres off eastern Vietnam, but the meridional position of the double centres is farther north than that of the eddy pair. The skill in Zone A is in the range of 35%–55%, and about 50%–70% of the low‐frequency variation comes from the steric effect. Zone B is off the west coast of the Philippines. The skill in Zone B increases southward, and it is dominated by the wind‐induced dynamic process which is attributed to the remote Rossby wave from the tropical Pacific. Based on the S‐EOF analysis, the SEOF‐1 mode mainly portrays the decadal variation of the SLA, while the SEOF‐2 mode reflects the interannual variation of the SLA. In Zone B, almost all of the low‐frequency variation could be attributed to ENSO and PDO, especially to PDO which has a larger contribution. However, the double centres in Zone A are governed by the SCS summer monsoon, instead of ENSO and PDO.

Host-specific bacterial communities associated with six cold-seep sponge species in the South China Sea - Yan Wang; Lin Gong; Zhaoming Gao; Yong Wang; Feng Zhao; Lulu Fu; Xinzheng Li (Frontiers in Marine Science, 2023)
The cold-seep sponge holobionts are attracting growing attention in recent years. In this study, we utilized 16S rRNA amplicons to characterize the bacterial communities of six deep-sea sponge species found in sponge grounds at the Formosa Ridge cold seep in the South China Sea. Bacterial communities in these geographically proximal sponge species are dominated by Proteobacteria (mainly Gammaproteobacteria and Alphaproteobacteria) but exhibit distinct diversity and compositions among communities. Further analysis revealed that the SUP05 clade (Thioglobaceae) dominated most of the sponge samples. Meanwhile, phylogenetic analysis showed that the six sponge species harbored diverse SUP05 OTU phylotypes, indicating significant divergence within this clade. Additionally, operational taxonomic units (OTUs) of the family Methylomonadaceae, another abundant group in these sponges, displayed a significant genetic distance both from each other and from known species. Our findings support the hypothesis of the host-species specificity of sponge-associated bacterial communities, a widely accepted concept in shallow-water and other deep-sea sponges. The presence of dominant functional microbes, such as sulfur- and methanol-oxidizing bacteria, suggests their crucial role as chemosynthetic symbionts in facilitating the niche adaption of sponge hosts to the cold seep ecosystem. In conclusion, our study reveals the diverse and novel bacterial communities in deep-sea sponges from cold seep environments, contributing new knowledge to the host-species specificity of bacterial communities within sponges and highlighting the potential significance of functional microbes in cold seep ecosystems with dynamic energy supplies.

Two new bibenzyls from Pleione grandiflora (Rolfe) Rolfe and their antioxidant activity - Wei Li; Jia-Rui Fu; Li-Jun Zheng; Lin Ni; Jun-Qing Liu; Jun-Wen Zhai; Zhuang Zhou; Sha-Sha Wu (Natural Product Research, 2023)

Effect of copper ions on transformation of organic sulfur in cationic exchange resins in Li2CO3–Na2CO3–K2CO3 molten-salt system - Zhi Zhang; Yun Xue; Yue-Lin Wang; Wen-Da Xu; Yong-De Yan; Yang-Hai Zheng; Fu-Qiu Ma; Guo-Qiang Li (Chemosphere, 2023)

Dihydromyricetin attenuates cisplatin-induced acute kidney injury by reducing oxidative stress, inflammation and ferroptosis - Zheming Xu; Minjing Zhang; Wenwen Wang; Suhan Zhou; Minghua Yu; Xingyu Qiu; Shan Jiang; Xiaohua Wang; Chun Tang; Shuijie Li; Chih-Hong Wang; Runzhi Zhu; et al. (Toxicology and Applied Pharmacology, 2023)

miR-665 overexpression inhibits the apoptosis of luteal cells in small ruminants suppressing HPGDS - Heng Yang; Lin Fu; Licai Li; Dezhi Zhang; Qianyong Li; Peng Zhou (Theriogenology, 2023)

Relationship between light absorption properties of black carbon and aerosol origin at a background coastal site - Haiyan Li; Chengfeng Liu; Hao Li; Guochen Wang; Xiaofei Qin; Jia Chen; Yanfen Lin; Juntao Huo; Qingyan Fu; Yusen Duan; Congrui Deng; Kan Huang (Science of The Total Environment, 2023)

Enhanced Hg(II) efficient and selective removal by post-functional Ti-MOF with 2，5 thiophene dicarboxylic acid - Jing Li; Guo Lin; Biao Zeng; Likang Fu; Zeying Wang; Shixing Wang; Tu Hu; Libo Zhang (Process Safety and Environmental Protection, 2023)

Metagenome-based analysis of carbon-fixing microorganisms and their carbon-fixing pathways in deep-sea sediments of the southwestern Indian Ocean - Xiao-Lan Yue; Lin Xu; Li Cui; Ge-Yi Fu; Xue-Wei Xu (Marine Genomics, 2023)

Genomic analysis of Marinomonas algicola SM1966T reveals its role in marine sulfur cycling - Min Zhang; Xiao-Di Wang; Yue Lin; Shu-Yan Wang; Shan Zhang; Jin Cheng; Mei-Ling Sun; Peng Wang; Hui-Hui Fu; Chun-Yang Li; Nan Zhang (Marine Genomics, 2023)

A sustainable emulsion for separation and Raman identification of microplastics and nanoplastics - Yinan Li; Jianxin Fu; Lin Peng; Xun Sun; Guoqing Wang; Yunqing Wang; Lingxin Chen (Chemical Engineering Journal, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

GS6.1 controls kernel size and plant architecture in rice - Hongyuan Zhao; Yu Fu; Guiquan Zhang; Yingqin Luo; Weifeng Yang; Xiaoya Liang; Lin Yin; Zhenwu Zheng; Yijun Wang; Zhan Li; Haitao Zhu; Jinyan Huang; et al. (Planta, 2023)

The dynamics of the equatorial Atlantic upwelling seasonal cycle under global warming and its potential impact on Pacific ENSO - Li-Chiao Wang; Thi Lan Dao; Yong-Fu Lin; Jia-Yuh Yu (Climate Dynamics, 2023)

Nitrogen species and microbial community coevolution along groundwater flowpath in the southwest of Poyang Lake area, China - Xianglong Chen; Guangcai Wang; Yizhi Sheng; Fu Liao; Hairu Mao; Bo Li; Hongyu Zhang; Zhiyuan Qiao; Jiahui He; Yingxue Liu; Yilun Lin; Ying Yang (Chemosphere, 2023)

Magnetic anaerobic granular sludge for sequestration and immobilization of Pb - Rui Zhou; Han Li; Chengshuai Liu; Yizhang Liu; Jyh-Fu Lee; Yu-Jung Lin; Zhang Yan; Zhangyi Xu; Xiaoyun Yi; Chunhua Feng (Water Research, 2023)

Long-term effects of rewetting and drought on GPP in a temperate peatland based on satellite remote sensing data - Yinying Zhou; Torsten Sachs; Zhan Li; Yuwen Pang; Junfeng Xu; Aram Kalhori; Christian Wille; Xiaoxue Peng; Xianhao Fu; Yanfei Wu; Lin Wu (Science of The Total Environment, 2023)

Bifunctional reduced graphene oxide/polyelectrolyte/NiFe layered double hydroxide composites for efficient catalyzed dephosphorylation and 4-nitrophenol reduction - Zijun Xie; Bo Sun; Hongying Lin; Meng Fu; Yi Zhang; Zequn Ma; Xiangming Li (Journal of Water Process Engineering, 2023)

Joint semantic–geometric learning for polygonal building segmentation from high-resolution remote sensing images - Weijia Li; Wenqian Zhao; Jinhua Yu; Juepeng Zheng; Conghui He; Haohuan Fu; Dahua Lin (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Modulating the interfacial built-in electric field in oxygen vacancies-enriched Ru/MxOy@C (M = V, Nb, Ta) ordered macroporous heterojunctions for electrocatalytic hydrogen production - Xiao Hui Chen; Hong Chuan Fu; Xiao Lin Li; Ting Li; Qing Zhang; Zi Qing Li; Yuan Hao Luo; Jing Lei Lei; Nian Bing Li; Hong Qun Luo (Chemical Engineering Journal, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

A novel method of calcium dissolution-crystallization-polymerization for stabilization/solidification of MSWI fly ash - Jie Chen; Wanchen Zhu; Yizhe Shen; Congkai Fu; Minjie Li; Xiaoqing Lin; Xiaodong Li; Jianhua Yan (Chemosphere, 2023)

Ca–La layered double hydroxide (LDH) for selective and efficient removal of phosphate from wastewater - Yuhang Cao; Xuewei Wu; Biqing Li; Xia Tang; Xueran Lin; Pengfei Li; Hang Chen; Fu Huang; Chaohai Wei; Jian Wei; Guanglei Qiu (Chemosphere, 2023)

Embryonic thermosensitivity and hatchling morphology differ among three species of crocodilians farm-raised in China - Dan Liu; Jia-Tian Chen; Jung-Chien Tsai; Cheng-Wang Li; Chi-Xian Lin; Yan-Fu Qu; Yu Du; Xiang Ji (Aquaculture, 2023)

Relating critical and limiting fluxes to metastable and long-term stable fluxes in colloidal membrane filtration through collision-attachment theory - Junxia Liu; Wei Fu; Xuri Yu; Haiyan Yang; Dongsheng Zhao; Zhihong Wang; Lin Wang; Xianhui Li; Chuyang Y. Tang (Water Research, 2023)

PBX1-promoted SFRP4 transcription inhibits cell proliferation and epithelial-mesenchymal transition in endometrial carcinoma - Liwen Guo; Huihua Chen; Jinguo Chen; Chen Gao; Xianguo Fu; Sujuan Zhou; Wenjuan Wu; Taoping Li; Jingfang Lin; Tailai Yang; Zichun Chen; Luoyuan Cao (Tissue and Cell, 2023)

Long-term cadmium exposure induces chronic obstructive pulmonary disease-like lung lesions in a mouse model - Wen-Jing Wang; Kun Peng; Xue Lu; Yan-Yan Zhu; Zhao Li; Qing-Hua Qian; Ya-Xin Yao; Lin Fu; Yan Wang; Yi-Chao Huang; Hui Zhao; Hua Wang; et al. (Science of The Total Environment, 2023)

An overlooked soil carbon pool in vegetated coastal ecosystems: National-scale assessment of soil organic carbon stocks in coastal shelter forests of China - Yuan Li; Chuancheng Fu; Weiqi Wang; Lin Zeng; Chen Tu; Yongming Luo (Science of The Total Environment, 2023)

Two generations of crustal anatexis in association with two-stage exhumation of ultrahigh-pressure metamorphic rocks in the Dabie orogen - Qiong-Xia Xia; Meng Yu; Er-Lin Zhu; Ren-Xu Chen; Wan-Cai Li; Yong-Fei Zheng; Zi-Fu Zhao; Zhao-Ya Li (Lithos, 2023)

Fe(VI) activation system mediated by a solar-driven TiO2 nanotubes electrode for CLQ degradation: Performances, mechanisms and pathways - Jinzhe Li; Chuyun Fu; Qiufeng Lin; Tao Zeng; Da Wang; Xinwen Huang; Shuang Song; Cong Li; Feilong Dong (Journal of Hazardous Materials, 2023)

Evaluation of modified bitumen properties using waste plastic pyrolysis wax as warm mix additives - Chuanqiang Li; Haobo Wang; Chaoliang Fu; Shaosong Shi; Guannan Li; Qizheng Liu; Dan Zhou; Lin Jiang; Ying Cheng (Journal of Cleaner Production, 2023)

Preparation of nitrogen-containing compounds and nitrogen-doped biochar via nitrogen-rich pyrolysis coupled with ammonia source impregnation - Donghua Li; Meihua Fu; Tao Pei; Yi Lu; Can Liu; Xu Lin; Defa Hou; Hao Sun; Cuiping Luo; Zhifeng Zheng; Yunwu Zheng (Journal of Environmental Chemical Engineering, 2023)

Rational design of one inorganic-organic hybrid Z-scheme heterojunction for high-performance photocatalytic water splitting - Cun-biao Lin; Fu-li Sun; Jun Wen; Wen-xian Chen; Gui-lin Zhuang (Fuel, 2023)

Lanthanide bimetallic MOF-based fluorescent sensor for sensitive and visual detection of sulfamerazine and malachite - Xiaoyue Yue; Long Fu; Yan Li; Sheng Xu; Xin Lin; Yanhong Bai (Food Chemistry, 2023)

Gestational cadmium exposure disrupts fetal liver development via repressing estrogen biosynthesis in placental trophoblasts - Yi-Ting Fu; Jin Zhang; Wei-Bo Liu; Yu-Feng Zhang; Shuang Zhang; Lu-Lu Tan; Qing Lin; Kong-Wen Ou-Yang; Yong-Wei Xiong; Wei Chang; Hao Li; Jun-Ying Yu; et al. (Food and Chemical Toxicology, 2023)

High entropy promoted active site in layered double hydroxide for ultra-stable oxygen evolution reaction electrocatalyst - Thi Xuyen Nguyen; Chia-Chien Tsai; Van Thanh Nguyen; Yan-Jia Huang; Yen-Hsun Su; Siang-Yun Li; Rui-Kun Xie; Yu-Jung Lin; Jyh-Fu Lee; Jyh-Ming Ting (Chemical Engineering Journal, 2023)

Regulation of the autochthonous microbial community in excess sludge for the bioconversion of carbon dioxide to acetate without exogenic hydrogen - Zhiwen Lin; Jinan Tan; Zhihan Xiong; Zisen Fu; Jing Chen; Tonghui Xie; Jia Zheng; Yongkui Zhang; Panyu Li (Bioresource Technology, 2023)

Genome-wide Association Study of Root Hair Length in Maize - Li Xuhui; Lu Siqi; Chen Weiwei; Zhu Hang; Lin Huanzhang; Fu Danwen; Fan Lina; Fang Junteng; Hu Yuanqiang; Zhang Xiangbo; Chang Hailong; Qi Yongwen (Tropical Plant Biology, 2023)

Histone modification landscape and the key significance of H3K27me3 in myocardial ischaemia/reperfusion injury - Le Ni; Bowen Lin; Yanping Zhang; Lingjie Hu; Jianghua Lin; Fengmei Fu; Meiting Shen; Can Li; Lei Chen; Jian Yang; Dan Shi; Yi-Han Chen (Science China Life Sciences, 2023)

Three-dimensional quantitative structural-activity relationship and molecular dynamics study of multivariate substituted 4-oxyquinazoline HDAC6 inhibitors - Linan Zhao; Le Fu; Guangping Li; Yongxin Yu; Juan Wang; Haoran Liang; Mao Shu; Zhihua Lin; Yuanqiang Wang (Molecular Diversity, 2023)

Countering beta-cypermethrin: partitioning roles of the insect gut and its bacteria - Li Bai; Xiao-Lin Cai; Man-Yu Li; Fu-Xiao Wang; Chuan-Shan Zou; Jun-Sheng Zhang; Ming-Yu Xie; Feng-Hui Qi; Tian-Zhong Jing (Journal of Pest Science, 2023)

Deletion of the cheZ gene results in the loss of swimming ability and the decrease of adhesion ability to Caco-2 cells in Escherichia coli Nissle 1917 - Bingming Ou; Haihui Lv; Hua Ge; Dexiang Fu; Xin Lin; Saiqiao Huang; Xiaojie Chen; Yufu Liu; Sainan Li; Wenhua Liu; Lihua Huang; Ying Yang; et al. (Folia Microbiologica, 2023)

Identification and Pathogen Stimulation Patterns of Neuronal Nitric Oxide Synthase (nNOS) in Black Rockfish (Sebastes schlegelii) - Xu Yan; Ningning Wang; Min Cao; Chao Li; Ning Yang; Ting Xue; Qiang Fu; Lin Song (Journal of Ocean University of China, 2023)

Analysis of the evolutionary game between maritime regulators and carriers under the discharge of ballast nuclear wastewater from ships - Jun Jiang; Zhiming Ma; Li Lin; Yiping Yuan; Xiaona Fu (Ocean & Coastal Management, 2023)

Tannic acid exerts antifungal activity in vitro and in vivo against Alternaria alternata causing postharvest rot on apple fruit - Haixia Wang; Lin Fu; Chunli Li; Xinlu Zhang; Kpadonou Essedolo Narcisse; Haishi Qi; Chuanyu Han; Xiangyu Wang; Hongbin Ma; Chunyu Zhu; Fangliang Zheng (Physiological and Molecular Plant Pathology, 2023)

Insight into copper-cerium catalysts with different Cu valence states for CO-SCR and in-situ DRIFTS study on reaction mechanism - Jinfeng Li; Jiexuan Zhu; Shiying Fu; Lin Tao; Bingxian Chu; Qiuju Qin; Jingkai Wang; Bin Li; Lihui Dong (Fuel, 2023)

Mechanisms of acidic electrolyzed water killing bacteria - Fan Wang; Yan-Ning Lin; Yu Xu; Yong-Bing Ba; Zhao-Huan Zhang; Li Zhao; Wing Lam; Fu-Lan Guan; Yong Zhao; Chang-Hua Xu (Food Control, 2023)

Taurine reduces apoptosis mediated by endoplasmic reticulum stress in islet β-cells induced by high-fat and -glucose diets - Dongdong Zhao; Xiaozhou Zhang; Yongxin Bian; Lu Meng; Yutong Wu; Yidi Ma; Chen Li; Jingjing Wang; Zizheng Fu; Jingyuan Dai; Deqi Yin; Shumei Lin; et al. (Food and Chemical Toxicology, 2023)

An injectable and rapidly degraded carboxymethyl chitosan/polyethylene glycol hydrogel for postoperative antiadhesion - Meiyue Wang; Sen Lin; Mengzhe Liu; Jing Jiao; Hongyan Mi; Jingjing Sun; Yiming Liu; Ruiying Guo; Sirui Liu; Haojie Fu; Yanyu Yang; Rui Li (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Paraburkholderia sp. GD17 improves tomato plant growth and resistance to Botrytis cinerea-induced disease - Anqi Gu; Danni Zhao; Huaqiang Liu; Wei Fu; Guangzhe Li; Lin Hao (Plant and Soil, 2023)

Chemiluminescence Immunoassay Method of Urinary Liver Fatty-acid-binding Protein as a Promising Candidate for Kidney Disease - Lisong Niu; Lanya Li; Jinshan Li; Zhitian Chen; Jiayuan Lin; Bo Zhang; Xiaoling Fu (Journal of Fluorescence, 2023)

Triassic granitoids in the East Kunlun Orogenic Belt, Northwestern China: magmatic source and implications for geodynamic evolution - Zhi-He Xu; Wei Xin; Xiao-Dong Zhou; Qing-Lin Xu; Fu-Wen Li; Zhao-Jun Song (International Geology Review, 2023)

A novel autotrophic denitrification and nitrification integrated constructed wetland process for marine aquaculture wastewater treatment - Lin Zhao; Guiping Fu; Weicheng Pang; Xiaxin Li; Chao Pan; Zhangli Hu (Chemosphere, 2023)

The occurrence, formation and transformation of disinfection byproducts in the water distribution system: A review - Feilong Dong; Jiani Zhu; Jinzhe Li; Chuyun Fu; Guilin He; Qiufeng Lin; Cong Li; Shuang Song (Science of The Total Environment, 2023)

Accelerated carbonation of ball-milling modified MSWI fly ash: Migration and stabilization of heavy metals - Jie Chen; Yizhe Shen; Zhiliang Chen; Congkai Fu; Minjie Li; Tieying Mao; Ruiyang Xu; Xiaoqing Lin; Xiaodong Li; Jianhua Yan (Journal of Environmental Chemical Engineering, 2023)

Flexible, sensitive and rapid humidity-responsive sensor based on rubber/aldehyde-modified sodium carboxymethyl starch for human respiratory detection - Zhongjie Zheng; Li Yang; Yunpeng Yang; Luji Li; Baofeng Lin; Lihua Fu; Chuanhui Xu (Carbohydrate Polymers, 2023)

Late diagenetic alteration of carbonate evidenced by carbonate-deficient siliciclastic laminae - Xubin Wang; Lin Dong; Tong Li; Ziyi Wang; Changhu Zhang; Zhijun Jin; Jinhua Fu; Rukai Zhu; Kun Ling; Tianyu Wang (Chemical Geology, 2023)

Cesium exposure and pulmonary function decline: Potential mediating role of oxidative stress in chronic obstructive pulmonary disease patients - Min-Min Tang; Xue-Feng Hou; Jing Sun; Jia-Yi Cheng; You-Peng Deng; Meng-Die Li; Ling Liu; Dong-Xu Hua; Jin Yang; Ya-Lin Jiang; Lin Fu; Hui Zhao (Atmospheric Pollution Research, 2023)

Composition, Distribution, and Source Apportionment of Organochlorine Pesticides (OCPs) in Soil of a Chemical Industrial Park and its Surrounding in the Northeast of Qinghai-Tibet Plateau - Xiaojun Li; Lixia Cao; Xin Lin; Wanlong Fu; Zongqiang Gong; Xiangfeng Zeng; Huajun Fang; Zhiheng Li (Water, Air, & Soil Pollution, 2023)

The cell cycle arrested results in the premature advent of apical leaflets development cessation in Zygophyllum xanthoxylon - Gaofei Fu; Jing Li; Lin Li; Shengdan Wu; Yanbo Wu; Yue Wang; Cui Liu; Linjing Zhang (Trees, 2023)

The diversity of mycorrhiza‐associated fungi and trees shapes subtropical mountain forest ecosystem functioning - Ya‐Huang Luo; Liang‐Liang Ma; Sebastian Seibold; Marc W. Cadotte; Kevin S. Burgess; Shao‐Lin Tan; Lin‐Jiang Ye; Wei Zheng; Jia‐Yun Zou; Zhi‐Fa Chen; De‐Tuan Liu; Guang‐Fu Zhu; et al. (Journal of Biogeography, 2023)
Aim Mycorrhiza play key roles for ecosystem structure and functioning in forests. However, how different mycorrhizal types influence mountain forest biodiversity–ecosystem functioning (BEF) relationships are largely unknown. We evaluate how the diversity of distinct mycorrhiza‐associated fungi and trees shapes forest carbon storage along elevational gradients. Location Gaoligong Mountains within Hengduan Mountains, Southwest China. Taxon Seed plants and mycorrhizal fungi. Methods We used the data from 31 subtropical forest plots along elevational gradients on two aspects (east and west) of the mountain. We quantified species richness of trees and symbiotic fungi and assigned both to their mycorrhizal type (arbuscular mycorrhiza [AM], ectomycorrhiza [EcM] and ericoid mycorrhiza [ErM]). We then examined the diversity effects of mycorrhiza‐associated fungi and trees on above‐ground carbon stored in trees and organic carbon stored in soils. Results Species richness was highest for AM trees (79.5%), followed by ErM trees (13.4%) and then EcM trees (7.1%). Species richness of AM‐associated trees and fungi decreased with increasing elevation, while ErM‐associated trees and fungi showed an opposite trend. EcM‐associated diversity followed a hump‐shaped relationship with elevation. Positive relationships between diversity and above‐ground carbon were detected in all three mycorrhizal associations, but despite low species number, canopy‐dominating EcM trees comprised 64.4% of the amount of above‐ground carbon. Furthermore, community‐weighted means of height exhibited positive correlations with forest above‐ground carbon, indicating that positive selection effects occur. Soil organic carbon was positively related to EcM‐associated fungi diversity, above‐ground carbon mass and soil nitrogen availability, with the latter having strongest direct effects. Main Conclusions The distributions of forest biodiversity and carbon storage can be modulated by distinct mycorrhizal fungi and trees. Moreover, future global changes (e.g. climate warming, intensifying nitrogen deposition) could alter the mycorrhizal‐mediated BEF relationships in mountain forests.

Vocalization Behavior of Chinese Bahaba (Bahaba taipingensis) during the Reproduction Season - Hongquan Li; Zhongchang Song; Jiangang Hui; Yingnan Su; Weijie Fu; Shufei Zhang; Lin Yan; Kuoqiu Yan; Honghui Huang; Yu Zhang (Journal of Marine Science and Engineering, 2023)
Chinese bahaba (Bahaba taipingensis) is a critically endangered fish species, which can produce sounds like other Sciaenidae species. In this study, sounds produced by sexually mature Chinese bahaba were recorded during the reproduction season for the first time. Two distinct types of sounds were observed during the reproduction season, termed as single drum and fast drum trains calls. Single drum callings occurred as a series of trains with rapid pulses, while fast drum trains callings were mainly made of a single signal. The single drum and fast drum trains had a peak frequency of 77.8 ± 16.2 Hz and 79.1 ± 8.7 Hz, respectively. Statistical analysis suggested significant differences in −3 dB bandwidth, signal duration, and root-mean-square sound pressure levels, except for peak frequency (p

Leonurine improves bovine oocyte maturation and subsequent embryonic development by reducing oxidative stress and improving mitochondrial function - Lv Zheng; Yuwen Luo; Dan Zhou; Hongyu Liu; Guizhen Zhou; Lin Meng; Yunpeng Hou; Changbin Liu; Jun Li; Xiangwei Fu (Theriogenology, 2023)

Plant identity shapes phyllosphere microbiome structure and abundance of genes involved in nutrient cycling - Jian Li; Ming-Kang Jin; Roy Neilson; Shi-Lin Hu; Yi-Jia Tang; Zhao Zhang; Fu-Yi Huang; Jing Zhang; Xiao-Ru Yang (Science of The Total Environment, 2023)

Secondary pollution of microplastic hetero-aggregates after chlorination: Released contaminants rarely re-adsorbed by the second-formed hetero-aggregates - Yan Jin; Minghui Li; Feiyong Chen; Lin Wang; Lijie Zhang; Zhigang Yang; Ning Wang; Jie Fu; Yang Yu; Xiaoxiang Cheng; Daoji Wu (Journal of Hazardous Materials, 2023)

Citrate-promoted dissolution of nanostructured manganese oxides: Implications for nano-enabled sustainable agriculture - Di Fu; Lin Duan; Xiaoyan Li; Chuanjia Jiang; Tong Zhang; Wei Chen (Journal of Environmental Sciences, 2023)

Tailoring the crumpled structures of a polyamide membrane with a heterostructural MXene-TiO2 interlayer for high water permeability - Jiawei Fu; Hang Xu; Tao Lin; Ao Wang; Anqi Wang; Chen Yao; Weihang Chen; Mingmei Ding; Chunxia Geng; Li Gao (Desalination, 2023)

Transformation of soil organic matter subjected to environmental disturbance and preservation of organic matter bound to soil minerals: a review - Qingchao Li; Lingli Wang; Yu Fu; Dagang Lin; Meiru Hou; Xiaodie Li; Dongdong Hu; Zhaohui Wang (Journal of Soils and Sediments, 2023)

Identification and Characterization of Bacillus subtilis B9: A Diazotrophic Plant Growth-Promoting Endophytic Bacterium Isolated from Sugarcane Root - Yi-ning Di; Ling Kui; Pratiksha Singh; Lu-feng Liu; Lin-yan Xie; Li-lian He; Fu-sheng Li (Journal of Plant Growth Regulation, 2023)
Plant endophytic microorganisms, which can enhance plant growth and resistance to biotic and abiotic stresses, are untapped resources with large potential applications for crop production. However, the endophytic community is influenced by multiple factors, such as host genetics, the environment, and other microbes. Thus, it is important to characterize well-adapted endophytes from native crops. We isolated 43 endophytic bacteria from sugarcane cultivar Yunzhe-99-91. All these 43 isolates were examined in vitro for nitrogenase activity and the ability to dissolve phosphorus and produce siderophore. One of these strains, B9, identified as Bacillus subtilis and showed maximum plant growth promotion, was selected for detailed studies. B9 promoted the production of organic acids such as propionic acid, acetic acid, malic acid and citric acid, and the production of phytohormones, including indole-3-acetic acid, cytokinin, 6-benzyladenine, and zeatin. Moreover, B9 significantly promoted the growth of sugarcane plantlets and increased the content of nitrogen, phosphorus, and potassium in the seedlings by 29.26%, 50.78%, and 15.49%, respectively. The photosynthetic rate, root development, and chlorophyll content were also improved with varying degrees compared to the non-inoculated control. The cotyledon and hypocotyl of sugarcane gems germinated faster when co-cultured with the B9 strain compared with control group. Colonization assay showed that B9 was mainly colonized in the roots, followed by the stems and leaves. In conclusion, the positive interaction between endophytic strain B9 and sugarcane may provide long-lasting benefits and a direction for developing and utilizing B9 as a biofertilizer for sugarcane cultivation to decrease fertilizer application.

Girdin acts as an oncogene in gastric cancer by regulating AKT/GSK3β/β-catenin signaling - Yun Wang; Qiang Fu; Yun-jian Tao; Sheng-nan Ying; Heng-gao Zhong; Yue Zhu; Xiao-han Qian; Lin Miao; Li-hua Yang (Functional & Integrative Genomics, 2023)
ThE present work focused on exploring Girdin expression within gastric cancer (GC), examining the effect of Girdin on the cell phenotype of GC, and clarifying the underlying mechanisms. Girdin expression in GC samples was identified by immunohistochemistry (IHC) and quantitative real-time PCR (qRT-PCR) assays. Girdin-targeting siRNAs were transfected into GC cells; later, we examined GC cell proliferation, migration, invasion, and apoptosis, respectively. Additionally, the protein expression was examined through Western blotting assay. Moreover, the tumor implantation experiment was conducted for examining Girdin knockdown in vivo. The results showed that Girdin expression elevated within GC samples, which was associated with the dismal prognostic outcome. Girdin knockdown suppressed GC cell proliferation, migration, and invasion, and enhanced apoptosis and cell cycle arrest. Girdin promoted the phosphorylation of AKT, GSK3β, and β-catenin. Moreover, Girdin inhibited the phosphorylation of β-catenin. Girdin suppressed cell apoptosis and stimulated cell migration and invasion, while AKT inhibitor (MK2206) treatment reversed the effect of Girdin overexpression, and GSK3β inhibitor (CHIR99021) treatment enhanced the effect of Girdin overexpression on GC cells. Besides, Girdin delayed tumor growth in vivo. In conclusion, Girdin was abnormally expressed in GC samples, which promoted the development of GC by regulating AKT/GSK3β/β-catenin signaling.

No tillage outperforms conventional tillage under arid conditions and following fertilization - Stavros D. Veresoglou; Junjiang Chen; Xuheng Du; Qi Fu; QingLiu Geng; Chenyan Huang; Xilin Huang; Nan Hu; Yiming Hun; Guolin C. Li; Zhiman Lin; Zhiyu Ma; et al. (Soil Ecology Letters, 2023)

Hydraulic determinants of drought-induced tree mortality and changes in tree abundance between two tropical forests with different water availability - Yong-Qiang Wang; Hui-Qing Song; Ya-Jun Chen; Pei-Li Fu; Jiao-Lin Zhang; Kun-Fang Cao; Shi-Dan Zhu (Agricultural and Forest Meteorology, 2023)

Cobalt exposure and dyslipidemia in elderly population: the mediating role of systemic inflammation and lipid peroxidation - Jia-Hui Huang; Li Tao; Yi Wu; Wei He; Jun-Xian Wang; Xi Chen; Lin Fu (Environmental Science and Pollution Research, 2023)

Co-hydrothermal carbonization of polyvinyl chloride and lignocellulose biomasses for chlorine and inorganics removal - Jing Zhang; Yuhan Chen; Xu Xia; Binbin Fu; Chuanjin Lin; Guangchao Jia; Xin Cui; Fang Liu; Peitao Zhao; Yimin Li (Waste Management, 2023)

Rapid reduction of Cr(VI) with plant leaves: Implications for ex-situ phytoremediation of chromium-polluted waters in cold region - Yu Fu; Lingli Wang; Yunjiao Liu; Meiru Hou; Qingchao Li; Xiaodie Li; Dagang Lin; Jialin Chen; Zhaohui Wang; Bing Xie (Journal of Cleaner Production, 2023)

A new strategy: Inhibitory effect and mechanism of Cymbopogon martinii essential oil on Aspergillus flavus - Lizhen Lin; Shuaipeng Chen; Wenxin Xia; Tingting Li; Lin Dong; Yan Zhang; Yuanyuan Zhang; Hangying Li; Yunsheng Zhao; Xueyan Fu (Food Bioscience, 2023)

Selenium alleviates cadmium-induced mitophagy through FUNDC1-mediated mitochondrial quality control pathway in the lungs of sheep - Shixuan Lin; Fan Yang; Mingwen Hu; Jing Chen; Guiping Chen; Aiming Hu; Xiong Li; Danghua Fu; Chenghong Xing; Zhiwei Xiong; Yunhui Wu; Huabin Cao (Environmental Pollution, 2023)

Cobalt single atom anchored on N-doped carbon nanoboxes as typical single-atom catalysts (SACs) for boosting the overall water splitting - Tong Li; Siyuan Ren; Cheng Zhang; Lingxia Qiao; Jiang Wu; Ping He; Jia Lin; Yongsheng Liu; Zaiguo Fu; Qunzhi Zhu; Weiguo Pan; Baofeng Wang; et al. (Chemical Engineering Journal, 2023)

A green and designable natural deep eutectic solvent-based supramolecular solvents system: Efficient extraction and enrichment for phytochemicals - Zi-Hui Cai; Jian-Dong Wang; Lin Liu; Liu-Ding Ruan; Qi Gu; Xin-Yu Yan; Li-Na Fu; Peng-Quan Zhao; Su Zhang; Yu-Jie Fu (Chemical Engineering Journal, 2023)

Highly efficient harvesting of vibration energy for complex wastewater purification using Bi5Ti3FeO15 with controlled oxygen vacancies - Ying Zheng; Xinyan Wu; Yongcheng Zhang; Yanqiang Li; Weiquan Shao; Jie Fu; Qing Lin; Jinshan Tan; Shouwu Gao; Wanneng Ye; Haitao Huang (Chemical Engineering Journal, 2023)

Enhanced antibacterial effect and biodegradation of coating via dual-in-situ growth based on carboxymethyl cellulose - Zhenhao Lin; Hao Fu; Yuancheng Zhang; Yongfu Deng; Fuxiang Wei; Hao Li; Chuanhui Xu; Fuli Hua; Baofeng Lin (Carbohydrate Polymers, 2023)

Hybridization of carboxymethyl chitosan with bimetallic MOFs to construct renewable metal ion “warehouses” with rapid sterilization and long-term antibacterial effects - Hao Li; Yuwei Zhang; Yuancheng Zhang; Fuxiang Wei; Yongfu Deng; Zhenhao Lin; Chuanhui Xu; Lihua Fu; Baofeng Lin (Carbohydrate Polymers, 2023)

AIFM1 variants associated with auditory neuropathy spectrum disorder cause apoptosis due to impaired apoptosis-inducing factor dimerization - Yue Qiu; Hongyang Wang; Huaye Pan; Jing Guan; Lei Yan; Mingjie Fan; Hui Zhou; Xuanhao Zhou; Kaiwen Wu; Zexiao Jia; Qianqian Zhuang; Zhaoying Lei; et al. (Journal of Zhejiang University-SCIENCE B, 2023)

Construction of the dynamic model of SCI rehabilitation using bidirectional stimulation and its application in rehabilitating with BCI - Zhengzhe Cui; Juan Lin; Xiangxiang Fu; Shiwei Zhang; Peng Li; Xixi Wu; Xue Wang; Weidong Chen; Shiqiang Zhu; Yongqiang Li (Cognitive Neurodynamics, 2023)

Phosphorus availability mediates plant–plant interaction and field productivity in maize-grass pea intercropping system: Field experiment and its global validation - Shuang-Guo Zhu; Hong-Yan Tao; Wen-Bo Li; Rui Zhou; Yan-Wen Gui; Li Zhu; Xiao-Lin Zhang; Wei Wang; Bao-Zhong Wang; Fu-Jian Mei; Hao Zhu; You-Cai Xiong (Agricultural Systems, 2023)

Antiherbivore effect of Cuscuta campestris against Spodoptera frugiperda - Chang-Lin Sung; Fang-Yu Hu; Yi Li; Shin-Fu Tsai; Wen-Po Chuang (Arthropod-Plant Interactions, 2023)

Biofouling characteristics in Xinghua Bay of Fujian, China - Heshan Lin; Yaqin Huang; Yingyue Lin; Shuyi Zhang; Shihao Yu; Kun Liu; Jianfeng Mou; Junhui Lin; Xuebao He; Sujing Fu; Weijie Xie; Zhongbao Li (Frontiers in Marine Science, 2023)
Biofouling is one of the main factors affecting the efficiency and safety of cooling water systems in coastal nuclear power plants. Understanding the population dynamics, succession rules and cumulative effects of major fouling organisms is the basis for targeted prevention and control. A 1-year simulated concrete panel test was conducted from December 2020 to November 2021 in Xinghua Bay, China. A total of 78 species of fouling organisms were recorded by combining the monthly, seasonal, semiannual, annual and monthly cumulative panels, and the community composition was dominated by nearshore warm-water species, making for a typical subtropical inner bay-type community. The fouling organisms had a peak attachment period from June to October. Significantly more attachment was observed during summer (from June to August) than during the other three seasons. The attachment amount in the second half-year (from June to November) was much higher than that in the first half-year (from December to May). The attachment thickness, density, and biomass of the bottom summer panels reached 20 cm, 105,150 ind./m 2 , and 19,274.50 g/m 2 , respectively, while those of the bottom annual panels were 40 cm, 27,300 ind./m 2 , and 17,762.50 g/m 2 , respectively. The dominant fouling organisms with calcified shells mainly included Amphibalanus reticulatus and Pernaviridis . These species had high attachment amounts,could accumulate attachments for a long time, and even might cause secondary blockage, making them the most detrimental to the safety of a cooling system. Moreover,the seasonal upward growth of hydroids and bryozoans can also significantly reduce the efficiency of cooling water intake. We suggest that targeted prevention and control should be carried out according to the larval attachment period of different dominant groups of fouling organisms during June-October, which can greatly improve the prevention and control efficiency. Strengthening the research on the biological cycle phenomenon of the main species and their main environmental impact factors, and establishing a scientific and effective early-warning model are the governance direction of formulating and implementing scientific pollution prevention and control in the future.

Water microecology is affected by seasons but not sediments: A spatiotemporal dynamics survey of bacterial community composition in Lake Changshou—The largest artificial lake in southwest China - Ai-ling Chen; Fu-qing Xu; Xia Su; Fu-pan Zhang; Wan-chao Tian; Shang-jie Chen; Fang Gou; Zhi-lin Xing; Jin-xin Xiang; Juan Li; Tian-tao Zhao (Marine Pollution Bulletin, 2023)

Zero-valent iron boosts nitrate-to-ammonia bioconversion via extracellular electron donation and reduction pathway complementation - Xue Li; Jie Li; Xiao-Rong Yu; Yong-Kun Zhu; Hou-Qi Liu; Lin Chen; Jing Wu; Xian-Zhong Fu; Shuo Cui; Tian-Yin Huang; Ru-Quan Ye; Wen-Wei Li (Resources, Conservation and Recycling, 2023)

Enhanced high-salinity brines treatment using polyamide nanofiltration membrane with tunable interlayered MXene channel - Ao Wang; Hang Xu; Jiawei Fu; Tao Lin; Jun Ma; Mingmei Ding; Li Gao (Science of The Total Environment, 2023)

Catalytic co-cracking of biomass and waste plastics with sawdust mediated ZSM-5 synthesized via activating gel process - Fuwei Li; Xiaofeng Wang; Hengshuo Gu; Hongbing Fu; Asad Ali; Hongfei Lin; Zhixia Li (Fuel, 2023)

Enhancement of lycopene bioaccessibility in tomatoes using excipient emulsions: Effect of dark tea polysaccharides - Chao Wang; Yinxin Fu; Yi Cao; Jialu Huang; Hongyi Lin; Peiyi Shen; David Julian McClements; Lingyu Han; Tiantian Zhao; Xiaoxuan Yan; Qian Li (Food Research International, 2023)

Residential greenness and dyslipidemia risk: Dose-response relations and mediation through BMI and air pollution - Qinjian Wang; Xiaoqing Li; Wenling Zhong; Hongyun Liu; Chuanteng Feng; Chao Song; Bin Yu; Yao Fu; Xi Lin; Yanrong Yin; Tiehui Chen; Jan D. Reinhardt; et al. (Environmental Research, 2023)

Robust emission in near-infrared II of lanthanide nanoprobes conjugated with Au (LNPs-Au) for temperature sensing and controlled photothermal therapy - Guofeng Liu; Zhenxing Wang; Wan Sun; Xiaohui Lin; Rui Wang; Chonghui Li; Li Zong; Zuoling Fu; Hanping Liu; Shicai Xu (Chemical Engineering Journal, 2023)

Near-infrared I/II emission and absorption carbon dots via constructing localized excited/charge transfer state for multiphoton imaging and photothermal therapy - Wen-Bo Zhao; Dan-Dan Chen; Kai-Kai Liu; Yong Wang; Rui Zhou; Shi-Yu Song; Fu-Kui Li; Lai-Zhi Sui; Qing Lou; Lin Hou; Chong-Xin Shan (Chemical Engineering Journal, 2023)

An S-scheme CdS/K2Ta2O6 heterojunction photocatalyst for production of H2O2 from water and air - Cui Lai; Mengyi Xu; Fuhang Xu; Bisheng Li; Dengsheng Ma; Yixia Li; Ling Li; Mingming Zhang; Danlian Huang; Lin Tang; Shiyu Liu; Huchuan Yan; et al. (Chemical Engineering Journal, 2023)

Calcination temperature regulates non-radical pathways of peroxymonosulfate activation via carbon catalysts doped by iron and nitrogen - Yue Wang; Yan Lin; Chunping Yang; Shaohua Wu; Xintao Fu; Xiang Li (Chemical Engineering Journal, 2023)

Bistable electrochromic dual-output array display based on intramolecular proton coupled electron transfer - Chengcheng Wang; Jiashuang Li; Wenhua Lin; Jingwen Wang; Yuhua Chen; Bingzhen Li; Liping Zhang; Shaohai Fu (Chemical Engineering Journal, 2023)

Combined population transcriptomic and genomic analysis reveals cis-regulatory differentiation of non-coding RNAs in maize - Jiawen Lu; Sihan Zhen; Jie Zhang; Yuxin Xie; Cheng He; Xiaoli Wang; Zheyuan Wang; Song Zhang; Yongxiang Li; Yu Cui; Guoying Wang; Jianhua Wang; et al. (Theoretical and Applied Genetics, 2023)

Expression profile of long non-coding RNAs in the intestine of black rockfish Sebastes schlegelii in response to Edwardsiella tarda infection - Xu Yan; Min Cao; Qiang Fu; Ning Yang; Ningning Wang; Lin Song; Chao Li (Journal of Oceanology and Limnology, 2023)

Ginsenoside Rb1 inhibits oxidative stress-induced ovarian granulosa cell injury through Akt-FoxO1 interaction - Ping Zhou; Feng Deng; Zi Yang; Canhui Cao; Hongcui Zhao; Fenting Liu; Ke Zhong; Lin Fu; Tianliu Peng; Di Sun; Hui Liu; Rong Li; et al. (Science China Life Sciences, 2022)

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

A histological study of vascular wall resident stem cells in venous malformations - Hou-Fu Xia; Wen-Qiang Lai; Gao-Hong Chen; Ye Li; Qi-Hui Xie; Yu-Lin Jia; Gang Chen; Yi-Fang Zhao (Cell and Tissue Research, 2022)

New loci for refractive errors and ocular biometric parameters in young Chinese Han adults - Yunyun Sun; Zi-Bing Jin; Shifei Wei; Hongyan Jia; Kai Cao; Jianping Hu; Caixia Lin; Wenzai An; Jiyuan Guo; He Li; Jing Fu; Shi-Ming Li; et al. (Science China Life Sciences, 2022)

Dynamic response and failure evolution of low-angled interbedding soft and hard stratum rock slope under earthquake - Jun Feng; Yingbin Zhang; Jianxian He; Hui Zhu; Lin Huang; Wentao Mao; Haiying Fu; Dejian Li (Bulletin of Engineering Geology and the Environment, 2022)

Wheat genomic study for genetic improvement of traits in China - Jun Xiao; Bao Liu; Yingyin Yao; Zifeng Guo; Haiyan Jia; Lingrang Kong; Aimin Zhang; Wujun Ma; Zhongfu Ni; Shengbao Xu; Fei Lu; Yuannian Jiao; et al. (Science China Life Sciences, 2022)

Catalytic effect of cesium on the oxidation behavior of cation exchange resins in Li2CO3-Na2CO3-K2CO3 melt - Yang-Hai Zheng; Yong-De Yan; Yun Xue; Yue-Lin Wang; Xin Liu; Wan-Sheng Mi; Qing-Guo Zhang; Yu Li; Fu-Qiu Ma; Mi-Lin Zhang; Zhi-Hao Gan; Kai Zhu (Environmental Science and Pollution Research, 2022)

Impacts of Mercury Exposure Levels and Sources on the Demethylation of Methylmercury Through Human Gut Microbiota - Xian-Feng Yang; Shao-Chen Yang; Fu-Li Wen; Lin Feng; Bo Meng; Hai-Yan Hu; Bao-Lin Wang; Jun Li; Alexandre J. Poulain; Ping Li (Bulletin of Environmental Contamination and Toxicology, 2022)

Potential millennial‐scale avian declines by humans in southern China - Feng Dong; Qiang Zhang; Yi‐Lin Chen; Fu‐Min Lei; Shou‐Hsien Li; Fei Wu; Xiao‐Jun Yang (Global Change Biology, 2022)
Mounting observational records demonstrate human‐caused faunal decline in recent decades, while accumulating archaeological evidence suggests an early biodiversity impact of human activities during the Holocene. A fundamental question arises concerning whether modern wildlife population declines began during early human disturbance. Here, we performed a population genomic analysis of six common forest birds in East Asia to address this question. For five of them, demographic history inference based on 25–33 genomes of each species revealed dramatic population declines by 4‐ to 48‐fold over millennia (e.g. 2000–5000 thousand years ago). Nevertheless, summary statistics detected nonsignificant correlations between these population size trajectories and Holocene temperature variations, and ecological niche models explicitly predicted extensive range persistence during the Holocene, implying limited demographic consequence of Holocene climate change. Further analyses suggest high negative correlations between the reconstructed population declines and human disturbance intensities and indicate a potential driver of human activities. These findings provide a deep‐time and large‐scale insight into the recently recognized avifaunal decline and support an early origin hypothesis of human effects on biodiversity. Overall, our study sheds light on the current biodiversity crisis in the context of long‐term human–environment interactions and offers a multi‐evidential framework for quantitatively assessing the ecological consequences of human disturbance.

Correction to: Inhibition of Dectin-1 Ameliorates Neuroinflammation by Regulating Microglia/Macrophage Phenotype After Intracerebral Hemorrhage in Mice - Xiongjie Fu; Hanhai Zeng; Jikuang Zhao; Guoyang Zhou; Hang Zhou; Jianfeng Zhuang; Chaoran Xu; Jianru Li; Yucong Peng; Yang Cao; Yin Li; Huaijun Chen; et al. (Translational Stroke Research, 2022)

Ginsenoside Rb3 attenuates skin flap ischemia-reperfusion damage by inhibiting STING-IRF3 signaling - Yuanbin Li; Haifen Liu; Zhaohui Zeng; Hui Lin; Xin Chen; Xianglian Yuan; Jizhe Qiu; Fengchun Fu; Zhuang Chen; Jianjun Kuang (Journal of Molecular Histology, 2022)

Vertical patterns of chlorophyll a in the euphotic layer are related to mesoscale eddies in the South China Sea - Mei-Lin Wu; You-Shao Wang; Yu-Tu Wang; Fu-Lin Sun; Xiaomei Li; Fang-Fang Gu; Jing-Chang Xiang (Frontiers in Marine Science, 2022)
Phytoplankton closely connects with the hydrodynamics and biogeochemical environment of the ocean. While research focusing on both the physiochemical factors and hydrodynamics regulating phytoplankton has already been conducted, the coupling mechanism between mesoscale eddies and the vertical distribution of phyto plankton in the South China Sea (SCS) is still not well understood. Here, phytoplankton was studied under one weak-cold and two warm eddies along the 18°N transect in the SCS. The results show that the vertical distribution of chlorophyll (chl- a ) presented a similar pattern at all four sampling stations. The mixed layer is less than 50 m. It is the same as the meridional salinity gradients that may be distinguished above a depth of 60 m. The subsurface chlorophyll maximum at the edge of a warm (WI) and cold eddy (CI) at E413 and E411 was shallower than that at the edge of a warm eddy (WII) at E407 and E409, indicating that temperature and salinity may be the important driving factors. On the whole, mesoscale eddies had a significant influence on the vertical pattern of chl- a in the SCS during the study period.

PPARγ Dysfunction in the Medial Prefrontal Cortex Mediates High-Fat Diet-Induced Depression - Cong-Cong Fu; Xin-Yi Zhang; Liu Xu; Hui-Xian Huang; Shuang Xu; Qiao-Qi Wu; Zhen Wang; Xi Gu; Li-Fang Lin; Song Lin; Ying-Ying Fang; Xiong Cao; et al. (Molecular Neurobiology, 2022)

Diminished miR-374c-5p negatively regulates IL (interleukin)-6 in unexplained recurrent spontaneous abortion - Lin Zhao; Li Han; Guozhen Hei; Ran Wei; Zhen Zhang; Xiaoxiao Zhu; Qiang Guo; Chu Chu; Xiaoxiao Fu; Ke Xu; Xia Li (Journal of Molecular Medicine, 2022)

Influence of asymmetric blockage of the drainage system of a deep-buried tunnel on water gushing - He-lin Fu; Peng-tao An; Yi-min Wu; Jie Li; Long Chen (Journal of Mountain Science, 2022)

Correction to: Publication characteristics, topic trends and knowledge domains of karst ecological restoration: a bibliometric and knowledge mapping analysis from 1991 to 2021 - Kehui Liu; Xiaojin Guan; Guangluan Li; Min Duan; Yi Li; Yanyan Hong; Meimei Lin; Rongxin Fu; Fangming Yu (Plant and Soil, 2022)

Publication characteristics, topic trends and knowledge domains of karst ecological restoration: a bibliometric and knowledge mapping analysis from 1991 to 2021 - Kehui Liu; Xiaojin Guan; Guangluan Li; Min Duan; Yi Li; Yanyan Hong; Meimei Lin; Rongxin Fu; Fangming Yu (Plant and Soil, 2022)

A Deep Mesencephalic Nucleus Circuit Regulates Licking Behavior - Di Zheng; Jia-Yu Fu; Meng-Yu Tang; Xiao-Dan Yu; Yi Zhu; Chen-Jie Shen; Chun-Yue Li; Shi-Ze Xie; Shan Lin; Minmin Luo; Xiao-Ming Li (Neuroscience Bulletin, 2022)

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

Effects of conservation measures on crop diversity and their implications for climate-resilient livelihoods: the case of Rupa Lake Watershed in Nepal - Yun-li Bai; Chao Fu; Balaram Thapa; Ram Balladur Rana; Lin-xiu Zhang (Journal of Mountain Science, 2022)
Agrobiodiversity conservation is vital for achieving sustainability, but empirical studies on the effects of different practices or measures on crop diversity are rare. This study aims to estimate the effects of raising conservation awareness (RCA), building diversity blocks (BDB), and their combination on crop diversity among 240 randomly selected households surrounding the Rupa Lake Watershed in Nepal. Based on descriptive analysis and multiple regression models, the results indicate that the two single measures had no significant effect on the numbers of crop species and varieties grown by households in 2018. However, the combination of RCA and BDB had a significantly positive effect on the number of crop varieties, especially for grain and vegetable crops. Considering that these crops are essential in the daily lives of local people, the results indicate that a strategy that combines both awareness raising and on-farm conservation measures can generate higher crop diversity and better serve the climate-resilient livelihoods of people in mountainous areas.

Antifungal sesquiterpenes with post-harvest anthracnose control effect on bananas from the fungus Fusarium lateritium - Junjie Zhu; Ping Xiong; Ziyang Li; Jiazhong Li; Longsheng Lin; Xing Fu; Yuxuan Huang; Yahong Xiong; Chunyuan Li (Natural Product Research, 2022)

MoOpy2 is essential for fungal development, pathogenicity, and autophagy in Magnaporthe oryzae - Ying‐Ying Cai; Jing‐Yi Wang; Xi‐Yu Wu; Shuang Liang; Xue‐Ming Zhu; Lin Li; Jian‐Ping Lu; Xiao‐Hong Liu; Fu‐Cheng Lin (Environmental Microbiology, 2022)
Summary The development and pathogenicity of the fungus Magnaporthe oryzae , the causal agent of destructive rice blast disease, require it to perceive external environmental signals. Opy2, an overproduction‐induced pheromone‐resistant protein 2, is a crucial protein for sensing external signals in Saccharomyces cerevisiae . However, the biological functions of the homologue of Opy2 in M. oryzae are unclear. In this study, we identified that MoOPY2 is involved in fungal development, pathogenicity, and autophagy in M. oryzae . Deletion of MoOPY2 resulted in pleiotropic defects in hyphal growth, conidiation, germ tube extension, appressorium formation, appressorium turgor generation, and invasive growth, therefore leading to attenuated pathogenicity. Furthermore, MoOpy2 participates in the Osm1 MAPK pathway and the Mps1 MAPK pathway by interacting with the adaptor protein Mst50. The interaction sites of Mst50 and MoOpy2 colocalized with the autophagic marker protein MoAtg8 in the preautophagosomal structure sites (PAS). Notably, the Δ Moopy2 mutant caused cumulative MoAtg8 lipidation and rapid GFP‐MoAtg8 degradation in response to nitrogen starvation, showing that MoOpy2 is involved in the negative regulation of autophagy activity. Taken together, our study revealed that MoOpy2 of M. oryzae plays an essential role in the orchestration of fungal development, appressorium penetration, autophagy and pathogenesis.

Endosomal sorting complexes required for transport‐0 ( ESCRT ‐0) are essential for fungal development, pathogenicity, autophagy and ER ‐phagy in Magnaporthe oryzae - Li‐Xiao Sun; Hui Qian; Meng‐Yu Liu; Ming‐Hua Wu; Yun‐Yun Wei; Xue‐Ming Zhu; Jian‐Ping Lu; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2022)
Summary Magnaporthe oryzae is an important plant pathogen that causes rice blast. Hse1 and Vps27 are components of ESCRT‐0 involved in the multivesicular body (MVB) sorting pathway and biogenesis. To date, the biological functions of ESCRT‐0 in M. oryzae have not been determined. In this study, we identified and characterized Hse1 and Vps27 in M. oryzae . Disruption of MoHse1 and MoVps27 caused pleiotropic defects in growth, conidiation, sexual development and pathogenicity, thereby resulting in loss of virulence in rice and barley leaves. Disruption of MoHse1 and MoVps27 triggered increased lipidation of MoAtg8 and degradation of GFP‐MoAtg8, indicating that ESCRT‐0 is involved in the regulation of autophagy. ESCRT‐0 was determined to interact with coat protein complex II (COPII), a regulator functioning in homeostasis of the endoplasmic reticulum (ER homeostasis), and disruption of MoHse1 and MoVps27 also blocked activation of the unfolded protein response (UPR) and autophagy of the endoplasmic reticulum (ER‐phagy). Overall, our results indicate that ESCRT‐0 plays critical roles in regulating fungal development, virulence, autophagy and ER‐phagy in M. oryzae .

Fishery Status and Rebuilding of Major Economic Fishes in the Largest Freshwater Lake in China Based on Limited Data - Yang Liu; Huiyun Fu; Linlong Wang; Li Lin; Gang He; Peifeng Fu; Changlai Wang; Yanping Zhang; Bin Kang (Fishes, 2022)
Poyang Lake, the largest freshwater lake in China, possesses abundant fishery resources, but its fish stock status is still unclear. In this work, the stock status of and fishing efforts of nine major economic fishes in the Poyang Lake were estimated from 2000 to 2019 with a catch-based maximum sustainable yield (CMSY) model based on catch and resilience data. It was further predicted whether the biomass of those fishes could be restored to support maximum sustainable yield (Bmsy) under the policy of “Ten years fishing moratorium in the Yangtze River”. The results showed that goldfish Carassius auratus, grass carp Ctenopharyngodon idella, and black carp Mylopharyngodon piceus suffered from higher fishing efforts and low biomass in the past 20 years; bighead carp Hypophthalmichthys nobilis, yellow catfish Tachysurus fulvidraco, and common carp Cyprinus carpio responded differently to their fishing efforts; silver carp Hypophthalmichthys molitrix, Amur catfish Silurus asotus, and mandarin fish Siniperca chuatsi were underexploited. Six species were overfished in 2019, and their biomass would be expected to recover for sustainable exploitation during the fishing moratorium, except for M. piceus. This study provided a case study of feasible freshwater fishery evaluation in limnetic ecosystems.

Airborne black carbon variations during the COVID-19 lockdown in the Yangtze River Delta megacities suggest actions to curb global warming - Hao Li; Kan Huang; Qingyan Fu; Yanfen Lin; Jia Chen; Congrui Deng; Xudong Tian; Qian Tang; Qingchuan Song; Zhen Wei (Environmental Chemistry Letters, 2022)

Different effects of the DRD4 genotype on intrinsic brain network connectivity strength in drug-naïve children with ADHD and healthy controls - Shuangli Chen; Andan Qian; Jiejie Tao; Ronghui Zhou; Chuqi Fu; Chuang Yang; Qingxia Lin; JieJie Zhou; Jiance Li; Xiaoqi Huang; Meihao Wang (Brain Imaging and Behavior, 2022)
The dopamine D4 receptor gene (DRD4) has been consistently reported to be associated with attention-deficit/hyperactivity disorder (ADHD). Recent studies have linked DRD4 to functional connectivity among specific brain regions. The current study aimed to compare the effects of the DRD4 genotype on functional integrity in drug-naïve ADHD children and healthy children. Resting-state functional MRI images were acquired from 49 children with ADHD and 37 healthy controls (HCs). We investigated the effects of the 2-repeat allele of DRD4 on brain network connectivity in both groups using a parameter called the degree of centrality (DC), which indexes local functional relationships across the entire brain connectome. A voxel-wise two-way ANCOVA was performed to examine the diagnosis-by-genotype interactions on DC maps. Significant diagnosis-by-genotype interactions with DC were found in the temporal lobe, including the left inferior temporal gyrus (ITG) and bilateral middle temporal gyrus (MTG) (GRF corrected at voxel level p < 0.001 and cluster level p < 0.05, two-tailed). With the further subdivision of the DC network according to anatomical distance, additional brain regions with significant interactions were found in the long-range DC network, including the left superior parietal gyrus (SPG) and right middle frontal gyrus (MFG). The post-hoc pairwise analysis found that altered network centrality related to DRD4 differed according to diagnostic status (p < 0.05). This genetic imaging study suggests that the DRD4 genotype regulates the functional integration of brain networks in children with ADHD and HCs differently. This may have important implications for our understanding of the role of DRD4 in altering functional connectivity in ADHD subjects.

Development and validation of a 30-day death nomogram in patients with spontaneous cerebral hemorrhage: a retrospective cohort study - Qian Han; Mei Li; Dongpo Su; Aijun Fu; Lin Li; Tong Chen (Acta Neurologica Belgica, 2022)

New paraconic acids from the endophytic fungus Xylariaceae sp. J4 - Chao Yuan; Xue-Chun Shu; Lin Fan; Ying-Bo Zhang; Ling-Liang Guan; Fu-Lai Yu; Xiao-Lu Chen; Gang Li (Natural Product Research, 2022)

N-acetylcysteine alleviates pulmonary inflammatory response during benzo[a]pyrene-evoked acute lung injury - Hui Zhao; Lin Fu; Hui-Xian Xiang; Ying Xiang; Meng-Die Li; Bian-Bian Lv; Zhu-Xia Tan; Lan Gao; Cheng Zhang; De-Xiang Xu (Environmental Science and Pollution Research, 2022)

A novel alphahypovirus that infects the fungal plant pathogen Sclerotinia sclerotiorum - Weibo Liang; Zhongbo Lu; Jie Duan; Daohong Jiang; Jiatao Xie; Jiasen Cheng; Yanping Fu; Tao Chen; Bo Li; Xiao Yu; Weidong Chen; Yang Lin (Archives of Virology, 2022)

Inhibition of Dectin-1 Ameliorates Neuroinflammation by Regulating Microglia/Macrophage Phenotype After Intracerebral Hemorrhage in Mice - Xiongjie Fu; Hanhai Zeng; Jikuang Zhao; Guoyang Zhou; Hang Zhou; Jianfeng Zhuang; Chaoran Xu; Jianru Li; Yucong Peng; Yang Cao; Yin Li; Huaijun Chen; et al. (Translational Stroke Research, 2021)

Occurrence, source apportionment, and carcinogenic risk assessment of polycyclic aromatic hydrocarbons in urban road dusts in Shanghai - Xue-Tong Wang; Rui Fu; Ying Zhou; Cheng-Lin Wang; Guo-Fa Ren; Xiao-Li Wang; Hui Li (Environmental Science and Pollution Research, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Environmental contamination with SARS‐CoV ‐2 in COVID ‐19 hospitals in Wuhan, China, 2020 - Wei Liu; Dingchen Li; Chaojie Yang; Fangyan Chen; Ruizhong Jia; Leili Jia; Xinyi Xia; Shanhong Fan; Qing Tan; Yuehua Ke; Yong Chen; Haifeng Li; et al. (Environmental Microbiology, 2021)
Summary Coronavirus disease 2019 (COVID‐19) pandemic has caused high number of infections and deaths of healthcare workers globally. Distribution and possible transmission route of SARS‐CoV‐2 in hospital environment should be clarified. We herein collected 431 environmental (391 surface and 40 air) samples in the intensive care unit (ICU) and general wards (GWs) of three hospitals in Wuhan, China from February 21 to March 4, 2020, and detected SARS‐CoV‐2 RNA by real‐time quantitative PCR. The viral positive rate in the contaminated areas was 17.8% (28/157), whereas there was no virus detected in the clean areas. Higher positive rate (22/59, 37.3%) was found in ICU than that in GWs (3/63, 4.8%). The surfaces of computer keyboards and mouse in the ICU were the most contaminated (8/10, 80.0%), followed by the ground (6/9, 66.7%) and outer glove (2/5, 40.0%). From 17 air samples in the contaminated areas, only one sample collected at a distance of around 30 cm from the patient was positive. Enhanced surface disinfection and hand hygiene effectively decontaminated the virus from the environment. This finding might help understand the transmission route and contamination risk of SARS‐CoV‐2 and evaluate the effectiveness of infection prevention and control measures in healthcare facilities.

Degraded polysaccharides from Porphyra haitanensis: purification, physico-chemical properties, antioxidant and immunomodulatory activities - Yun-Feng Huo; Yin-Ting Li; Wei Xia; Chong Wang; Yuan-Yuan Xie; Yan-Bo Wang; Tao Zhou; Ling-Lin Fu (Glycoconjugate Journal, 2021)

Descending Modulation of Spinal Itch Transmission by Primary Somatosensory Cortex - Zi-Han Wu; Han-Yu Shao; Yuan-Yuan Fu; Xiao-Bo Wu; De-Li Cao; Sheng-Xiang Yan; Wei-Lin Sha; Yong-Jing Gao; Zhi-Jun Zhang (Neuroscience Bulletin, 2021)

Deficiency of Klc2 Induces Low-Frequency Sensorineural Hearing Loss in C57BL/6 J Mice and Human - Xiaolong Fu; Yachun An; Hongyang Wang; Peipei Li; Jing Lin; Jia Yuan; Rongyu Yue; Yecheng Jin; Jiangang Gao; Renjie Chai (Molecular Neurobiology, 2021)

Fast estimation method of volumes of landslide deposit by the 3D reconstruction of smartphone images - Lin Fu; Jun Zhu; Wei-lian Li; Ji-gang You; Zhang-yu Hua (Landslides, 2021)

Passivation and remediation of Pb and Cr in contaminated soil by sewage sludge biochar tubule - Lin Chen; Qi Ni; Yan Wu; Chuan Fu; Wei Ping; Hongyu Bai; Mengnan Li; Hongcheng Huang; Hanshuang Liu (Environmental Science and Pollution Research, 2021)

A Multilevel Recognition Model of Water Inrush Sources: A Case Study of the Zhaogezhuang Mining Area - Gang Lin; Dong Jiang; Donglin Dong; Jingying Fu; Xiang Li (Mine Water and the Environment, 2021)

3D Step-by-step inversion strategy for audio magnetotellurics data based on unstructured mesh - San Cheng; Zhi-Yong Zhang; Feng Zhou; Man Li; Hui Chen; Fu-Sheng Shi; Lin-Pin Huang; Yong Li (Applied Geophysics, 2021)

Wogonin Accelerates Hematoma Clearance and Improves Neurological Outcome via the PPAR-γ Pathway After Intracerebral Hemorrhage - Jianfeng Zhuang; Yucong Peng; Chi Gu; Huihui Chen; Zheng Lin; Hang Zhou; Xiao Wu; Jianru Li; Xiaobo Yu; Yang Cao; Hanhai Zeng; Xiongjie Fu; et al. (Translational Stroke Research, 2021)

Evaluation and improvement of the greenness of plasma spraying through life cycle assessment and grey relational analysis - Jing Liu; Liming Wang; Fangyi Li; Yanle Li; Xueju Ran; Lin Kong; Yan Fu (The International Journal of Life Cycle Assessment, 2021)

RSF1 requires CEBP/β and hSNF2H to promote IL-1β-mediated angiogenesis: the clinical and therapeutic relevance of RSF1 overexpression and amplification in myxofibrosarcomas - Chien-Feng Li; Ti-Chen Chan; Cheng-I. Wang; Fu-Min Fang; Po-Chun Lin; Shih-Chen Yu; Hsuan-Ying Huang (Angiogenesis, 2021)

Cysteiniphilum marinum sp. nov., isolated from coastal seawater - Hai-Min Luo; Jun-Hui Feng; Liang-Hui Li; Meng-Meng Li; Ru-Qin Liu; Fu Chen; Ying Lin; Wen-Jun Li; Ping-Hua Qu; Min Xiao (Antonie van Leeuwenhoek, 2021)

Soil fertility, enzyme activity, and microbial community structure diversity among different soil textures under different land use types in coastal saline soil - Yun Zhu; Bin Guo; Chen Liu; Yicheng Lin; Qinglin Fu; Ningyu Li; Hua Li (Journal of Soils and Sediments, 2021)

Kelp aquaculture in China: a retrospective and future prospects - Zi‐Min Hu; Ti‐Feng Shan; Jie Zhang; Quan‐Sheng Zhang; Alan T. Critchley; Han‐Gil Choi; Norishige Yotsukura; Fu‐Li Liu; De‐Lin Duan (Reviews in Aquaculture, 2021)
Globally, China has the largest scale of kelp cultivation and production operations. However, its kelp aquaculture industry is suffering from declining germplasm diversity, degradation of agronomic traits, the presence of polluted environments, changing ocean conditions and increasing anthropological interference. This review covers two of the most commercially important kelp species in China, viz. Saccharina japonica and Undaria pinnatifida . It summarizes the history of their cultivation, production, economic and ecological benefits, their breeding programmes (e.g. inter‐ and intra‐specific hybridization and marker‐assisted selection) and efforts towards population genetic diversity and conservation. The article focuses on three significant challenges, for example genetic cross‐contamination between the wild and farmed kelp populations, ocean warming and ocean acidification. Accordingly, we outline the steps required to provide several intervention measures, for example (i) collection and preservation of wild and cultivated kelp germplasm; (ii) selection of suitable cultivation sites under changing environmental conditions; (iii) developing stress‐resistant cultivars; and finally, (iv) adoption of innovative cultivation models. The review concludes with genome‐based, designs for molecular breeding and calls for the establishment of an East Asian Kelp Consortium (EAKC). Collectively, the Chinese kelp industry could provide beneficial goods and services, for example bioenergy to fine chemicals and environmental benefits, such as carbon capture, pH amelioration and provision of habitat for many other marine species of commercial value. The strategies proposed in this article thus have the potential to not only improve but also reinvigorate the kelp industry in China and nearby Japan and Korea, in the context of both environmental health and economic benefits.

Cover Image - Zi‐Min Hu; Ti‐Feng Shan; Jie Zhang; Quan‐Sheng Zhang; Alan T. Critchley; Han‐Gil Choi; Norishige Yotsukura; Fu‐Li Liu; De‐Lin Duan (Reviews in Aquaculture, 2021)
The cover image is based on the Review Article Kelp aquaculture in China: A retrospective and future prospects by Zi‐Min Hu et al., https://doi.org/10.1111/raq.12524 . image

Three new acenaphthene derivatives from rhizomes of Musa basjoo and their cytotoxic activity - Li Jiang; Bao Zhang; Yang Wang; Jia Sun; Xue Ma; Guangcheng Wang; Sihong Fu; Changhu Lin; YongJun Li (Natural Product Research, 2021)

Structure of SARS-CoV-2 main protease in the apo state - Xuelan Zhou; Fanglin Zhong; Cheng Lin; Xiaohui Hu; Yan Zhang; Bing Xiong; Xiushan Yin; Jinheng Fu; Wei He; Jingjing Duan; Yang Fu; Huan Zhou; et al. (Science China Life Sciences, 2021)

Human β-Defensin 118 Attenuates Escherichia coli K88–Induced Inflammation and Intestinal Injury in Mice - Qian Lin; Qingqing Fu; Xiang Li; Yuheng Luo; Junqiu Luo; Daiwen Chen; Xiangbing Mao; Bing Yu; Ping Zheng; Zhiqing Huang; Jie Yu; Hui Yan; et al. (Probiotics and Antimicrobial Proteins, 2021)

Selective Ferroptosis Inhibitor Liproxstatin-1 Attenuates Neurological Deficits and Neuroinflammation After Subarachnoid Hemorrhage - Yang Cao; Yin Li; Chao He; Feng Yan; Jian-Ru Li; Hang-Zhe Xu; Jian-Feng Zhuang; Hang Zhou; Yu-Cong Peng; Xiong-Jie Fu; Xiao-Yang Lu; Yuan Yao; et al. (Neuroscience Bulletin, 2021)

miR-23b Attenuates LPS-Induced Inflammatory Responses in Acute Lung Injury via Inhibition of HDAC2 - Zhi-Feng Luo; Xiang-Hui Jiang; Huan Liu; Li-Yuan He; Xiong Luo; Fu-Chun Chen; Yu-Lin Tan (Biochemical Genetics, 2021)

Experimental evidence for long‐term coexistence of copiotrophic and oligotrophic bacteria in pelagic surface seawater - Yi Li; Zhi‐Bin Wang; Xi‐Ying Zhang; Yan‐Ru Dang; Lin‐Lin Sun; Wei‐Peng Zhang; Hui‐Hui Fu; Gui‐Peng Yang; Min Wang; Andrew McMinn; Xiu‐Lan Chen; Yin Chen; et al. (Environmental Microbiology, 2021)
Summary Most marine copiotrophic bacteria can produce extracellular enzymes to degrade biopolymers into bio‐available smaller solutes, while oligotrophic bacteria usually cannot. Bacterial extracellular enzymes and enzymatic products can be a common resource that could be utilized by both copiotrophs and oligotrophs; when present, oligotrophs may outcompete the enzyme‐producing copiotrophs. However, copiotrophs and oligotrophs consistently coexist in the ocean. How they maintain coexistence has still not been experimentally studied. In this study, the interaction and coexistence of a copiotroph and an oligotroph, isolated from the same surface seawater sample and utilizing the same proteinaceous substrate, were experimentally investigated. The copiotroph could secrete extracellular proteases to degrade and then utilize the proteinaceous substrate. The oligotroph was unable to utilize the proteinaceous substrate by itself, but could grow by using the hydrolysate amino acids. The copiotroph outcompeted the oligotroph by adsorbing the amino acids quickly and having a higher growth rate in the rich medium. The oligotroph survived by adapting to low concentration of nutrients. The copiotroph and oligotroph were able to maintain long‐term (up to 142 days) coexistence in the laboratory. This study indicates that differences in the utilization of different concentrations of nutrients can drive the coexistence of marine copiotrophs and oligotrophs.

Geographical and interspecific variation in susceptibility of three common thrips species to the insecticide, spinetoram - Yong-Fu Gao; Ya-Jun Gong; Li-Jun Cao; Jin-Cui Chen; Yu-Lin Gao; Majid Mirab-balou; Min Chen; Ary A. Hoffmann; Shu-Jun Wei (Journal of Pest Science, 2021)

Stocks and losses of soil organic carbon from Chinese vegetated coastal habitats - Chuancheng Fu; Yuan Li; Lin Zeng; Haibo Zhang; Chen Tu; Qian Zhou; Kuanxu Xiong; Jiaping Wu; Carlos M. Duarte; Peter Christie; Yongming Luo (Global Change Biology, 2021)
Global vegetated coastal habitats (VCHs) represent a large sink for organic carbon (OC) stored within their soils. The regional patterns and causes of spatial variation, however, remain uncertain. The sparsity and regional bias of studies on soil OC stocks from Chinese VCHs have limited the reliable estimation of their capacity as regional and global OC sinks. Here, we use field and published data from 262 sampled soil cores and 181 surface soils to report estimates of soil OC stocks, burial rates and losses of VCHs in China. We find that Chinese mangrove, salt marsh and seagrass habitats have relatively low OC stocks, storing 6.3 ± 0.6, 7.5 ± 0.6, and 1.6 ± 0.6 Tg C (±95% confidence interval) in the top meter of the soil profile with burial rates of 44 ± 17, 159 ± 57, and 6 ± 45 Gg C/year, respectively. The variability in the soil OC stocks is linked to biogeographic factors but is mostly impacted by sedimentary processes and anthropic activities. All habitats have experienced significant losses, resulting in estimated emissions of 94.2–395.4 Tg CO 2 e (carbon dioxide equivalent) over the past 70 years. Reversing this trend through conservation and restoration measures has, therefore, great potential in contributing to the mitigation of climate change while providing additional benefits. This assessment, on a national scale from highly sedimentary environments under intensive anthropogenic pressures, provides important insights into blue carbon sink mechanism and sequestration capacities, thus contributing to the synchronous progression of global blue carbon management.

Melatonin ameliorates spatial memory and motor deficits via preserving the integrity of cortical and hippocampal dendritic spine morphology in mice with neurotrauma - Xiao-Jing Lin; Ruoxu Liu; Chenyi Li; Xueqing Yi; Bo Fu; M. J. Walker; Xiao-Ming Xu; Gang Sun; Cheng-Hsien Lin (Inflammopharmacology, 2020)

Transcellular Model for Neutral and Charged Nanoparticles Across an In Vitro Blood–Brain Barrier - Lin Zhang; Jie Fan; Guanglei Li; Zhaokai Yin; Bingmei M. Fu (Cardiovascular Engineering and Technology, 2020)

Os4BGlu14, a monolignol β-Glucosidase, negatively affects seed longevity by influencing primary metabolism in rice - Rui-Juan Ren; Pei Wang; Li-Na Wang; Jing-Ping Su; Lin-Jing Sun; Yue Sun; De-Fu Chen; Xi-Wen Chen (Plant Molecular Biology, 2020)

3′UTRs Regulate Mouse Ntrk2 mRNA Distribution in Cortical Neurons - Shangqin Chen; Jinjin Zhu; Peijun Li; Zhaonan Xia; Mengjing Tu; Zhenlang Lin; Baoji Xu; Xiaoqin Fu (Journal of Molecular Neuroscience, 2020)
There are two major isoforms of NTRK2 (neurotrophic receptor tyrosine kinase 2, or TrkB), full-length isoform with tyrosine kinase (TK) domain intact (+) and spliced isoform without tyrosine kinase domain (TK(−)). Within each isoform, there exist subtypes with minor modifications of the protein sequences. In human, the NTRK2 mRNA transcripts encoding TK(+) have same 3′UTRs, while the transcripts encoding subtypes of NTRK2 TK(−) have two completely different 3′UTRs. In mouse, the mRNA transcripts encoding same NTRK2 protein sequence for either TK(+) or TK(−) have long or short 3′UTRs, respectively. The physiological functions of these different 3′UTRs are still unknown. Pilocarpine stimulation increased Ntrk2 mRNA levels in soma, while the increase in synaptosome was smaller. FISH results further showed that mouse Ntrk2 transcripts with different 3′UTRs were distributed differently in cultured cortical neurons. The transcripts with long 3′UTR were distributed more in apical dendrites compared with transcripts with short 3′UTR. Our results provide evidence of non-coding 3′UTR function in regulating mRNA distribution in neurons.

Whether the carbon emission from green roofs can be effectively mitigated by recycling waste building material as green roof substrate during five-year operation? - Liangqian Fan; Jingting Wang; Xiaoling Liu; Hongbing Luo; Ke Zhang; Xiaoying Fu; Mei Li; Xiaoting Li; Bing Jiang; Jia Chen; Shuzhi Fu; You Mo; et al. (Environmental Science and Pollution Research, 2020)

Prenylated isoflavones with potential antiproliferative activities from Mappianthus iodoides - Yan-Ping Liu; Li-Li Sun; Xiang-Lin Zhang; Hai-Yuan Niu; Zheng-Hong Pan; Yan-Hui Fu (Natural Product Research, 2020)

Initial chest CT findings in COVID-19: correlation with clinical features - Zhu-jing Shen; Nan Lu; Lu-lu Gao; Jian Lv; Hua-fu Luo; Ji-feng Jiang; Chao Xu; Shi-ya Li; Ju-jiang Mao; Kai Li; Xiao-pei Xu; Bin Lin (Journal of Zhejiang University-SCIENCE B, 2020)

Dynamics of radial oxygen loss in mangroves subjected to waterlogging - Hao Cheng; Mei-Lin Wu; Chang-Da Li; Fu-Lin Sun; Cui-Ci Sun; You-Shao Wang (Ecotoxicology, 2020)

Mechanical properties of soft soils experiencing lateral unloading under initial excess pore water pressure - Wei Huang; Kejun Wen; Junjie Li; Xuemei Fu; Shihui Liu; Yang Li; Lin Li; Farshad Amini (Arabian Journal of Geosciences, 2020)

A new 5α,8α-epidioxysterol with immunosuppressive activity from the South China Sea soft coral Sinularia sp. - Min Yang; Lin-Fu Liang; Heng Li; Wei Tang; Yue-Wei Guo (Natural Product Research, 2020)

Spatial Relationships of Water Resources with Energy Consumption at Coal Mining Operations in China - Gang Lin; Dong Jiang; Jingying Fu; Donglin Dong; Wenjie Sun; Xiang Li (Mine Water and the Environment, 2020)

Influence of Aphis gossypii feeding on defense strategy of native and introduced populations of Ageratina adenophora - Ying Lin; Shu-Qi He; Zhi-Hui Lu; Yu-Lin Gao; Yan-Ru Duan; Zheng-Yue Li; Bin Chen; Fu-Rong Gui (Arthropod-Plant Interactions, 2020)

Plastic pollution in croplands threatens long‐term food security - Dan Zhang; Ee Ling Ng; Wanli Hu; Hongyuan Wang; Pablo Galaviz; Hude Yang; Wentao Sun; Chongxiao Li; Xingwang Ma; Bin Fu; Peiyi Zhao; Fulin Zhang; et al. (Global Change Biology, 2020)
Plastic pollution is a global concern given its prevalence in aquatic and terrestrial ecosystems. Studies have been conducted on the distribution and impact of plastic pollution in marine ecosystems, but little is known on terrestrial ecosystems. Plastic mulch has been widely used to increase crop yields worldwide, yet the impact of plastic residues in cropland soils to soil health and crop production in the long term remained unclear. In this paper, using a global meta‐analysis, we found that the use of plastic mulch can indeed increase crop yields on average by 25%–42% in the immediate season due to the increase of soil temperature (+8%) and moisture (+17%). However, the unabated accumulation of film residues in the field negatively impacts its physicochemical properties linked to healthy soil and threatens food production in the long term. It has multiple negative impacts on plant growth including crop yield (at the mean rate of −3% for every additional 100 kg/ha of film residue), plant height (−2%) and root weight (−5%), and soil properties including soil water evaporation capacity (−2%), soil water infiltration rate (−8%), soil organic matter (−0.8%) and soil available phosphorus (−5%) based on meta‐regression. Using a nationwide field survey of China, the largest user of plastic mulch worldwide, we found that plastic residue accumulation in cropland soils has reached 550,800 tonnes, with an estimated 6%–10% reduction in cotton yield in some polluted sites based on current level of plastic residue content. Immediate actions should be taken to ensure the recovery of plastic film mulch and limit further increase in film residue loading to maintain the sustainability of these croplands.

Reduction of Human DNA Contamination in Clinical Cerebrospinal Fluid Specimens Improves the Sensitivity of Metagenomic Next-Generation Sequencing - Xin-Chao Ji; Lin-Fu Zhou; Chao-Yang Li; Ya-Jun Shi; Meng-Li Wu; Yun Zhang; Xiao-Fei Fei; Gang Zhao (Journal of Molecular Neuroscience, 2020)

Serum Uric Acid Levels and Risk of Intracranial Atherosclerotic Stenosis: A Cross-Sectional Study - Lin Li; Jun-Xia Zhu; Xiao-He Hou; Ya-Hui Ma; Wei Xu; Chen-Chen Tan; Fu-Rong Sun; Hong-Qi Li; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Photoprotection capacity of microalgae improved by regulating the antenna size of light-harvesting complexes - Guang-Rong Hu; Yong Fan; Yan-Lin Zheng; Feng Xu; Lei Zhang; Fu-Li Li (Journal of Applied Phycology, 2020)

Oil palm plantation mapping from high-resolution remote sensing images using deep learning - Runmin Dong; Weijia Li; Haohuan Fu; Lin Gan; Le Yu; Juepeng Zheng; Maocai Xia (International Journal of Remote Sensing, 2020)

Growth factor regulatory system: a new system for not truly recognized organisms - Jian Xiao; Zhuofeng Lin; Hua Qin; Zhilong Zheng; Fanghua Gong; Yanlong Liu; Xiaokun Li; Xiaobing Fu (Science China Life Sciences, 2020)

An on-demand construction method of disaster scenes for multilevel users - Weilian Li; Jun Zhu; Yunhao Zhang; Lin Fu; Yuhang Gong; Ya Hu; Yungang Cao (Natural Hazards, 2020)

Combined GWAS and QTL analysis for dissecting the genetic architecture of kernel test weight in maize - Xiaoxiang Zhang; Zhongrong Guan; Lei Wang; Jun Fu; Yinchao Zhang; Zhaoling Li; Langlang Ma; Peng Liu; Yanling Zhang; Min Liu; Peng Li; Chaoying Zou; et al. (Molecular Genetics and Genomics, 2020)

Prolonged Neo-Tethyan magmatic arc in Myanmar: evidence from geochemistry and Sr–Nd–Hf isotopes of Cretaceous mafic–felsic intrusions in the Banmauk–Kawlin area - Jin-Xiang Li; Wei-Ming Fan; Li-Yun Zhang; Tou-Ping Peng; Ya-Li Sun; Lin Ding; Fu-Long Cai; Kyaing Sein (International Journal of Earth Sciences, 2020)

Vertical variation in Vibrio community composition in Sansha Yongle Blue Hole and its ability to degrade macromolecules - Bei Li; Jiwen Liu; Shun Zhou; Liang Fu; Peng Yao; Lin Chen; Zuosheng Yang; Xiaolei Wang; Xiao-Hua Zhang (Marine Life Science & Technology, 2020)
With the advantages of wide distribution, fast growth, and broad metabolic spectrum to organic carbon compounds, Vibrio may play an important role in organic carbon cycling. However, the ecological roles of Vibrio in many marine environments have not been explored. Here, the world’s deepest ‘blue hole’, the Sansha Yongle Blue Hole (SYBH) in the South China Sea, which is a geographically semi-enclosed environment featuring unique chemical characters, was investigated. The abundance, diversity and carbon source utilization capability of Vibrio were studied by quantification and high-throughput sequencing of Vibrio specific 16S rRNA genes and cultivation methods. The abundance of Vibrio in water column of the SYBH ranged from 3.78 × 10 4 to 7.35 × 10 6 16S rRNA gene copies L −1 . Free-living Vibrio was more abundant than particle-associated Vibrio (~ 1.20 × 10 6 versus~ 2.68 × 10 5 gene copies L −1 ), indicating that Vibrio prefers a free-living life style. The Vibrio assemblages showed clear vertical stratification and could be divided into three groups: aerobic-transition, middle anaerobic and bottom anaerobic zones. Dissolved oxygen (DO), temperature, pH and salinity were the main environmental factors affecting the abundance and community composition. Cultivated Vibrio demonstrated a degrading capability to various macromolecular substrates, including starch, Tween 20/40/80, DNA, gelatin, alginate, casein, chitin, lecithin, κ-carrageenan, mannan, xylan and hyaluronic acid. This suggests that Vibrio could produce a variety of highly active extracellular enzymes. Our study provides new insights into the distribution pattern and possible role in carbon cycle of Vibrio in the unique environment of a ‘blue hole’.

The acclimation of leaf photosynthesis of wheat and rice to seasonal temperature changes in T‐FACE environments - Chuang Cai; Gang Li; Lijun Di; Yunjie Ding; Lin Fu; Xuanhe Guo; Paul C. Struik; Genxing Pan; Haozheng Li; Weiping Chen; Weihong Luo; Xinyou Yin (Global Change Biology, 2020)
Crops show considerable capacity to adjust their photosynthetic characteristics to seasonal changes in temperature. However, how photosynthesis acclimates to changes in seasonal temperature under future climate conditions has not been revealed. We measured leaf photosynthesis ( A n ) of wheat ( Triticum aestivum L.) and rice ( Oryza sativa L.) grown under four combinations of two levels of CO 2 (ambient and enriched up to 500 µmol/mol) and two levels of canopy temperature (ambient and increased by 1.5–2.0°C) in temperature by free‐air CO 2 enrichment (T‐FACE) systems. Parameters of a biochemical C 3 ‐photosynthesis model and of a stomatal conductance ( g s ) model were estimated for the four conditions and for several crop stages. Some biochemical parameters related to electron transport and most g s parameters showed acclimation to seasonal growth temperature in both crops. The acclimation response did not differ much between wheat and rice, nor among the four treatments of the T‐FACE systems, when the difference in the seasonal growth temperature was accounted for. The relationships between biochemical parameters and leaf nitrogen content were consistent across leaf ranks, developmental stages, and treatment conditions. The acclimation had a strong impact on g s model parameters: when parameter values of a particular stage were used, the model failed to correctly estimate g s values of other stages. Further analysis using the coupled g s –biochemical photosynthesis model showed that ignoring the acclimation effect did not result in critical errors in estimating leaf photosynthesis under future climate, as long as parameter values were measured or derived from data obtained before flowering.

Regulation of Circadian Genes by the MAPK Pathway: Implications for Rapid Antidepressant Action - Xin-Ling Wang; Kai Yuan; Wen Zhang; Su-Xia Li; George Fu Gao; Lin Lu (Neuroscience Bulletin, 2020)

Soil particle-size distribution and aggregate stability of new reconstructed purple soil affected by soil erosion in overland flow - Feng-Lin Zuo; Xiao-Yan Li; Xiao-Fan Yang; Yang Wang; Yu-Jun Ma; Yu-Han Huang; Chao-Fu Wei (Journal of Soils and Sediments, 2020)

Nitrogen fertilizer enhances zinc and cadmium uptake by hyperaccumulator Sedum alfredii Hance - Ziwen Lin; Chunying Dou; Yongfu Li; Hailong Wang; Nabeel Khan Niazi; Shaobo Zhang; Dan Liu; Keli Zhao; Weijun Fu; Yongchun Li; Zhengqian Ye (Journal of Soils and Sediments, 2020)

Association between long-term occupational manganese exposure and bone quality among retired workers - Defu Li; Xiaoting Ge; Zhenfang Liu; Lulu Huang; Yanting Zhou; Peng Liu; Lian Qin; Suzhen Lin; Chaoqun Liu; Qingzhi Hou; Longman Li; Hong Cheng; et al. (Environmental Science and Pollution Research, 2020)

Characteristics and Prognosis of Talaromyces marneffei Infection in Non-HIV-Infected Children in Southern China - Jing Guo; Bing-Kun Li; Tian-Min Li; Fang-Lin Wei; Yu-Jiao Fu; Yan-Qing Zheng; Kai-Su Pan; Chun-Yang Huang; Cun-Wei Cao (Mycopathologia, 2019)

Microfluidic tools for lipid production and modification: a review - Jin-Zheng Wang; Lin-Lin Zhu; Fan Zhang; Richard Ansah Herman; Wen-Jing Li; Xue-Jiao Zhou; Fu-An Wu; Jun Wang (Environmental Science and Pollution Research, 2019)

Expression of AHI1 Rescues Amyloidogenic Pathology in Alzheimer’s Disease Model Cells - Lai-Lei Ting; Hsien-Tsung Lu; Shu-Fen Yen; Thi Huong Ngo; Fang-Yu Tu; I-Shih Tsai; Yi-Hua Tsai; Fu-Yen Chang; Xiao-Jiang Li; Shihua Li; Ching-Kuo Lee; Shu-Huei Kao; et al. (Molecular Neurobiology, 2019)

Eco-friendly preparation of chitooligosaccharides with different degrees of deacetylation from shrimp shell waste and their effects on the germination of wheat seeds - Xiaodan Fu; Lin Zhu; Li Li; Tan Zhang; Meng Li; Haijin Mou (Marine Life Science & Technology, 2019)
Production of chitosan and its derivatives by traditional methods involves the excessive use of a reaction solution comprised of sodium hydroxide and hydrochloric acid. Waste water resulting from this process has limited the application of chitosan as a fertilizer as the process causes serious environmental pollution. Specifically, the resulting waste water contains high levels of dissolved nitrogen and minerals from shrimp shells. In this study, an eco-friendly method was established to produce chitooligosaccharides (COS) with different degrees of deacetylation (DDAs) from shrimp shell waste. At a solid-to-solvent ratio of 1:6, the degree of demineralization was above 90% with the treatment of 30 g·L −1 H 3 PO 4 , and the degree of deproteinization was above 80% when treated with 30 g·L −1 KOH at 70 °C. Chitosans with different DDAs were obtained by microwave-assisted KOH metathesis and the COS with Mw approximately 1500 Da were then prepared by oxidative degradation. In summary, 33.73 kg H 3 PO 4 , 12.77 kg, and 241.31 kg KOH were supplied during the processes of demineralization, deproteinization, and deacetylation of 100 kg shrimp shell waste, respectively. The process water was totally recycled, demonstrating that the shrimp shell could be wholly transformed into fertilizer. The entire process created a product with the fractions of N:P 2 O 5 :K 2 O:COS = 7.94:24.44:10.72:18.27. The test on the germination promotion of wheat seeds revealed that the COS with 72.12% DDA significantly promoted germination. This work demonstrated the use of an eco-friendly preparation method of COS with a specific degree of deacetylation that can be applied as a fertilizer.

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

Neural Stem Cells Transfected with Leukemia Inhibitory Factor Promote Neuroprotection in a Rat Model of Cerebral Ischemia - Lili Tian; Wenli Zhu; Yuanchu Liu; Ye Gong; Aowei Lv; Zhen Wang; Xiaoli Ding; Shaowu Li; Ying Fu; Yi Lin; Yaping Yan (Neuroscience Bulletin, 2019)

Identifying spatial heterogeneity of groundwater and its response to anthropogenic activities - Zhi-wei Wang; Hua-wei Chen; Fu-lin Li (Environmental Science and Pollution Research, 2019)

Four LysR-type transcriptional regulator family proteins (LTTRs) involved in antibiotic resistance in Aeromonas hydrophila - Yuying Fu; Qilan Cai; Yuqian Wang; Wanxin Li; Jing Yu; Guidi Yang; Wenxiong Lin; Xiangmin Lin (World Journal of Microbiology and Biotechnology, 2019)

Extensive changes in gene expression and alternative splicing due to homoeologous exchange in rice segmental allopolyploids - Zhibin Zhang; Tiansi Fu; Zhijian Liu; Xutong Wang; Hongwei Xun; Guo Li; Baoxu Ding; Yuzhu Dong; Xiuyun Lin; Karen A. Sanguinet; Bao Liu; Ying Wu; et al. (Theoretical and Applied Genetics, 2019)

Extreme stress threatened double rice production in Southern China during 1981–2010 - Sheng-Li Liu; Xing Wang; Shou-Tian Ma; Xin Zhao; Fu Chen; Xiao-Ping Xiao; Rattan Lal; Hai-Lin Zhang (Theoretical and Applied Climatology, 2019)

Dynamics of MiRNA Transcriptome in Turbot (Scophthalmus maximus L.) Intestine Following Vibrio anguillarum Infection - Chengbin Gao; Xin Cai; Qiang Fu; Ning Yang; Lin Song; Baofeng Su; Fenghua Tan; Baining Liu; Chao Li (Marine Biotechnology, 2019)

The Mechanism of Rap1 Regulates N-cadherin to Control Neuronal Migration - Ciqing Yang; Xiaoying Li; Bichao Zhang; Sulei Fu; Shuanqing Li; Jianing Shen; Lihong Guan; Liang Qiao; Juntang Lin (Journal of Molecular Neuroscience, 2019)

Role of Pigment Epithelium-Derived Factor in Arsenic-Induced Vascular Endothelial Dysfunction in a Rat Model - Xiangnan Guo; Xiaoyan Fu; Xiaona Liu; Jingqiu Wang; Zhongzhe Li; Lin Gao; Yuanyuan Li; Wei Zhang (Biological Trace Element Research, 2019)

F‐box proteins MoFwd1, MoCdc4 and MoFbx15 regulate development and pathogenicity in the rice blast fungus Magnaporthe oryzae - Huan‐Bin Shi; Nan Chen; Xue‐Ming Zhu; Shuang Liang; Lin Li; Jiao‐Yu Wang; Jian‐Ping Lu; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2019)
Summary The Skp1‐Cul1‐F‐box‐protein (SCF) ubiquitin ligases are important parts of the ubiquitin system controlling many cellular biological processes in eukaryotes. However, the roles of SCF ubiquitin ligases remain unclear in phytopathogenic Magnaporthe oryzae . Here, we cloned 24 F‐box proteins and confirmed that 17 proteins could interact with MoSkp1, showing their potential to participate in SCF complexes. To determine their functions, null mutants of 21 F‐box‐containing genes were created. Among them, the F‐box proteins MoFwd1, MoCdc4 and MoFbx15 were found to be required for growth, development and full virulence. Fluorescent‐microscopy observations demonstrated that both MoFbx15 and MoCdc4 were localized to the nucleus, compared with MoFwd1, which was distributed in the cytosol. MoCdc4 and MoFwd1 bound to MoSkp1 via the F‐box domain, the deletion of which abrogated their function. Race tube and qRT‐PCR assays confirmed that MoFwd1 was involved in circadian rhythm by regulating transcription and protein stability of the core circadian clock regulator MoFRQ . Moreover, MoFWD1 also orchestrates conidial germination by influencing conidial amino acids pools and oxidative stress release. Overall, our results indicate that SCF ubiquitin ligases play indispensable roles in development and pathogenicity in M. oryzae .

The associations of air pollution exposure during pregnancy with fetal growth and anthropometric measurements at birth: a systematic review and meta-analysis - Li Fu; Yi Chen; Xinyi Yang; Zuyao Yang; Sha Liu; Lei Pei; Baixiang Feng; Ganxiang Cao; Xin Liu; Hualiang Lin; Xing Li; Yufeng Ye; et al. (Environmental Science and Pollution Research, 2019)

Neural Differentiation of Mouse Neural Stem Cells as a Tool to Assess Developmental Neurotoxicity of Drinking Water in Taihu Lake - Yang Zhou; Yu Fu; Zhendong Bai; Peixin Li; Bo Zhao; Yuehua Han; Ting Xu; Ningyan Zhang; Lin Lin; Jian Cheng; Jun Zhang; Jing Zhang (Biological Trace Element Research, 2019)

Evaluation of the integrated multi-satellite retrievals for global precipitation measurement over the Tibetan Plateau - Lu Ma; Lin Zhao; Li-ming Tian; Li-ming Yuan; Yao Xiao; Le-le Zhang; De-fu Zou; Yong-ping Qiao (Journal of Mountain Science, 2019)

Complement Complex C5b-9 Levels Are Associated with the Clinical Outcomes of Acute Ischemic Stroke and Carotid Plaque Stability - Weixin Si; Pingping He; Yi Wang; Yu Fu; Xin Li; Xiaoru Lin; Fenghua Chen; Guodong Cao; Hong Zhang (Translational Stroke Research, 2019)

Exosomal long non-coding RNAs: biological properties and therapeutic potential in cancer treatment - Jie Luo; Yan Xiong; Pei-fen Fu; En-chun Li; Lei Qu; Xiao Fan; Zhi-jian Cai; Ai-fu Lin (Journal of Zhejiang University-SCIENCE B, 2019)

Novel mutations in ZP1, ZP2, and ZP3 cause female infertility due to abnormal zona pellucida formation - Zhou Zhou; Caixia Ni; Ling Wu; Biaobang Chen; Yao Xu; Zhihua Zhang; Jian Mu; Bin Li; Zheng Yan; Jing Fu; Wenjing Wang; Lin Zhao; et al. (Human Genetics, 2019)

A new triterpene diglycoside from the roots of Bupleurum chinense DC. and its inhibitory effect on adipogensis in 3T3-L1 cells - Yujing Feng; Zhou-Wei Wu; Yanyan Luo; Liang Chen; Yufeng Cao; Lun Wang; Aftab Yaseen; Bin Chen; Ashfaq Ahmad Khan; Ming-Kui Wang; Guo-Lin Zhang; Xin-Feng Wang; et al. (Medicinal Chemistry Research, 2019)

Programmed cell death induced by cadmium stress and/or boron deprivation in tobacco (Nicotiana tabacum L.) cultivar Bright Yellow 2 cells - Li Ping Jiang; Lin Zi; Xiao Fang Liu; Zi-Xi Liu; Lai Fu Zhong; Xiang Xin Xue (In Vitro Cellular & Developmental Biology - Plant, 2019)

Mining for genes encoding proteins associated with NopL of Sinorhizobium fredii HH103 using quantitative trait loci in soybean (Glycine max Merr.) recombinant inbred lines - Yanjiao Zhang; Xueying Liu; Lin Chen; Ying Fu; Changyu Li; Zhaoming Qi; Jianan Zou; Rongsheng Zhu; Shuping Li; Wei Wei; Jinhui Wang; Huilin Chang; et al. (Plant and Soil, 2018)

Lack of Association Between DNMT3B Polymorphisms and Sporadic Parkinson’s Disease in a Han Chinese Population - Hong Pan; Jun-Yi Shen; Juan-Juan Du; Shi-Shuang Cui; Jin Liu; Yi-Qi Lin; Yi-Xi He; Yang Fu; Chao Gao; Gen Li; Sheng-Di Chen; Jian-Fang Ma (Neuroscience Bulletin, 2018)

Aeromonas veronii and aerolysin are important for the pathogenesis of motile aeromonad septicemia in cyprinid fish - Chao Ran; Chubin Qin; Mingxu Xie; Jinxiong Zhang; Jie Li; Yadong Xie; Yibing Wang; Shuning Li; Lihui Liu; Xiaozhe Fu; Qiang Lin; Ningqiu Li; et al. (Environmental Microbiology, 2018)
Summary Aeromonas species are ubiquitous inhabitants of freshwater environments, and are responsible for fish motile aeromonad septicemia (MAS). A. hydrophila is implicated as the primary etiologic agent of MAS. Here, we analysed MAS epidemiological data for cyprinid fish in southern China, and found that A. veronii infections dominated. Consistent with this observation, A. veronii isolates were generally more virulent than A. hydrophila isolates when infecting germ‐free zebrafish larvae via continuous immersion challenge. Through in vivo screening of the transposon library of the A. veronii strain Hm091, aerolysin was identified as the key virulence factor. Further results indicated that A. veronii Hm091 aerolysin disrupts the intestinal barrier of zebrafish, enabling systematic invasion by not only A. veronii Hm091 in a mono‐infection, but also A. hydrophila NJ‐1 in a mixed infection. Moreover, the differences in aerolysin expression and activity were the major contributor to the observed differences between the A. veronii and A. hydrophila strains regarding invasion efficacy via intestine. Together, our results provide new insights into the aetiology and pathogenesis of Aeromonas infections, and highlight the importance of A. veronii ‐targeted treatments in future efforts against MAS.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Impact of mixed anthropogenic and natural emissions on air quality and eco-environment—the major water-soluble components in aerosols from northwest to offshore isle - Yilun Jiang; Guoshun Zhuang; Qiongzhen Wang; Kan Huang; Congrui Deng; Guangyuan Yu; Chang Xu; Qingyan Fu; Yanfen Lin; Joshua S. Fu; Mei Li; Zhen Zhou (Air Quality, Atmosphere & Health, 2018)

Eriodictyol protects against Staphylococcus aureus-induced lung cell injury by inhibiting alpha-hemolysin expression - He Xuewen; Ouyang Ping; Yuan Zhongwei; Yin Zhongqiong; Fu Hualin; Lin Juchun; He Changliang; Shu Gang; Yuan Zhixiang; Song Xu; Zou Yuanfeng; Li Lixia; et al. (World Journal of Microbiology and Biotechnology, 2018)

Converting natural evergreen broadleaf forests to intensively managed moso bamboo plantations affects the pool size and stability of soil organic carbon and enzyme activities - Ziwen Lin; Yongfu Li; Caixian Tang; Yu Luo; Weijun Fu; Xiaoqing Cai; Yongchun Li; Tian Yue; Peikun Jiang; Shuaidong Hu; Scott X. Chang (Biology and Fertility of Soils, 2018)

Laboratory tests and numerical simulations on the impact of subsurface barriers to saltwater intrusion - Fu-lin Li; Xue-qun Chen; Cai-hong Liu; Yan-qing Lian; Li He (Natural Hazards, 2018)

Neural Stem Cell Transplantation Promotes Functional Recovery from Traumatic Brain Injury via Brain Derived Neurotrophic Factor-Mediated Neuroplasticity - Liu-Lin Xiong; Yue Hu; Piao Zhang; Zhuo Zhang; Li-Hong Li; Guo-Dong Gao; Xin-Fu Zhou; Ting-Hua Wang (Molecular Neurobiology, 2018)

HAP1 Is Required for Endocytosis and Signalling of BDNF and Its Receptors in Neurons - Yoon Lim; Linda Lin-Yan Wu; Si Chen; Ying Sun; Swarna Lekha Vijayaraj; Miao Yang; Larisa Bobrovskaya; Damien Keating; Xiao-Jiang Li; Xin-Fu Zhou (Molecular Neurobiology, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

Modulation of ARTS and XIAP by Parkin Is Associated with Carnosic Acid Protects SH-SY5Y Cells against 6-Hydroxydopamine-Induced Apoptosis - Ru-Huei Fu; Li-Chun Huang; Chia-Yuan Lin; Chia-Wen Tsai (Molecular Neurobiology, 2018)

Effects of biochar application in forest ecosystems on soil properties and greenhouse gas emissions: a review - Yongfu Li; Shuaidong Hu; Junhui Chen; Karin Müller; Yongchun Li; Weijun Fu; Ziwen Lin; Hailong Wang (Journal of Soils and Sediments, 2018)

Effect of the dark septate endophytic fungus Acrocalymma vagum on heavy metal content in tobacco leaves - Hui-Qing Jin; Hua-Bing Liu; Ying-Ying Xie; Yong-Gang Zhang; Qing-Quan Xu; Li-Juan Mao; Xin-Jun Li; Jin Chen; Fu-Cheng Lin; Chu-Long Zhang (Symbiosis, 2018)

Physical interactions and mutational analysis of MoYpt7 in Magnaporthe oryzae - Lu-yao Huang; Min Wu; Xiao-yun Yu; Lin Li; Fu-cheng Lin; Xiao-hong Liu (Journal of Zhejiang University-SCIENCE B, 2018)

Tamoxifen usage correlates with increased risk of Parkinson’s disease in older women with breast cancer: a case–control study in Taiwan - Hsien-Feng Lin; Kuan-Fu Liao; Ching-Mei Chang; Cheng-Li Lin; Shih-Wei Lai (European Journal of Clinical Pharmacology, 2018)

Lipid accumulation and anti-rotifer robustness of microalgal strains isolated from Eastern China - Cheng Yuan; Yan-Lin Zheng; Wan-Lu Zhang; Ru He; Yong Fan; Guang-Rong Hu; Fu-Li Li (Journal of Applied Phycology, 2017)

Association of use of selective serotonin reuptake inhibitors with risk of acute pancreatitis: a case-control study in Taiwan - Hsien-Feng Lin; Kuan-Fu Liao; Ching-Mei Chang; Cheng-Li Lin; Shih-Wei Lai (European Journal of Clinical Pharmacology, 2017)

First evidence of pyrrolizidine alkaloid N-oxide-induced hepatic sinusoidal obstruction syndrome in humans - Mengbi Yang; Jianqing Ruan; Hong Gao; Na Li; Jiang Ma; Junyi Xue; Yang Ye; Peter Pi-Cheng Fu; Jiyao Wang; Ge Lin (Archives of Toxicology, 2017)

Molecular diversity of phenothiazines: design and synthesis of phenothiazine–dithiocarbamate hybrids as potential cell cycle blockers - Dong-Jun Fu; Ruo-Han Zhao; Jia-Huan Li; Jia-Jia Yang; Ruo-Wang Mao; Bo-Wen Wu; Ping Li; Xiao-Lin Zi; Qing-Qing Zhang; Hui-Jie Cai; Sai-Yang Zhang; Yan-Bing Zhang; et al. (Molecular Diversity, 2017)

Exploring the Potential of Naturalized Plants for Phytoremediation of Heavy Metal Contamination - Wei Fu; Kai Huang; Hong-Hong Cai; Jian Li; De-Li Zhai; Zhi-Cong Dai; Dao-Lin Du (International Journal of Environmental Research, 2017)

Impacts of precipitation variation and soil and water conservation measures on runoff and sediment yield in the Loess Plateau Gully Region, China - Lu Xia; Xiao-yu Song; Na Fu; Chun-fang Meng; Huai-you Li; Yao-lin Li (Journal of Mountain Science, 2017)

The biological features and genetic diversity of novel fish rhabdovirus isolates in China - Xiaozhe Fu; Qiang Lin; Hongru Liang; Lihui Liu; Zhibin Huang; Ningqiu Li; Jianguo Su (Archives of Virology, 2017)

Associations of rs3740677 within GAB2 Gene with LOAD in Chinese Han Population - Jing-Yu Zheng; Hui-Fu Wang; Yu Wan; Meng-Shan Tan; Chen-Chen Tan; Lin Tan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Correlation between proton pump inhibitors and risk of pyogenic liver abscess - Hsien-Feng Lin; Kuan-Fu Liao; Ching-Mei Chang; Cheng-Li Lin; Shih-Wei Lai (European Journal of Clinical Pharmacology, 2017)

Expression-based genotyping of the rice blast resistance genes in the elite maintainer line Yixiang1B - Li Wang; Xiao-Hong Hu; Gang Lin; De-Ming Zhao; Jun Shi; Zhi-Xue Zhao; Rui Zeng; Heng-Jing Li; De-Qiang Li; Jing Fan; Yan Li; Fu Huang; et al. (European Journal of Plant Pathology, 2017)

Developing the science product algorithm testbed for Chinese next-generation geostationary meteorological satellites: Fengyun-4 series - Min Min; Chunqiang Wu; Chuan Li; Hui Liu; Na Xu; Xiao Wu; Lin Chen; Fu Wang; Fenglin Sun; Danyu Qin; Xi Wang; Bo Li; et al. (Journal of Meteorological Research, 2017)

Association of DISC1 Polymorphisms with Late-Onset Alzheimer’s Disease in Northern Han Chinese - Xiao-Yan Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Ling-Li Kong; Zhan-Jie Zheng; Chen-Chen Tan; Wei Zhang; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; et al. (Molecular Neurobiology, 2017)

Future Science Prize goes to non-invasive prenatal testing - Kang Li; Yaou Duan; Magdalene Yin Lin Ting; Zhiying Ou; Li Liu; Kang Zhang; Xin Fu (Science China Life Sciences, 2017)

SORL1 Is Associated with the Risk of Late-Onset Alzheimer’s Disease: a Replication Study and Meta-Analyses - Cheng-Cheng Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Erratum to: Down-regulation of miR-181a can reduce heat stress damage in PBMCs of Holstein cows - Kun-Lin Chen; Yuan-Yuan Fu; Min-Yan Shi; Hui-Xia Li (In Vitro Cellular & Developmental Biology - Animal, 2017)

Risk of parkinsonism induced by flunarizine or cinnarizine: a population-based study - Hsiu-Li Lin; Hsiu-Chen Lin; Yuan-Fu Tseng; Shih-Chang Chen; Chien-Yeh Hsu (European Journal of Clinical Pharmacology, 2017)

Evolution Mechanism and Rainfall Warning Criteria for Maijianwo Slope in Henan Province, China - Yi-heng Pan; Jian-ping Chen; Li-qing Wu; Wei Wang; Fu-lin Tan (Geotechnical and Geological Engineering, 2017)

Analysis of QTL for seed oil content in Brassica napus by association mapping and QTL mapping - Ying Fu; Dongqing Zhang; Madeleine Gleeson; Yaofeng Zhang; Baogang Lin; Shuijin Hua; Houdong Ding; Martin Frauen; Jiana Li; Wei Qian; Huasheng Yu (Euphytica, 2017)

GEM: a dynamic tracking model for mesoscale eddies in the ocean - Qiu-Yang Li; Liang Sun; Sheng-Fu Lin (Ocean Science, 2016)
The Genealogical Evolution Model (GEM) presented here is an efficient logical model used to track dynamic evolution of mesoscale eddies in the ocean. It can distinguish between different dynamic processes (e.g., merging and splitting) within a dynamic evolution pattern, which is difficult to accomplish using other tracking methods. To this end, the GEM first uses a two-dimensional (2-D) similarity vector (i.e., a pair of ratios of overlap area between two eddies to the area of each eddy) rather than a scalar to measure the similarity between eddies, which effectively solves the “missing eddy” problem (temporarily lost eddy in tracking). Second, for tracking when an eddy splits, the GEM uses both “parent” (the original eddy) and “child” (eddy split from parent) and the dynamic processes are described as the birth and death of different generations. Additionally, a new look-ahead approach with selection rules effectively simplifies computation and recording. All of the computational steps are linear and do not include iteration. Given the pixel number of the target region L, the maximum number of eddies M, the number N of look-ahead time steps, and the total number of time steps T, the total computer time is O(LM(N + 1)T). The tracking of each eddy is very smooth because we require that the snapshots of each eddy on adjacent days overlap one another. Although eddy splitting or merging is ubiquitous in the ocean, they have different geographic distributions in the North Pacific Ocean. Both the merging and splitting rates of the eddies are high, especially at the western boundary, in currents and in “eddy deserts”. The GEM is useful not only for satellite-based observational data, but also for numerical simulation outputs. It is potentially useful for studying dynamic processes in other related fields, e.g., the dynamics of cyclones in meteorology.

N-cadherin regulates beta-catenin signal and its misexpression perturbs commissural axon projection in the developing chicken spinal cord - Ciqing Yang; Xiaoying Li; Congrui Wang; Sulei Fu; Han Li; Zhikun Guo; Shanting Zhao; Juntang Lin (Journal of Molecular Histology, 2016)

A novel bocavirus from domestic mink, China - Shixing Yang; Yan Wang; Wang Li; Zhaobin Fan; Lili Jiang; Yuan Lin; Xingli Fu; Quan Shen; Zixuan Sun; Xiaochun Wang; Xutao Deng; Wen Zhang; et al. (Virus Genes, 2016)

Secondary metabolites from marine-derived Streptomyces antibioticus strain H74-21 - Shuna Fu; Fan Wang; Hongyu Li; Yixuan Bao; Yu Yang; Huifang Shen; Birun Lin; Guangxiong Zhou (Natural Product Research, 2016)

Permeability of novel 4′-N-substituted (aminomethyl) benzoate-7-substituted nicotinic acid ester derivatives of scutellarein in Caco-2 cells and in an in vitro model of the blood-brain barrier - Yu Ou; Min Luo; Yong-Xi Dong; Hang Su; Xiao-Zhong Fu; Yu-Feng Cha; Shun Zhang; Yong-Long Zhao; Yong-Jun Li; Yong-Lin Wang (Medicinal Chemistry Research, 2016)

Wnt5a mediated canonical Wnt signaling pathway activation in orthodontic tooth movement: possible role in the tension force-induced bone formation - Hai-Di Fu; Bei-Ke Wang; Zi-Qiu Wan; Heng Lin; Mao-Lin Chang; Guang-Li Han (Journal of Molecular Histology, 2016)

Down-regulation of miR-181a can reduce heat stress damage in PBMCs of Holstein cows - Kun-Lin Chen; Yuan-Yuan Fu; Min-Yan Shi; Hui-Xia Li (In Vitro Cellular & Developmental Biology - Animal, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Factorial Analysis of Variables Influencing Mechanical Characteristics in Le Fort I Osteotomy Using FEA and Statistics-Based Taguchi Method - Shao-Fu Huang; Lun-Jou Lo; Chun-Li Lin (Journal of Medical and Biological Engineering, 2016)

Suppression of dioxins by S-N inhibitors in pilot-scale experiments - Ming-Xiu Zhan; Jian-Ying Fu; Tong Chen; Xiao-Qing Lin; Xiao-Dong Li; Jian-Hua Yan; Alfons Buekens (Environmental Science and Pollution Research, 2016)

Education and Risk of Dementia: Dose-Response Meta-Analysis of Prospective Cohort Studies - Wei Xu; Lan Tan; Hui-Fu Wang; Meng-Shan Tan; Lin Tan; Jie-Qiong Li; Qing-Fei Zhao; Jin-Tai Yu (Molecular Neurobiology, 2016)

The adipokine Chemerin induces lipolysis and adipogenesis in bovine intramuscular adipocytes - Yuan-Yuan Fu; Kun-Lin Chen; Hui-Xia Li; Guang-Hong Zhou (Molecular and Cellular Biochemistry, 2016)

Cyanidin-3-O-glucoside Induces Apoptosis and Inhibits Migration of Tumor Necrosis Factor-α-Treated Rat Aortic Smooth Muscle Cells - Xuerui Yan; Lin Wu; Bin Li; Xianjun Meng; Hanping Dai; Yanan Zheng; Junfan Fu (Cardiovascular Toxicology, 2016)

Improvement and comparison of the rainfall–runoff methods in SWAT at the monsoonal watershed of Baocun, Eastern China - Qin-Bo Cheng; Christian Reinhardt-Imjela; Xi Chen; Achim Schulte; Xiang Ji; Fu-Lin Li (Hydrological Sciences Journal, 2016)

Silicon Alleviates Cadmium Toxicity in Two Cypress Varieties by Strengthening the Exodermis Tissues and Stimulating Phenolic Exudation of Roots - Bin Guo; Chen Liu; Nengfei Ding; Qinglin Fu; Yicheng Lin; Hua Li; Ningyu Li (Journal of Plant Growth Regulation, 2016)

Effects of seasonal variations on soil microbial community composition of two typical zonal vegetation types in the Wuyi Mountains - Ze-yan Wu; Wen-xiong Lin; Jian-juan Li; Jin-fu Liu; Bai-lian Li; Lin-kun Wu; Chang-xun Fang; Zhi-xing Zhang (Journal of Mountain Science, 2016)

Mechanism Underlying the Analgesic Effect Exerted by Endomorphin-1 in the rat Ventrolateral Periaqueductal Gray - Tao Chen; Jing Li; Ban Feng; Rui Hui; Yu-Lin Dong; Fu-Quan Huo; Ting Zhang; Jun-Bin Yin; Jian-Qing Du; Yun-Qing Li (Molecular Neurobiology, 2016)

Diversity of phototrophic phytoplankton in Northern South China Sea indicated by rbcL analysis - Nan Li; Shu-Xian Yu; Yin-Chu Wang; Jia-Lin Li; Fu-Chao Li; Song Qin (Journal of Applied Phycology, 2016)

New Re-Os isotopic constrains on the formation of the metalliferous deposits of the Lower Cambrian Niutitang formation - Yong Fu; Lin Dong; Chao Li; Wenjun Qu; Haoxiang Pei; Wenlang Qiao; Bing Shen (Journal of Earth Science, 2016)

Methane and nitrous oxide emissions under no‐till farming in China: a meta‐analysis - Xin Zhao; Sheng‐Li Liu; Chao Pu; Xiang‐Qian Zhang; Jian‐Fu Xue; Ran Zhang; Yu‐Qiao Wang; Rattan Lal; Hai‐Lin Zhang; Fu Chen (Global Change Biology, 2016)
No‐till ( NT ) practices are among promising options toward adaptation and mitigation of climate change. However, the mitigation effectiveness of NT depends not only on its carbon sequestration potential but also on soil‐derived CH 4 and N 2 O emissions. A meta‐analysis was conducted, using a dataset involving 136 comparisons from 39 studies in China, to identify site‐specific factors which influence CH 4 emission, CH 4 uptake, and N 2 O emission under NT . Comparative treatments involved NT without residue retention ( NT 0), NT with residue retention ( NTR ), compared to plow tillage ( PT ) with residue removed ( PT 0). Overall, NT 0 significantly decreased CH 4 emission by ~30% ( P 0.05) compared to PT 0 with an average emission 218.8 kg ha −1 for rice paddies. However, the increase in N 2 O emission could partly offset the benefits of the decrease in CH 4 emission under NT compared to PT 0. NTR significantly enhanced N 2 O emission by 82.1%, 25.5%, and 20.8% ( P 0.05) compared to PT 0 for rice paddies, acid soils, and the first 5 years of the experiments, respectively. The results from categorical meta‐analysis indicated that the higher N 2 O emission could be mitigated by adopting NT within alkaline soils, for long‐term duration, and with less N fertilization input when compared to PT 0. In addition, the natural log (lnR) of response ratio of CH 4 and N 2 O emissions under NT correlated positively (enhancing emission) with climate factors (temperature and precipitation) and negatively (reducing emission) with experimental duration, suggesting that avoiding excess soil wetness and using NT for a long term could enhance the benefits of NT . Therefore, a thorough understanding of the conditions favoring greenhouse gas(es) reductions is essential to achieving climate change mitigation and advancing food security in China.

QTL mapping of flag leaf traits in common wheat using an integrated high-density SSR and SNP genetic linkage map - Qiuhong Wu; Yongxing Chen; Lin Fu; Shenghui Zhou; Jiaojiao Chen; Xiaojie Zhao; Dong Zhang; Shuhong Ouyang; Zhenzhong Wang; Dan Li; Guoxin Wang; Deyun Zhang; et al. (Euphytica, 2016)

OsBAK1 is involved in rice resistance to Xanthomonas oryzae pv. oryzae PXO99 - Hualan Liao; Xiaorong Xiao; Xiuqiong Li; Yan Chen; Xiumei Fu; Daozhe Lin; Xiaolei Niu; Yinhua Chen; Chaozu He (Plant Biotechnology Reports, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Different Responses of an Invasive Clonal Plant Wedelia trilobata and its Native Congener to Gibberellin: Implications for Biological Invasion - Zhi-Cong Dai; Wei Fu; Shan-Shan Qi; De-Li Zhai; Si-Chong Chen; Ling-Yun Wan; Ping Huang; Dao-Lin Du (Journal of Chemical Ecology, 2016)

Metabolic differences of industrial acarbose-producing Actinoplanes sp. A56 under various osmolality levels - Kun-tai Li; Wei-fu Peng; Wei Xia; Lin Huang; Xin Cheng (World Journal of Microbiology and Biotechnology, 2016)

Synthesis, Characterization, Properties and DFT Calculations of 2-(Benzo[b]thiophen-2-yl)pyridine-based Iridium(III) Complexes with Different Ancillary Ligands - Gao-Nan Li; Yong-Pi Zeng; Kai-Xiu Li; Hao-Hua Chen; Hui Xie; Fu-Lin Zhang; Guang-Ying Chen; Zhi-Gang Niu (Journal of Fluorescence, 2016)

CTRP3 attenuates post-infarct cardiac fibrosis by targeting Smad3 activation and inhibiting myofibroblast differentiation - Dan Wu; Hong Lei; Jin-Yu Wang; Cheng-Lin Zhang; Han Feng; Feng-Ying Fu; Li Li; Li-Ling Wu (Journal of Molecular Medicine, 2015)

Two jasmonate-responsive factors, TcERF12 and TcERF15, respectively act as repressor and activator of tasy gene of taxol biosynthesis in Taxus chinensis - Meng Zhang; Shutao Li; Lin Nie; Qingpu Chen; Xiangping Xu; Longjiang Yu; Chunhua Fu (Plant Molecular Biology, 2015)

High-level expression and characterization of a thermophilic β-mannanase from Aspergillus niger in Pichia pastoris - Shi Yu; Zhezhe Li; Yaping Wang; Wanping Chen; Lin Fu; Wei Tang; Chen Chen; Yunyun Liu; Xue Zhang; Lixin Ma (Biotechnology Letters, 2015)

Effects of Fluoride on DNA Damage and Caspase-Mediated Apoptosis in the Liver of Rats - Guo Hua Song; Fu Bing Huang; Ji Ping Gao; Mao Lin Liu; Wen Biao Pang; Wei bin Li; Xiao Yan Yan; Mei Jun Huo; Xia Yang (Biological Trace Element Research, 2015)

Protective Effect of Apigenin on Ischemia/Reperfusion Injury of the Isolated Rat Heart - Jing Hu; Zilin Li; Li-ting Xu; Ai-jun Sun; Xiao-yan Fu; Li Zhang; Lin-lin Jing; An-dong Lu; Yi-fei Dong; Zheng-ping Jia (Cardiovascular Toxicology, 2015)

Increased relative risk of acute pancreatitis in zolpidem users - Shih-Wei Lai; Cheng-Li Lin; Kuan-Fu Liao (Psychopharmacology, 2015)

Associations Between ApoEε4 Carrier Status and Serum BDNF Levels—New Insights into the Molecular Mechanism of ApoEε4 Actions in Alzheimer’s Disease - Yu-Hui Liu; Shu-Sheng Jiao; Ye-Ran Wang; Xian-Le Bu; Xiu-Qing Yao; Yang Xiang; Qing-Hua Wang; Lin Wang; Juan Deng; Jing Li; Xin-Fu Zhou; Hua-Dong Zhou; et al. (Molecular Neurobiology, 2015)

Prauserella endophytica sp. nov., an endophytic actinobacterium isolated from Tamarix taklamakanensis - Jia-Meng Liu; Xugela Habden; Lin Guo; Li Tuo; Zhong-Ke Jiang; Shao-Wei Liu; Xian-Fu Liu; Li Chen; Rong-Feng Li; Yu-Qin Zhang; Cheng-Hang Sun (Antonie van Leeuwenhoek, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Challenges and adaptations of farming to climate change in the North China Plain - Hai-Lin Zhang; Xin Zhao; Xiao-Gang Yin; Sheng-Li Liu; Jian-Fu Xue; Meng Wang; Chao Pu; Rattan Lal; Fu Chen (Climatic Change, 2015)

Association of ACP1 gene polymorphisms and coronary artery disease in northeast Chinese population - TIANBAO LI; XUESONG XU; JIANZHUO LI; SHU XING; LIN ZHANG; WANNAN LI; JUNFENG MA; XUEQI FU (Journal of Genetics, 2015)

Distribution of PCDD/Fs in the fly ash and atmospheric air of two typical hazardous waste incinerators in eastern China - Tong Chen; Ming-xiu Zhan; Xiao-qing Lin; Jian-ying Fu; Sheng-yong Lu; Xiao-dong Li (Environmental Science and Pollution Research, 2015)

Genome re-sequencing suggested a weedy rice origin from domesticated indica-japonica hybridization: a case study from southern China - Jie Qiu; Jinwen Zhu; Fei Fu; Chu-Yu Ye; Weidi Wang; Linfeng Mao; Zhangxiang Lin; Li Chen; Haiqiang Zhang; Longbiao Guo; Shen Qiang; Yongliang Lu; et al. (Planta, 2014)

MiR-199a is overexpressed in plasma of type 2 diabetes patients which contributes to type 2 diabetes by targeting GLUT4 - Shuang-Tong Yan; Chun-Lin Li; Hui Tian; Jian Li; Yu Pei; Yu Liu; Yan-Ping Gong; Fu-Sheng Fang; Ban-Ruo Sun (Molecular and Cellular Biochemistry, 2014)

The caspase-8 shRNA-modified mesenchymal stem cells improve the function of infarcted heart - Yeyou Liang; Qiuxiong Lin; Jiening Zhu; Xiaohong Li; Yongheng Fu; Xiao Zou; Xiaoying Liu; Honghong Tan; Chunyu Deng; Xiyong Yu; Zhixin Shan; Weiwei Yuan (Molecular and Cellular Biochemistry, 2014)

miR-210 over-expression enhances mesenchymal stem cell survival in an oxidative stress environment through antioxidation and c-Met pathway activation - JianFeng Xu; ZheYong Huang; Li Lin; MingQiang Fu; YanHua Gao; YunLi Shen; YunZeng Zou; AiJun Sun; JuYing Qian; JunBo Ge (Science China Life Sciences, 2014)

Contamination and distribution of parent, nitrated, and oxygenated polycyclic aromatic hydrocarbons in smoked meat - Yuanchen Chen; Guofeng Shen; Shu Su; Huizhong Shen; Ye Huang; Tongchao Li; Wei Li; Yanyan Zhang; Yan Lu; Han Chen; Chunli Yang; Nan Lin; et al. (Environmental Science and Pollution Research, 2014)

Assessment of carbon sustainability under different tillage systems in a double rice cropping system in Southern China - Jian-Fu Xue; Sheng-Li Liu; Zhong-Du Chen; Fu Chen; Rattan Lal; Hai-Ming Tang; Hai-Lin Zhang (The International Journal of Life Cycle Assessment, 2014)

Effect of dietary lysine on growth, intestinal enzymes activities and antioxidant status of sub-adult grass carp (Ctenopharyngodon idella) - Xue-Yin Li; Ling Tang; Kai Hu; Yang Liu; Wei-Dan Jiang; Jun Jiang; Pei Wu; Gang-Fu Chen; Shu-Hong Li; Sheng-Yao Kuang; Lin Feng; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2014)

Effects of Dietary Selenium Deficiency on mRNA Levels of Twenty-One Selenoprotein Genes in the Liver of Layer Chicken - C. P. Liu; J. Fu; S. L. Lin; X. S. Wang; S. Li (Biological Trace Element Research, 2014)

Prevalence of human papillomavirus infection in esophageal and cervical cancers in the high incidence area for the two diseases from 2007 to 2009 in Linzhou of Henan Province, Northern China - Hong Yan Liu; Sheng Li Zhou; Jian Wei Ku; Dong Yun Zhang; Bei Li; Xue Na Han; Zong Min Fan; Ji Li Cui; Hong Li Lin; Er Tao Guo; Xi Chen; Yuan Yuan; et al. (Archives of Virology, 2014)

Determinants of public goods investment in rural communities in mountainous areas of Sichuan Province, China - Shi-li Guo; Shao-quan Liu; Ren-fu Luo; Lin-xiu Zhang (Journal of Mountain Science, 2014)

Sustained endoplasmic reticulum stress inhibits hepatocyte proliferation via downregulation of c-Met expression - Yihuai He; Jun Long; Weiwei Zhong; Yu Fu; Ying Li; Shide Lin (Molecular and Cellular Biochemistry, 2014)

Primordial follicle assembly was regulated by notch signaling pathway in the mice - Chun-Lei Chen; Xia-Fei Fu; Lin-Qing Wang; Jun-Jie Wang; Hua-Gang Ma; Shun-Feng Cheng; Zhu-Mei Hou; Jin-Mei Ma; Guo-Bo Quan; Wei Shen; Lan Li (Molecular Biology Reports, 2014)

Involvement of the nuclear factor-κB pathway in the adhesion of neutrophils to renal tubular cells after injury induced by neonatal postasphyxial serum - Tao Xiong; Wenbin Dong; Hui Fu; Qingping Li; Cunliang Deng; Xiaoping Lei; Lin Guo (Molecular and Cellular Biochemistry, 2014)

Screening of multi-copy mannanase recombinants of Pichia pastoris based on colony size - Jia Zheng; Ning Guo; Fu-lai Lin; Li-shuang Wu; Hong-bo Zhou (World Journal of Microbiology and Biotechnology, 2014)

Generation of GGTA1 biallelic knockout pigs via zinc-finger nucleases and somatic cell nuclear transfer - Lei Bao; HaiDe Chen; UiMyong Jong; CholHo Rim; WenLing Li; XiJuan Lin; Dan Zhang; Qiong Luo; Chun Cui; HeFeng Huang; Yan Zhang; Lei Xiao; et al. (Science China Life Sciences, 2014)

Microbial Source Tracking: A Tool for Identifying Sources of Microbial Contamination in the Food Chain - Ling-Lin Fu; Jian-Rong Li (Critical Reviews in Food Science and Nutrition, 2014)

Alda-1 reduces cerebral ischemia/reperfusion injury in rat through clearance of reactive aldehydes - Si-Hai Fu; Hong-Feng Zhang; Zhong-Bao Yang; Ting-Bo Li; Bin Liu; Zheng Lou; Qi-Lin Ma; Xiu-Ju Luo; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

miR-124 Represses ROCK1 Expression to Promote Neurite Elongation Through Activation of the PI3K/Akt Signal Pathway - Xi Gu; Siying Meng; Shuhu Liu; Chunhong Jia; Yingying Fang; Shuji Li; Congcong Fu; Qiancheng Song; Lifang Lin; Xuemin Wang (Journal of Molecular Neuroscience, 2014)

MicroRNA Expression Aberration in Chinese Patients with Relapsing Remitting Multiple Sclerosis - Dan Yang; Wei-Zhi Wang; Xue-Mei Zhang; Hui Yue; Bing Li; Lin Lin; Jin Fu (Journal of Molecular Neuroscience, 2014)

Regulation of Autophagy and Ubiquitinated Protein Accumulation by bFGF Promotes Functional Recovery and Neural Protection in a Rat Model of Spinal Cord Injury - Hong-Yu Zhang; Zhou-Guang Wang; Fen-Zan Wu; Xiao-Xia Kong; Jie Yang; Bei-Bei Lin; Shi-Ping Zhu; Li Lin; Chao-Shi Gan; Xiao-Bing Fu; Xiao-Kun Li; Hua-Zi Xu; et al. (Molecular Neurobiology, 2013)

Genetic variation in alkaloid accumulation in leaves of Nicotiana - Bo Sun; Fen Zhang; Guo-jun Zhou; Guo-hai Chu; Fang-fang Huang; Qiao-mei Wang; Li-feng Jin; Fu-cheng Lin; Jun Yang (Journal of Zhejiang University-SCIENCE B, 2013)

The short chain cell-permeable ceramide (C6) restores cell apoptosis and perifosine sensitivity in cultured glioblastoma cells - Li-sen Qin; Zheng-quan Yu; Shi-ming Zhang; Guan Sun; Jian Zhu; Jin Xu; Jun Guo; Lin-shan Fu (Molecular Biology Reports, 2013)

Functional analyses of a flavonol synthase–like gene from Camellia nitidissima reveal its roles in flavonoid metabolism during floral pigmentation - Xing-Wen Zhou; Zheng-Qi Fan; Yue Chen; Yu-Lin Zhu; Ji-Yuan Li; Heng-Fu Yin (Journal of Biosciences, 2013)

Bird species migration ratio in East Asia, Australia, and surrounding islands - Yiliang Kuo; Da-Li Lin; Fu-Man Chuang; Pei-Fen Lee; Tzung-Su Ding (The Science of Nature, 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Particle swarm optimization algorithm for analyzing SNP–SNP interaction of renin-angiotensin system genes against hypertension - Shyh-Jong Wu; Li-Yeh Chuang; Yu-Da Lin; Wen-Hsien Ho; Fu-Tien Chiang; Cheng-Hong Yang; Hsueh-Wei Chang (Molecular Biology Reports, 2013)

Molecular Characterization and Expression of Ethylene Biosynthetic Genes During Cut Flower Development in Tree Peony (Paeonia suffruticosa) in Response to Ethylene and Functional Analysis of PsACS1 in Arabidopsis thaliana - Lin Zhou; Chao Zhang; Jianxin Fu; Miao Liu; Yuhuan Zhang; Yanjie Wang; Li Dong (Journal of Plant Growth Regulation, 2013)

Catalog of Erycina pusilla miRNA and categorization of reproductive phase-related miRNAs and their target gene families - Choun-Sea Lin; Jeremy J. W. Chen; Yao-Ting Huang; Chen-Tran Hsu; Hsiang-Chia Lu; Ming-Lun Chou; Li-Chi Chen; Chia-I Ou; Der-Chih Liao; Ysuan-Yu Yeh; Song-Bing Chang; Su-Chen Shen; et al. (Plant Molecular Biology, 2013)

SIRT1 interacts with metabolic transcriptional factors in the pancreas of insulin-resistant and calorie-restricted rats - Yong-Ru Chen; Yu-lin Lai; Shao-da Lin; Xi-tao Li; Yu-Cai Fu; Wen-Can Xu (Molecular Biology Reports, 2013)

Screening Chinese soybean genotypes for Agrobacterium-mediated genetic transformation suitability - Zhang-yue Song; Jing-luan Tian; Wei-zhe Fu; Lin Li; Ling-hong Lu; Lian Zhou; Zhi-hui Shan; Gui-xiang Tang; Hui-xia Shou (Journal of Zhejiang University-SCIENCE B, 2013)

Anatomical adaptations of the xerophilous medicinal plant, Capparis spinosa, to drought conditions - Lu Gan; Chunyu Zhang; Yongtai Yin; Zhiwei Lin; Yongwei Huang; Jun Xiang; Chunhua Fu; Maoteng Li (Horticulture, Environment, and Biotechnology, 2013)

Comparison of early transcriptome responses to copper and cadmium in rice roots - Chung-Yi Lin; Ngoc Nam Trinh; Shih-Feng Fu; Yu-Chyuan Hsiung; Li-Chiao Chia; Chung-Wen Lin; Hao-Jen Huang (Plant Molecular Biology, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Erratum to: Novel glycine-dependent inactivation of NMDA receptors in cultured hippocampal neurons - Yun-Feng Zhang; Xia Li; Liang-Liang Peng; Guo-Hua Wang; Kai-Fu Ke; Zheng-Lin Jiang (Neuroscience Bulletin, 2013)

A New Vector for Identification of Prokaryotes and Their Variable-Size Genomes - Tao Hou; Fu Liu; Caixia X. Lin; Dingyuan Y. Li (Current Microbiology, 2013)

High density lipoprotein cholesterol promotes the proliferation of bone-derived mesenchymal stem cells via binding scavenger receptor-B type I and activation of PI3K/Akt, MAPK/ERK1/2 pathways - Jianfeng Xu; Juying Qian; Xinxing Xie; Li Lin; Jianying Ma; Zheyong Huang; Mingqiang Fu; Yunzeng Zou; Junbo Ge (Molecular and Cellular Biochemistry, 2012)

Novel glycine-dependent inactivation of NMDA receptors in cultured hippocampal neurons - Yun-Feng Zhang; Xia Li; Liang-Liang Peng; Guo-Hua Wang; Kai-Fu Ke; Zheng-Lin Jiang (Neuroscience Bulletin, 2012)

Effects of fertilization and drought stress on tannin biosynthesis of Casuarina equisetifolia seedlings branchlets - Li Hua Zhang; Hong Bo Shao; Gong Fu Ye; Yi Ming Lin (Acta Physiologiae Plantarum, 2012)

Molecular characterization of the PpMADS1 gene from peach - Cui Li; Hua Xie; Lin Zhang; Yong Xu; Yun-Fu Li; Rong-Cai Ma (Tree Genetics & Genomes, 2012)

Spatial variation of bacterial community structure of the Northern South China Sea in relation to water chemistry - Juan Ling; Jun-De Dong; You-Shao Wang; Yan-Ying Zhang; Chao Deng; Li Lin; Mei-Lin Wu; Fu-Lin Sun (Ecotoxicology, 2012)

Detrital zircon U-Pb geochronology and its provenance implications on Silurian Tarim basin - Jingyan Liu; Changsong Lin; Sitian Li; Zhenzhong Cai; Shiqiang Xia; Chao Fu; Yongquan Liu (Journal of Earth Science, 2012)

Celecoxib inhibits growth of human autosomal dominant polycystic kidney cyst-lining epithelial cells through the VEGF/Raf/MAPK/ERK signaling pathway - Tao Xu; Nian-Song Wang; Li-Li Fu; Chao-Yang Ye; Sheng-Qiang Yu; Chang-Lin Mei (Molecular Biology Reports, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Effect of active immunization against a recombinant mouse granulocyte-macrophage colony-stimulating factor/somatostatin fusion protein on the growth of mice - Bingbing Wu; Ruili Qi; Bin Li; Taoyan Yuan; Heshan Liu; Jun He; Zhiwei Lin; Weifen Li; Yan Fu; Dong Niu (Molecular Biology Reports, 2012)

Computational prediction and experimental assessment of an HLA-A*0201-restricted cytotoxic T lymphocyte epitope from neutral endopeptidase - Jingbo Zhang; Zhengcai Jia; Zhihua Lin; Jingyi Li; Xiaolan Fu; Yunjian Huang; Jinghong Zhao; Ling Nie; Weiping Hou; Fahuan Yuan; Yuzhang Wu (Immunologic Research, 2012)

Induced bone marrow mesenchymal stem cells improve cardiac performance of infarcted rat hearts - Xiao-Hong Li; Yong-Heng Fu; Qiu-Xiong Lin; Zai-Yi Liu; Zhi-Xin Shan; Chun-Yu Deng; Jie-Ning Zhu; Min Yang; Shu-Guang Lin; Yangxin Li; Xi-Yong Yu (Molecular Biology Reports, 2012)

Norcantharidin, a protective therapeutic agent in renal tubulointerstitial fibrosis - Ying Li; Yan Ge; Fu You Liu; You Ming Peng; Lin Sun; Jun Li; Qiong Chen; Yan Sun; Kun Ye (Molecular and Cellular Biochemistry, 2012)

Construction and characterization of a normalized cDNA library from the river snail Bellamya aeruginosa after exposure to copper - Zi-Cheng Li; Li-Hui An; Qing Fu; Ying Liu; Lei Zhang; Hao Chen; Xing-Ru Zhao; Li-Jing Wang; Bing-Hui Zheng; Lin-Bo Zhang (Ecotoxicology, 2012)

Late Triassic bivalves associated with a hydrothermal vent system in the Yidun Island Arc (SW China) of the eastern Tethys - Li Lin; LiDong Zhu; YanChun Pang; JinGeng Sha; Franz T. Fürsich; XiuGen Fu; XinLi Wang (Science China Earth Sciences, 2011)

Effects of air–sea coupling on the boreal summer intraseasonal oscillations over the tropical Indian Ocean - Ailan Lin; Tim Li; Xiouhua Fu; Jing-Jia Luo; Yukio Masumoto (Climate Dynamics, 2011)

Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves) - Hsu‐Chun Wu; Rong‐Chien Lin; Hsin‐Yi Hung; Chia‐Fen Yeh; Jui‐Hua Chu; Xiao‐Jun Yang; Chiou‐Ju Yao; Fa‐Sheng Zou; Cheng‐Te Yao; Shou‐Hsien Li; Fu‐Min Lei (Zoologica Scripta, 2011)
Wu, H.‐C., Lin, R.‐C., Hung, H.‐Y., Yeh, C.‐F., Chu, J.‐H., Yang, X.‐J., Yao, C.‐J., Zou, F.‐S., Yao, C.‐T., Li, S.‐H. & Lei, F.‐M. (2011). Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves). — Zoologica Scripta, 40 , 468–478. The Vinaceous Rosefinch ( Carpodacus vinaceus ) is endemic in East Asia with two recognized subspecies – C. v. vinaceus , distributed along the eastern edge of the Tibetan Plateau and the Himalayas, and C. v. formosanus , restricted to Taiwan’s Central Mountain Range. As reflected in a controversial taxonomic history, this vastly disjunctive distribution pattern suggests that the subspecies, having been isolated from each other for a long time, might have diverged, challenging the current taxonomic treatment and calling for possible species delimitation. Sequences of two mitochondrial fragments (mtDNA) and two Z‐linked nuclear loci (zDNA) were used to reconstruct the intraspecific phylogeny of C. vinaceous . The mtDNA tree shows that the two subspecies of the vinaceous rosefinch form two exclusively monophyletic clades. All but one zDNA sequences from the nominate subspecies and C. v. formosanus also formed exclusively monophyletic clades (the exceptional zDNA sequence from C. v. vinaceous formed a weakly supported clade with two outgroup species). Moreover, by conducting quantitative comparisons of morphometric traits and male plumage coloration, we found that the two subspecies exhibit distinguishable morphological differences. All the evidence therefore suggests that C. v. formosanus is a cryptic species and that its taxonomic status should be restored to full species. Molecular dating suggests that the two sibling rosefinches split 1.7 ± 0.2 million years ago, providing a point estimate for the historical connectivity of biota between eastern Tibet‐Himalayas and montane Taiwan.

Levels and Congener Profiles of Particle-bound Polybrominated Dibenzo-p-dioxins/furans (PBDD/Fs) in Ambient Air around Guangzhou, China - Huiru Li; Lin Zhou; Ligui Mo; Ping’an Peng; Guoying Sheng; Jiamo Fu; Zhiqiang Yu (Bulletin of Environmental Contamination and Toxicology, 2011)

Spatial heterogeneity of bacterial community structure in the sediments of the Pearl River estuary - Fu-Lin Sun; You-Shao Wang; Mei-Lin Wu; Yu-Tu Wang; Qian P. Li (Biologia, 2011)

Malignant transformation of 293 cells induced by ectopic expression of human Nanog - Yan-Li Lin; Zheng-Bin Han; Fu-Yin Xiong; Li-Yuan Tian; Xiao-Jie Wu; Shi-Wei Xue; Yan-Rong Zhou; Ji-Xian Deng; Hong-Xing Chen (Molecular and Cellular Biochemistry, 2011)

Differentiation of Fecal Escherichia coli from Human, Livestock, and Poultry Sources by rep-PCR DNA Fingerprinting on the Shellfish Culture Area of East China Sea - Hong-Jia Ma; Ling-Lin Fu; Jian-Rong Li (Current Microbiology, 2011)

Characterization of Exserohilum rostratum, a new causal agent of banana leaf spot disease in China - Shan-Hai Lin; Si-Liang Huang; Qi-Qin Li; Chun-Jin Hu; Gang Fu; Li-Ping Qin; Yue-Feng Ma; Ling Xie; Zhen-Lu Cen; Wei-Hong Yan (Australasian Plant Pathology, 2011)

Genomic sequence of an avian paramyxovirus type 1 strain isolated from Muscovy duck (Cairina moschata) in China - S.-H. Shi; Yu Huang; S.-J. Cui; L.-F. Cheng; G.-H. Fu; X. Li; Z. Chen; C.-X. Peng; F. Lin; J.-S. Lin; Jing-Liang Su (Archives of Virology, 2011)

Genotype and host range analysis of infectious spleen and kidney necrosis virus (ISKNV) - Xiaozhe Fu; Ningqiu Li; Lihui Liu; Qiang Lin; Fang Wang; Yingtiao Lai; Haiming Jiang; Houjun Pan; Cunbin Shi; Shuqin Wu (Virus Genes, 2011)

Dynamic Changes of Heme Oxygenase-1 in the Hippocampus of Rats After Acute Carbon Monoxide Poisoning - Li Guan; Yan-Lin Zhang; Tao Wen; Xi-Fu Wang; Ming-Xia Zhu; Jin-Yuan Zhao (Archives of Environmental Contamination and Toxicology, 2011)

Genetic analysis and characterization of a new maize association mapping panel for quantitative trait loci dissection - Xiaohong Yang; Jianbing Yan; Trushar Shah; Marilyn L. Warburton; Qing Li; Lin Li; Yufeng Gao; Yuchao Chai; Zhiyuan Fu; Yi Zhou; Shutu Xu; Guanghong Bai; et al. (Theoretical and Applied Genetics, 2010)

RNA Interference-Based Transgenic Maize Resistant to Maize Dwarf Mosaic Virus - Zhi-Yong Zhang; Feng-Ling Fu; Lin Gou; Han-Guang Wang; Wan-Chen Li (Journal of Plant Biology, 2010)

Epigenetic regulation of peanut allergen gene Ara h 3 in developing embryos - Guohua Fu; Yujuan Zhong; Chenlong Li; Yin Li; Xiaodong Lin; Bin Liao; Edward W. T. Tsang; Keqiang Wu; Shangzhi Huang (Planta, 2010)

Chloroplast transformation of rapeseed (Brassica napus) by particle bombardment of cotyledons - Lin Cheng; He-Ping Li; Bo Qu; Tao Huang; Jin-Xing Tu; Ting-Dong Fu; Yu-Cai Liao (Plant Cell Reports, 2010)

Comparison of approaches for efficient gene silencing induced by microRNA-based short hairpin RNA and indicator gene expression - Z. X. Shan; Q. X. Lin; C. Y. Deng; Z. L. Zhou; H. H. Tan; Y. H. Fu; X. H. Li; J. N. Zhu; L. P. Mai; S. J. Kuang; S. G. Lin; X. Y. Yu (Molecular Biology Reports, 2010)

FAK is involved in invasion and metastasis of hepatocellular carcinoma - Jing-Song Chen; Xiao-Hui Huang; Qian Wang; Xi-Lin Chen; Xin-Hui Fu; Hao-Xiang Tan; Long-Juan Zhang; Wen Li; Jiong Bi (Clinical & Experimental Metastasis, 2010)

Secular trend of genome types of respiratory adenovirus type 3 during 1983–2005: a study from Taiwan - Yung-Cheng Lin; Kuei-Hsiang Lin; Guan-Ming Ke; Min-Sheng Lee; Pei-Chin Lin; Hsin-Fu Liu; Li-Ching Hsu; Po-Liang Lu (Archives of Virology, 2010)

Subglottic adenoid cystic carcinoma mistaken for asthma - Hua-lin Wang; Lin Xu; Fu-jun Li (Journal of Zhejiang University-SCIENCE B, 2009)

Secretory expression of K88 (F4) fimbrial adhesin FaeG by recombinant Lactococcus lactis for oral vaccination and its protective immune response in mice - Chun Xia Hu; Zi Rong Xu; Wei Fen Li; Dong Niu; Ping Lu; Ling Lin Fu (Biotechnology Letters, 2009)

An efficient method to enhance gene silencing by using precursor microRNA designed small hairpin RNAs - Zhixin Shan; Qiuxiong Lin; Chunyu Deng; Xiaohong Li; Wei Huang; Honghong Tan; Yongheng Fu; Min Yang; Xi-Yong Yu (Molecular Biology Reports, 2009)

Secretory expression of K88 (F4) fimbrial adhesin FaeG by recombinant Lactococcus lactis for oral vaccination and its protective immune response in mice - Chun Xia Hu; Zi Rong Xu; Wei Fen Li; Niu Dong; Ping Lu; Ling Lin Fu (Biotechnology Letters, 2009)

Seasonal changes in tannin and nitrogen contents of Casuarina equisetifolia branchlets - Li-hua Zhang; Gong-fu Ye; Yi-ming Lin; Hai-chao Zhou; Qi Zeng (Journal of Zhejiang University-SCIENCE B, 2009)

Fluorescent co-localization of PTS1 and PTS2 and its application in analysis of the gene function and the peroxisomal dynamic in Magnaporthe oryzae - Jiao-yu Wang; Xiao-yan Wu; Zhen Zhang; Xin-fa Du; Rong-yao Chai; Xiao-hong Liu; Xue-qin Mao; Hai-ping Qiu; Yan-li Wang; Fu-cheng Lin; Guo-chang Sun (Journal of Zhejiang University-SCIENCE B, 2008)

Emission of fine organic aerosol from traditional charcoal broiling in China - Ximei Hou; Guoshun Zhuang; Yanfen Lin; Juan Li; Yilun Jiang; Joshua S. Fu (Journal of Atmospheric Chemistry, 2008)

The chemistry of heavy haze over Urumqi, Central Asia - Juan Li; Guoshun Zhuang; Kan Huang; Yanfen Lin; Qiongzhen Wang; Yuhong Guo; Jinghua Guo; Shulong Yu; Caixia Cui; Joshua S. Fu (Journal of Atmospheric Chemistry, 2008)

Genome sequence and characterization of a new virus infecting Mikania micrantha H.B.K. - Rui-Long Wang; Ling-Wen Ding; Qiao-Yang Sun; Jing Li; Zeng-Fu Xu; Shao-Lin Peng (Archives of Virology, 2008)

Antifungal substances produced by Penicillium oxalicum strain PY-1—potential antibiotics against plant pathogenic fungi - Liping Yang; Jiatao Xie; Daohong Jiang; Yanping Fu; Guoqing Li; Fangcan Lin (World Journal of Microbiology and Biotechnology, 2008)

Magnaporthe oryzae MTP1 gene encodes a type III transmembrane protein involved in conidiation and conidial germination - Qin Lu; Jian-ping Lu; Xiao-dong Li; Xiao-hong Liu; Hang Min; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2008)

White-spot disease of Chinese soft-shelled turtles (Trionyx sinens) caused by Paecilomyces lilacinus - Xiao-liang Li; Chu-long Zhang; Wei-huan Fang; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2008)

High-Level Secretion of a Chimeric Thermostable Lichenase from Bacillus subtilis by Screening of Site-Mutated Signal Peptides with Structural Alterations - Ling-lin Fu; Zi-rong Xu; Jiang-bing Shuai; Chun-xia Hu; Wei Dai; Wei-fen Li (Current Microbiology, 2008)

A novel thioredoxin reductase inhibitor inhibits cell growth and induces apoptosis in HL-60 and K562 cells - Zuo-fu Peng; Lin-xiang Lan; Fang Zhao; Jing Li; Qiang Tan; Han-wei Yin; Hui-hui Zeng (Journal of Zhejiang University-SCIENCE B, 2008)

Selection of DNA aptamers against DC-SIGN protein - Yan Hui; Li Shan; Zhou Lin-fu; Zhu Jian-hua (Molecular and Cellular Biochemistry, 2007)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Using EEFM (Excitation Emission Fluorescence Matrix) to Differentiate the Organic Properties of the Effluents from the Ozonated Biofilters - Wen-Liang Lai; Lih-Fu Chen; Shao-Wei Liao; Shu-Lin Hsu; Li-Ho Tseng; Chang-Ling Miaw (Water, Air, & Soil Pollution, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

Genes expression analyses of sea-island cotton (Gossypium barbadense L.) during fiber development - Li-Li Tu; Xian-Long Zhang; Shao-Guang Liang; Di-Qiu Liu; Long-Fu Zhu; Fan-Chang Zeng; Yi-Chun Nie; Xiao-Ping Guo; Feng-Lin Deng; Jia-Fu Tan; Li Xu (Plant Cell Reports, 2007)

Origin of seed shattering in rice (Oryza sativa L.) - Zhongwei Lin; Megan E. Griffith; Xianran Li; Zuofeng Zhu; Lubing Tan; Yongcai Fu; Wenxu Zhang; Xiangkun Wang; Daoxin Xie; Chuanqing Sun (Planta, 2007)

Localization of vesicular glutamate transporters in the peripheral vestibular system of rat - Yuan Wang; You-Wang Pang; Yu-Lin Dong; Fu-Xing Zhang; Jin-Lian Li; Yun-Qing Li (Neuroscience Bulletin, 2007)

Fibrarecisin, a novel triterpenoid from Fibraurea recisa with antitumor activity - Jiao-Long Fu; Chang-Heng Tan; Li-Ping Lin; Ji Huang; Da-Yuan Zhu (Natural Product Research, 2007)

Preliminary validation of high performance liquid chromatography method for detection of methyl-testosterone residue in carp muscle - Jie Jiang; Hong Lin; Xiaoting Fu; Mingming Li (Journal of Ocean University of China, 2005)

High polyphenol oxidase activity and low titratable acidity in browning bamboo tissue culture - Li-Chun Huang; Ya-Lin Lee; Bau-Lian Huang; Ching-I Kuo; Jei-Fu Shaw (In Vitro Cellular & Developmental Biology - Plant, 2002)

Topaz–albite granites and rare-metal mineralization in the Limu District, Guangxi Province, southeast China - Jin-Chu Zhu; Ren-Ke Li; Fu-Chun Li; Xiao-Lin Xiong; Feng-Ying Zhou; Xiao-Long Huang (Mineralium Deposita, 2001)